Ergothioneine improves methane recovery and reduces indicators of oxidative stress in ammonia-stressed food waste anaerobic digestion - Xinyu Zhang; Linyan He; Wenjing Zhang; Jiali Chen; Shenghua Zhang; Binquan Jiao; Hong Cheng; Li Gu; Jiang Li (Bioresource Technology, 2027)

Environmental chemistry for the future: challenges, applications, and new AI-enabled pathways - Bo Weng; Minghui Zheng; Lijun Wu; Wei Chen; Cheng Gu; Liang Mao; Hui Li; Chiheng Chu; Qian Sui; Wei Zhang; Wei Shi; Qiancheng Xia; et al. (ENGINEERING Environment, 2026)

Stability of ultra-high pressure treated freshly squeezed Hami melon juice under simulated commercial cold chain conditions - Jinxiao Cheng; Congcong Huai; Di Shen; Yining Xia; Yang Yang; Yifan Gu; Jiakai Yu; Lingling Pang; Jia Liu; Yanfang Pan (Food Control, 2026)

Microspheres for bioactive substances delivery in the food industry: Materials, preparation technology, and applications - Ruidi He; Yan Hong; Lingjin Li; Li Cheng; Zhengbiao Gu (Trends in Food Science & Technology, 2026)

Carbon-efficient ride-pooling at intercity railway hubs: Nonlinear topological mechanisms and algorithmic insights - Zechao Ma; Tianqi Gu; Jiayan Zhang; Long Cheng; Inhi Kim; Bin Yu (Transportation Research Part D: Transport and Environment, 2026)

Fe-carbon-microbe coupling mediated CO₂ emission enhancement by dissolved black carbon in riparian soils - Yushu Yang; Zhenchen Li; Xiaoyun Li; Hongyi Wang; Li Gu; Hong Cheng; Binquan Jiao; Weiliang Pan (Soil and Tillage Research, 2026)

Urea-induced nitrogen-rich pyrolysis for co-upgrading of sludge-derived biochar and bio-oil - Ruizhi Wang; Junhong Chen; Jinze Li; Yi Yang; Li Gu; Dezhi Shi; Hong Cheng; Weiliang Pan; Yongdong Chen (Fuel, 2026)

Insights into specific and nonspecific butyrate-producing pathways during the in vitro fecal fermentation of butyrylated starch - Lingjin Li; Mengyuan Qin; Zhiqiang Xu; Yuanteng Xu; Yan Hong; Li Cheng; Zhengbiao Gu (Food Research International, 2026)

Modified β-glucans promote saponin and fucosylated chondroitin sulfate biosynthesis in sea cucumber Apostichopus japonicus in association with activation of the TLR-MAPK signaling pathway - Zezheng Qi; Zeyu Zhang; Wenyue Dai; Hongmei Ma; Junpeng Ge; Yutong Yu; Mengling Cheng; Wenjian Zhao; Shihui Pan; Min Gu; Nan Bai (Fish & Shellfish Immunology, 2026)

Association of combined exposure to polycyclic aromatic hydrocarbons, BTX and metals with metabolic syndrome risk - Xiaoyu Hao; Xiangkai Zhao; Zhiguang Gu; Bin Yang; Di Zhang; Rui Zhao; Xu Guo; Zhe Cheng; Gang Wang; Xiaohui Li; Junfeng Zhao; Zhiheng Li; et al. (Environmental Pollution, 2026)

Interface chemical bonding triggered rapid charge transfer for efficient photocatalytic H2 evolution on indium proximal to sulfur vacancy - Hui Chang; Cheng Luo; Pengrong Gu; Xiaojun Zheng; Wenjuan Fan; Hao Fu; Yufeng Li; Hu Li; Zhiqiang Jiang (Chemical Engineering Journal, 2026)

Deep learning based pore detection of welded connection plates and its creep prediction - Shuohui Yin; Xinlong Cheng; Baoyin Zhu; Dongpeng Li; Dungui Zuo; Shuitao Gu; Gongye Zhang (Annals of Nuclear Energy, 2026)

From anxiety to advantage: a multi-year longitudinal evidence of behavioral and spatial adaptation in electric ride-hailing - Zechao Ma; Tianqi Gu; Graham Currie; Long Cheng; Inhi Kim (Travel Behaviour and Society, 2026)

Spatio-temporal-functional assembly of Daqu microbiome: Mechanistic insights and quality improvement - Rui Ma; Xiaojie Nan; Yanting Li; Yuanyu Su; Mingxia Cheng; Yujie Zhang; Yang Cui; Qiong Zhou; Jingang Gu; Shang Guo (Food Research International, 2026)

Preparation and physicochemical properties of mitochondria-targeted starch nanoparticles - Mengyuan Qin; Yan Hong; Lingjin Li; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban (Food Research International, 2026)

Effect of redox status on the metabolic characteristics and microbiota composition of high-amylose maize starch during in vitro fermentation - Zehao Huang; Yi Zhang; Lingjin Li; Yahui Gao; Zhengbiao Gu; Li Cheng; Yan Hong (Food Chemistry, 2026)

Starch chain architecture and digestibility: Mechanistic links, kinetic descriptors, and routes toward prediction - Yexian Hu; Yuhan Ji; Zhengbiao Gu; Yan Hong; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Lingjin Li; Li Cheng (Carbohydrate Polymers, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

A bifunctional triblock zwitterionic copolymer combined with gold nanostars for antifouling electrochemical aptasensor to detect chloramphenicol in food samples - Jinzhi Liang; Cheng Zhang; Xian Chen; Kun Ge; Qi Zhang; Ying Gu (Analytica Chimica Acta, 2026)

Comprehensive application of multispectral data for alteration mapping in the volcanogenic massive sulphide deposit: a case study in Baiyin area, China - Hanyin Zhang; Sanyou Cheng; Xiaobo Liu; Pingyang Gu; Bo Ji; Qi Qi (International Journal of Remote Sensing, 2026)

The protective effect and mechanism of Piezo1 inhibition on blood-brain barrier injury after focal cerebral ischemia-reperfusion in rats - Chu-hua Gu; Wen-qi Song; Jia-yi Gan; Kuan Zheng; Xiao-hui Ding; Wei-cheng Lu; Hui Xie (Neurophysiology, 2026)

In-Season monitoring of rice phenology for massive germplasm resources using Explainable Machine learning and a Transformer CNN model - Xiaoxu Han; Yangyang Gu; Hengbiao Zheng; Di Wang; Fangming Wu; Meng Zhou; Hongxu Ai; Timothy A. Warner; Chongya Jiang; Tao Cheng; Yongchao Tian; Yan Zhu; et al. (Computers and Electronics in Agriculture, 2026)

Multimodal deep fusion of Low-Field NMR and proton Density-Weighted imaging for interpretable detection of Saline-Alkali stress in wheat - Ying Gu; Guoqing Feng; Ya’nan Zhou; Han Zhang; Cheng Wang; Liping Chen; Bin Luo (Computers and Electronics in Agriculture, 2026)

Perfluorocarboxylic acid toxicity analysis with albumin/1-anilinonaphthalene-8-sulfonate probe assisted by machine learning - Xinda Wu; Yicong Ma; Ziyao Liu; Cheng Gu (Water Research, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Impact of tannic acid on starch structure, properties, and applications: Comprehensive review - Feng Jiang; Mengyuan Qin; Yan Hong; Lingjin Li; Li Cheng; Zhengbiao Gu (Trends in Food Science & Technology, 2026)

Corrosion characteristics and support performance degradation mechanism of bolts in high-corrosion mines - Wenzhe Gu; Chengyong Liu; Jingyi Cheng; Chaofeng Yuan; Fengtian Sheng; Xin Sun; Hua Wang; Jie Xu; Ruiyan Wang (Process Safety and Environmental Protection, 2026)

Tether-aware dynamic collision avoidance for USV–HROV marine robotic systems - Yang Gu; Ziyang Hong; Xuanlin Chen; Hao Wei; Cheng Wang; Yulin Si (Ocean Engineering, 2026)

Structural phase transition–aligned preheating reprograms lipid-derived flavor formation in cooked meat: A case of lamb - Le Xu; Minghui Gu; Yina Chen; Shaobo Li; Xin Li; Cheng Li; Xiaochun Zheng; Li Chen; Dequan Zhang (Food Chemistry, 2026)

From protein structural reconfiguration to long-term emulsion stabilization: How ultrasound-microwave synergistic modulates no-added-salt myofibrillar protein-based emulsions through multiscale interfacial assembly - Yufeng Chen; Siqi Lan; Jipeng Gu; Weiwei Cheng; Xuxia Zhou; Shulai Liu; Yuting Ding (Food Chemistry, 2026)

Starch-based emulsion gels enhanced probiotic viability: effect of amylose content - Ziqi Chen; Zhengbiao Gu; Li Cheng; Yan Hong (Food Hydrocolloids, 2026)

Methoxycarbonylation of ethylene/ethane mixture to methyl propionate over Pd-phosphine system with H-Beta zeolite and sulfonic acid as acid promoters - Shaoxia Guo; Mengting Li; Liang Gao; Yongrui Wang; Cheng Gu; Longxiao Yang; Yuping Huang; Enhui Xing; Yibin Luo; Xinbin Ma; Xingtian Shu (Chemical Engineering Journal, 2026)

Dual-color switchable sensing platform based on dual-emission chiral carbon dots for specific and visual detection of cystatin C - Daohong Cheng; Wanqing Ni; Na Yu; Xinru Gu; Enqi Liu; Siyu Zhou; Tianyu Wei; Xingyi Ma; Guoying Sun; Yibing Liu (Chemical Engineering Journal, 2026)

Intrinsic waste component synergy: calcium-rich eggshell waste modulates fungal-bacterial microbiome toward selectively medium-chain fatty acid production - Xiang Li; Shuanglan Cheng; Xinjie Wang; Xia Gu; Xianbao Xu; Xu Duan; Gang Xue; Piotr Oleskowicz-Popiel; Jiajie Xu; Bin Liu; Zhihong Liu; Aijuan Zhou; et al. (Bioresource Technology, 2026)

Lactococcus cremoris subsp. sagaensis subsp. nov., Isolated from Naturally Fermented Yogurt - Lin Cheng; Tian-Xue Wang; Chun Yan Li; Chaoxin Man; Chun Tao Gu (Current Microbiology, 2026)

Correction to: Landslide susceptibility mapping based on InSAR coherence rainfall components and deep learning: a case study of Lanping county in Southwest China - Yongfa Li; Zhuopei Ruan; Xiaoqing Zuo; Xiaona Gu; Yujuan Dong; Yongning Li; Chao Shi; Cheng Huang; Wenbin Xie; Qinheng Zou; Jingsong Xiao (Bulletin of Engineering Geology and the Environment, 2026)

Geochemical associations and local prediction of rare earth elements in fine-grained stream and pond sediments from agricultural catchments (SW France) - Xinda Wu; Cheng Gu; Anne Probst (Applied Geochemistry, 2026)

Effects of different diet energy levels on growth performance and blood parameters in Hanwoo calves under heat stress - Eui Beom Chung; Won Seob Kim; Xue Cheng Jin; Bo Mi Kim; Jun Hee Lee; Keun Kyu Park; Hong Gu Lee (Animal Feed Science and Technology, 2026)

SWMFA-UNet: Joint Spatial-Wavelet-Fourier modeling for landslide segmentation in remote sensing images - Cheng Chai; Mingzhe Liu; Dongfen Li; Chenliang Wang; Haihua Ding; Mingrong Xiang; Xubo Gu; Dehao Li (Advances in Space Research, 2026)

Monoterpenoid indole alkaloids from the aerial parts of Tabernaemontana divaricata (L.) R. Br. ex Roem. & Schult. and their anti-inflammatory activity and cytotoxicity on acute leukaemia cells - Wan-Qi Yang; Cai-Xia Wen; Er-Gu Chen; Ren-Feng Ye; Min Jiang; Gui-Guang Cheng; Ya-Ping Liu (Natural Product Research, 2026)

Enhancing aboveground biomass estimation for winter wheat using UAV-based color space transformation and spectral feature reconstruction - Yang Xu; Xiaobo Gu; Penglin Li; Bowen Sun; Zhikai Cheng; Tongtong Zhao; Zhengtao Zhang; Chunyu Wei; Yadan Du (Soil and Tillage Research, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Cadmium transfer from tungsten mining and refining to soil, plants, and humans: Geochemical baseline and probabilistic human health risk - Yifan Lin; Hongguang Cheng; Xiang Gu; Chunye Lin (Science of The Total Environment, 2026)

Corrigendum to “Understanding the influence of energy and chemica use on water treatment plants carbon emissions accounting” [J. Water Process Eng. 69 (2025) 106669] - Mohamed Yateh; Cheng Li; Fengting Li; Chunping Gu; Shunjun Ma; Binbin Lu; Yulin Tang (Journal of Water Process Engineering, 2026)

Green synthesis of a histidine-copper biomimetic enzyme for sustainable degradation of sulfamethoxazole in aquaculture wastewater - Yini Zhao; Long Cheng; Tao Yu; Long Gu; Xiangyi Zhang; Hangfei Gao; Zhicen Liu; Ze Fan; Ting Yan; Dongli Qin; Xinyue Zhao; Haijiao Xie; et al. (Journal of Environmental Chemical Engineering, 2026)

Macrophyte-to-algae transition: Suspended particulate matter mediates the bioavailability and retention of heavy metal(loid)s in the sediment - Wenxuan Han; Yiheng Du; Xue Sun; Zhaode Wang; Lei Zhang; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Journal of Environmental Chemical Engineering, 2026)

Desensitizing mechanism of LBGP70 on peanut allergy: Competitive inhibition and allosteric regulation of DC-SIGN on dendritic cells - Ziqian Su; Aiqin Gu; Zejun Zhao; Wei Cao; Ni Cheng; Huxue Deng; Jinyang Huang; Yang Tian (Food Chemistry, 2026)

A health-oriented strategy for identifying and controlling high-risk PM2.5 sources: Case study of Heze - Xianmang Xu; Jingsen Zhao; Ying Li; Kun Liu; Chao Zhu; Lei Sun; Tao Li; Wenli Gu; Lidan Xu; Juan Dai; Jin Wang; Wei Cheng; et al. (Environmental Research, 2026)

Unveiling the structural requirements for congener-specific biodegradation of polybrominated diphenyl ethers by Burkholderia xenovorans LB400: A combined QSAR study - Chenggang Gu; Lezu Shen; Zhengyuan Gao; Xiuli Fan; Xinglun Yang; Zunyao Wang; Cheng Sun; Fang Wang; Xin Jiang (Environmental Research, 2026)

Effect of salinity on critical entrainment of fluid mud: a case study in the Yangtze River Estuary - Qi Shen; Xiaoxiao Wu; Jie Zhang; Wenrui Huang; Hualin Wu; Qin Zhu; Fengfeng Gu; Haifeng Cheng (Estuarine, Coastal and Shelf Science, 2026)

Quantum reinforcement learning for dynamic multi-objective energy management in community microgrids - Yan Gu; Huiru Yan; Qingle Wang; Cong Liu; Cheng Liu; Long Cheng (Energy and Buildings, 2026)

Enhanced performance of a heat-exchange vacuum membrane distillation (HE-VMD) module integrating polymer hollow-fiber tubes - Cheng Wu; Fangli Zhang; Chenyang Gu; Zhaohui Wang; Zhaoliang Cui (Desalination, 2026)

Spatiotemporal Dynamics and Source of CDOM in Gehu Lake, Taihu Basin, China - Cheng Gu; Tao Song; Jiehong Cheng; Xiangen Xu (Water, Air, & Soil Pollution, 2026)

Landslide susceptibility mapping based on InSAR coherence rainfall components and deep learning: a case study of Lanping county in Southwest China - Yongfa Li; Zhuopei Ruan; Xiaoqing Zuo; Xiaona Gu; Yujuan Dong; Yongning Li; Chao Shi; Cheng Huang; Wenbin Xie; Qinheng Zou; Jingsong Xiao (Bulletin of Engineering Geology and the Environment, 2026)

Genetic Variants in EMT-Related lncRNAs Modulate the Risk of Colorectal Cancer in the Chinese Population - Simeng Gu; Zhaohui Zhang; Keyi Cheng; Aibuta Yeerken; Sangni Qian; Fanjia Guo; Mingjuan Jin; Kun Chen (Biochemical Genetics, 2026)

Preparation Strategies and Application Progress of Coal-Based Carbon Dots - Zishuo Gu; Wei Zhao; Shuang Pang; Chaoshuai Hu; Junxia Cheng; Xuefei Zhao; Yaming Zhu (Journal of Fluorescence, 2026)

Microplastics in China’s commercial crayfish (Procambarus clarkii): Tissue-specific characteristics and potential human health risks - Qingyuan Guo; Yu Zhang; Qingqin Meng; Ziyou Gu; Xiaomei Shen; Mingzhe Cai; Cheng Ding; Min Xu (Environmental Monitoring and Assessment, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Synergistic T cell and microbiome dysregulation in FOXP3-mediated immune enteritis: insights from multimodal omics - Meiling Jin; Cheng Jin; Shunlai Shang; Yuqing Gu; Peng Jin; Haibin Yu; Diangeng Li (Science China Life Sciences, 2026)

Novel eudesmanolides from the flowers of Pentanema britannicum (L.) D.Gut.Larr with antidepressant activities - Yu-Qing Xie; Xin-Yue Zhang; Jun-Hui Zhang; Ping He; Sheng-He Yang; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Effects of dietary fiber from different particle sizes of wheat bran on myofibrillar protein structure - Jinling Li; Shunfan Gu; Ying Mao; Wenjing Huang; Huaying Liu; Cheng Guo; Jian Xia; Weiping Jin; Wangyang Shen (Food Research International, 2026)

High-amylose maize starch as a functional carbohydrate: Long-term regulation of glucose homeostasis following early-life intervention - Zhiqiang Xu; Lingjin Li; Li Cheng; Zhengbiao Gu; Yan Hong (Food Research International, 2026)

Indium-doped CuSnO3 perovskite hybrids for chemiresistive CO sensing - Linyan Gu; Yangtao Qian; Yiting Liu; Miao Cheng; Tao Wei; Qianqian Liu; Ruirui Wang; Wanfei Li; Zhenxiao Fu; Haiyang Jiang; Zibo Li; Bo Liu; et al. (Chemical Engineering Journal, 2026)

Effect of degree of substitution on the structural degradation and butyric acid production of butyrylated starch during in vitro fermentation - Yi Zhang; Yan Hong; Yuanteng Xu; Zhengbiao Gu; Li Cheng; Lingjin Li (Carbohydrate Polymers, 2026)

Robust nitrile hydratase design via molecular dynamics simulations: synergistic enhancement of stability, activity, and aromatic substrate tolerance - Ran Gu; Julia Berdychowska; Yiwei Meng; Zhongyi Cheng; Junling Guo; Lukasz Peplowski; Zhemin Zhou (Systems Microbiology and Biomanufacturing, 2026)
Nitrile hydratase (NHase) is a promising biocatalyst for the industrial synthesis of high value amides, yet its practical application is often limited by conformational instability and activity loss under high product concentrations. In this study, we employed a rational engineering strategy guided by molecular dynamics simulations in high amide concentrations to elucidate the structural dynamics of NHase acrylamide/water mixed solvents and identify key residues governing its stability. Through systematic mutagenesis, we developed a double mutant, βV4I/βI177K (designated M1), which exhibited a 2.2-fold increase in specific activity toward acrylonitrile, a 1.7-fold improvement in catalytic efficiency, and a 9.6-minute extension (corresponding to a 37% increase in enzyme durability) in thermal inactivation half-life compared to the wild-type enzyme. Under simulated industrial conditions, the superior catalytic stability and conversion efficiency of M1 resulted in a 1.3-fold increase in acrylamide yield. Furthermore, the mutant displayed broadened substrate adaptability, with activities toward 1-naphthonitrile and cinnamonitrile enhanced by 2.98- and 3.34-fold, respectively. These findings not only reveal the molecular mechanism underlying NHase inactivation acrylamide/water mixed solvents but also establish a robust engineering framework for developing highly efficient and stable biocatalysts for industrial amide synthesis.

Root residue mass loss of Leymus chinensis stimulates macro and mesofauna activity and enhances carbon accumulation in Songnen grasslands - Zhiwei Gu; Mengqi Jiang; Cheng Wang; Luxin Li; Long Yan; Hongyu Zhao; Tianyue Yang; Shouqi Deng; Xiaoqiang Li; Weihua Dong (Biology and Fertility of Soils, 2026)

Cyclodextrin glycosyltransferases for food innovation: from molecular mechanism to industrial application - Zihang Jiang; Tong Zhu; Zhengbiao Gu; Zhaofeng Li; Xiaofeng Ban; Yan Hong; Li Cheng; Caiming Li (Critical Reviews in Food Science and Nutrition, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Rapid behavioral regulations facilitate the formation of a novel migration route in swan geese - Zhongru Gu; Juan Long; Xinying Shi; Xin Liu; Zhuoran Kuang; Zhenyu Zhong; Jiade Bai; Zhibin Cheng; Nyambayar Batbayar; Batbayar Bold; Libo Zhou; Junfeng Chen; et al. (Science Bulletin, 2026)

Scenario-based assessment and rapid prediction of wharf mooring risk using an integrated FAHP–BN–RSM framework - Fangxin Hu; Yao Cheng; Chuanen Ji; Jiayang Gu; Shuai Zong; Renwei Ji; Pei Zhang; Peng Dou; Yihan Xing; Xiaosen Xu; Shuaishuai Wang (Ocean Engineering, 2026)

Soil texture modulates the impact of biodegradable microplastics on N2O emissions in agroecosystems - Ya Li; Fengxiao Zhu; Zhuyao Hua; Xiaomei Wang; Sha Chang; Changyin Zhu; Shiyin Li; Huan He; Cheng Gu (Journal of Hazardous Materials, 2026)

Valorization of vitamin C industrial byproduct as a soil amendment: Environmental benefits and enhancement of maize productivity - Haotian Cheng; Hao Sun; Jian Gu; Weichao Yang; Mingfu Gao; Hui Xu (Journal of Environmental Management, 2026)

Unveiling the regulation of biochar and ferrihydrite on organic carbon stabilization, CH4 emission and microbial community in paddy soil - Ran Zhang; Yujing Gu; Linrui Zhong; Yuantao Xu; Fanzhi Qin; Hong Qin; Qian Liu; Jiali Cheng; Jiahui Lei; Jingwen Yan; Yi Yin; Yue Lu (Journal of Environmental Sciences, 2026)

Synergistic regulation of composite films by starch chain-length distribution and chitosan molecular weight - Yilin Dong; Zhaofeng Li; Xiaofeng Ban; Zhengbiao Gu; Li Cheng; Yan Hong; Danyang Li; Caiming Li (Food Hydrocolloids, 2026)

An active cling film developed from pomelo peel for synergistic preservation of Oncorhynchus mykiss: Utilizing K/Fe enzyme-like materials and natural extracts - Tao Yu; Long Cheng; Yini Zhao; Long Gu; Hangfei Gao; Zicen Liu; Li Huang; Shuyan Bai; Dongli Qin; Peng Wang; Aimin Wang; Haijiao Xie; et al. (Food Packaging and Shelf Life, 2026)

Metal complexation-triggered chromogenic reaction and fluorescence response: A universal dual-mode sensing strategy for fast visualization of heavy metal ions - Shuangshou Wang; Zan Wang; Ruohan Xu; Cheng Cheng; Yujun Zhong; Jia Yang; Mingfu Ye; Jinying Chen; Yuxi Gu; Jingchong Yan (Environmental Research, 2026)

Bats as pest-fighting pioneers: Seasonal contributions in South China’s mountainous agroecosystem - Chen Zhang; Hao Gu; Jie Peng; Zheng Cheng; Gang Liu; Jiang Feng; Ying Liu (Agriculture, Ecosystems & Environment, 2026)

Enhancing winter wheat yield estimation by synergizing UAV remote sensing and a hybrid PROSAIL–AquaCrop data assimilation framework - Yang Xu; Xiaobo Gu; Jingya Liu; Ximeng Li; Gengmin Jiang; Zhikai Cheng; Haowei Yin; Tongtong Zhao; Yadan Du; Shikun Sun; Huanjie Cai (Agricultural and Forest Meteorology, 2026)

Correction to: RP13 516M14.1 Regulates Autophagy Through miR 429 via Both a ceRNA Network and Direct Interaction - Zhijian Yang; Anyu Zeng; Baoxi Yu; Chao Xie; Weiwen Zhu; Hailong Liu; Cheng Gu; Ming Fu (Biochemical Genetics, 2026)

Promoter-driven enhancement of PHBV synthesis in recombinant Escherichia coli using glucose and propionate as carbon sources - Zhao-song Huang; Cheng-jiao Yu; Zi-miao Yan; Chang-feng Miao; Ling-yi Hou; Peng-fei Gu; Xiang-yu Fan; Qiang Li (Archives of Microbiology, 2026)

Extraction of High-Resolution Target Highlights in Reverberant Background - Cheng Wang; Fangyong Wang; Xinyu Gu; Yuqing Mao; Guangping Zhu (Marine Geodesy, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Redox oscillations in riparian zone stimulate carbon loss by enhancing microbial respiration - Zhenchen Li; Xiaoyun Li; Binquan Jiao; Yushu Yang; Hongyi Wang; Li Gu; Hainan Ai; Hong Cheng; Shang Cheng (Water Research, 2026)

Mechanisms of cavitation-induced instability and performance loss in bulb tubular turbines - Xiaotong Song; Zhenggui Li; Shenglong Gu; Chuang Cheng; Meng Liu; Shouchun Liu; Hang Xin; Yanxiong Jiao; Wei Hua (Ocean Engineering, 2026)

Enhanced photoreduction of perfluorooctane sulfonate via a confined nitrilotriacetic acid system augmented by CTAB - Zhenyu Zhai; Yunmeng Zhao; Chaojie Zhang; Xuefei Zhou; Yalei Zhang; Sijie Lin; Xueran Xu; Xiang Liu; Di Huang; Yingping Huang; Cheng Gu (Journal of Hazardous Materials, 2026)

Integrated rational design and chemical modification for enhanced catalytic efficiency of Gt-GBE from Geobacillus thermoglucosidans - Yuxuan Cao; Chunyan Huang; Lei Wei; Zhengbiao Gu; Zhaofeng Li; Caiming Li; Yixiong Tian; Danyang Li; Yan Hong; Li Cheng; Xiaofeng Ban (Food Bioscience, 2026)

Starch as a designable platform for oral drug delivery: From structural modulation to application in inflammatory bowel disease - Mengyuan Qin; Feng Jiang; Yan Hong; Lingjin Li; Yongmin Cui; Canran Jin; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban (Carbohydrate Polymers, 2026)

Robust and precise three-dimensional printing of high-amylose starch gels via concentrated calcium chloride regulation - Jianyu Ren; Xianyao Li; Yubo Huang; Zhengbiao Gu; Yan Hong; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Li Cheng (Carbohydrate Polymers, 2026)

Comprehensive source health risks of PM2.5-bound trace metals in urban and rural areas of the North China Plain - Qingxia Ma; Shuangshuang Zou; Guoqing Zhao; Kaixin Cheng; Yunfei Wu; Renjian Zhang; Lei Gu; Xiaolei Bao; Quanzhou Han; Daiqi Ye (Atmospheric Pollution Research, 2026)

Soil legacy effects in soybean intercropping enhance tobacco resistance to Fusarium root rot - Yuhao Dai; Chengzhi Wen; Zhijun Cheng; Zipeng Gao; Zhihui Wang; Peng Zhao; Mingshi Ding; Zhen Yang; Qiming Zhou; Jinpeng Gu; Dingguo Han; Lei Yang; et al. (Applied Soil Ecology, 2026)

New nor-tirucallane triterpenoid with antitumor activity from Ailanthus altissima (mill.) swingle - Can Liu; Jun-ling Guo; Shuo-yu Zhao; Ning-ning Shi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Functional factors for precision nutrition interventions in starch-based delivery systems - Mengyuan Qin; Lingjin Li; Jing Du; Yan Hong; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban (Critical Reviews in Food Science and Nutrition, 2026)

Monitoring vertical SPAD distribution of winter wheat using UAV cross-circle oblique photography - Yang Xu; Xiaobo Gu; Zhikai Cheng; Yadan Du; Penglin Li; Chunyu Wei; Tongtong Zhao; Zhengtao Zhang; Jingya Liu (Computers and Electronics in Agriculture, 2026)

In-Situ sulfur implantation efficiently promoting nitrogen removal in low-carbon anoxic-oxic systems - Jia-Min Xu; Miao Gu; Yi-Fan Zhang; Guodong Zhang; Jia-Qiang Lv; Yu-Qi Wang; Yao Chen; Guijiao Zhang; Daheng Ren; Xuchen Ba; Bin Gao; Hao-Yi Cheng (Water Research, 2026)

Luteolin exhibits broad-spectrum antiviral activity against swine enteric coronaviruses by targeting 3CLpro - Xiaoxu Xing; Jiongze Cheng; Huinan Li; Ming Liu; Minghui Gu; Jiawei Xiao; Hansong Li; Lan Bi; Feiyu Zhao; Haixin Liu; Donghua Guo; Mingjun Su; et al. (Veterinary Microbiology, 2026)

The Holocene hydroclimatic changes, palsa peatland development and vegetation history in the inner part of the Central Siberian Plateau (Russia) - Elena Yu. Novenko; Anatoly S. Prokushkin; Natalia G. Mazei; Elya P. Zazovskaya; Dmitry A. Kupriyanov; Anton E. Shatunov; Rodion A. Andreev; Ekaterina A. Makarova; Maria V. Kusilman; Alexander A. Komarov; Xiuyuan Gu; Andrey N. Tsyganov; et al. (Quaternary International, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Multi-omics analysis uncovers an integrated network that reshapes flavor compound profile of goji bud tea by fermentation - Yajie Zhao; Chencheng Gu; He Qian; Weirong Yao; Yuliang Cheng (International Journal of Food Microbiology, 2026)

Effects of removing endogenous non-starch components on the structure, physicochemical properties, and in vitro digestibility of Castanopsis sclerophylla flour - Jianan Zhao; Mingyi Shen; Ruifang Wang; Zhengbiao Gu; Yan Hong; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Li Cheng (Food Research International, 2026)

Integrated bioinformatics and quantitative lipidomics reveal temporal lipid dynamics and oxidative metabolic networks in refrigerated pork - Minghui Gu; Cheng Li; Yuqing Ren; Li Chen; Shaobo Li; Dequan Zhang; Xiaochun Zheng (Food Research International, 2026)

Dityrosine induces myocardial injury via Ang II-MAPK-Nrf2 pathway-mediated oxidative stress, mitochondrial dysfunction, and fibrosis in mice - Yin-Yi Ding; Jia Chen; Yuxin Wang; Zhenyu Gu; Tianyuan Song; Yujun Ge; Tianming Xuan; Oushan Tang; Qing Shen; Keyun Cheng (Food and Chemical Toxicology, 2026)

Integrating multiple crop models and multi-source data in a knowledge-guided deep learning framework for wheat and maize yield forecasting in the Huang-Huai-Hai Plain, China - Zhikai Cheng; Xiaobo Gu; Yuanling Zhang; Xiaohai Fang; Yang Xu; Shikun Sun; Yadan Du; Huanjie Cai (Field Crops Research, 2026)

Forecasting crop yield through a data-driven framework of remote sensing and biophysical knowledge: A case study for wheat and maize in the Guanzhong Plain, China - Zhikai Cheng; Xiaobo Gu; Yuanling Zhang; Tongtong Zhao; Shikun Sun; Yadan Du; Huanjie Cai (European Journal of Agronomy, 2026)

Fabrication of acid-resistant nanofiltration membranes with intrinsic positive charges for lithium recovery - Yue Shen; Bingxin Gu; Xinhe Zhang; Yu Guo; Huiting Zhang; Cheng-Gang Jin; Bohao Chen; Yahua Lu; Gangqiang Yu; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Ferric oxide enhances mixed fungal-bacterial microbiome for medium-chain fatty acid production via endogenous electron donors - Shuanglan Cheng; Shujie Bai; Xianbao Xu; Xia Gu; Xu Duan; Haowen Duan; Xiang Li; Gang Xue; Francisco Jesús Fernández-Morales; Jacek Makinia (Chemical Engineering Journal, 2026)

Exploring the mechanism of Cucurbitacin B against myocardial ischemia reperfusion injury based on network pharmacology and experimental validation - Xingdong Cheng; Dengyan Zhu; Haizhou Guo; Tianliang Zheng; Bin Wu; Yinliang Sheng; Feng Li; Guangcheng Sun; Song Zhao; Li Ke; Zhuoyu Gu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

RP13-516M14.1 Regulates Autophagy Through miR-429 via Both a ceRNA Network and Direct Interaction - Zhijian Yang; Anyu Zeng; Baoxi Yu; Chao Xie; Weiwen Zhu; Hailong Liu; Cheng Gu; Ming Fu (Biochemical Genetics, 2026)

Asymmetric Shifts in Precipitation Alter Nitrogen Use Strategies in Global Croplands - Jinglan Cui; Yujing Gao; Luxi Cheng; Xi Zhang; Ouping Deng; Miao Zheng; Zhongrui Xie; Hans J. M. van Grinsven; Lorenzo Rosa; Baojing Gu (Global Change Biology, 2026)
Global warming intensifies regional precipitation imbalances that disrupt cropland nitrogen cycling and threaten food security. Here, we show that global croplands respond asymmetrically to future precipitation change. Under a middle of the road scenario for 2050, 78% of croplands are projected to become wetter, increasing yields by 15% but raising nitrogen losses by 45%. The remaining 22% that become drier would experience a 29% decline in yields and a 25% rise in nitrogen losses. Nitrogen use efficiency declines by 3%–14% worldwide because both wetter and drier conditions reduce plant uptake or accelerate losses. Although altered precipitation increases global crop production by 8%, the accompanying 43% rise in nitrogen losses may compromise long term sustainability. Subtropical and tropical regions between 30° N and 30° S emerge as disruption hotspots. Adaptation measures such as optimized fertilizer management and adjusted planting dates could mitigate up to 462 billion USD per year in damages linked to nitrogen losses. These results highlight the need for adaptive strategies to secure food production and environmental sustainability under asymmetric precipitation change.

Integrating ground-source heat pumps and photovoltaic thermal structures for low-carbon, cost-effective building energy solutions: a comparative investigation - Luyue Han; Fenghua Xia; Zhenxing Cheng; Song Zhou; Shoupu Gu; Rui Zhang; Xiuyan Zhang (Environment, Development and Sustainability, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Assessing algal blooms in Taihu Lake using hourly data: Seasonal characteristics and the relationship with environmental factors - Dian Yang; Xingfa Gu; Liang Gao; Tianhai Cheng; Ka-Veng Yuen; Chan Sun (Marine Pollution Bulletin, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Elucidating the role of overlooked environmentally persistent free radicals and reactive chlorine species on photoaged chlorine-containing microplastics: New insights into formation mechanisms and health risks - Linyang Xie; Jingbo Ling; Kaiyou Huang; Jianyu Lin; Hongjian Li; Zhiyu Zhou; Shixiang Gao; Rong Ji; Cheng Gu; Dongmei Zhou; Xueyuan Gu (Journal of Hazardous Materials, 2026)

Accelerated indirect photo-transformation of chlorophene in the presence of dissolved organic matter in saline waters: Role of both agglomeration and heterogeneous reactive species - Yichen Xu; Qian Chen; Yutong Zhang; Xiuyuan Xu; Xinhao Wang; Yi Wang; Davide Vione; Zhanghao Chen; Cheng Gu (Journal of Hazardous Materials, 2026)

Effect of boiling time on noodle surface tackiness: Roles of gluten network and broth components in steamed-then-boiled noodles - Yijun Fan; Mingyi Shen; Ruifang Wang; Zhengbiao Gu; Yan Hong; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Li Cheng (Journal of Cereal Science, 2026)

Starvation induces a transition from autophagy to apoptosis via the ER-Ca2+-calpain signaling axis in the fat body of Bombyx mori - Jialu Cheng; Sheng Zhang; Haoyi Gu; Xueling Qin; Bing Li (Insect Biochemistry and Molecular Biology, 2026)

Supply chain models dictate pork spoilage rates: Metabolomic profiling reveals the degradation mechanism under ambient exposure - Bin Han; Cheng Li; Su Wang; Dequan Zhang; Minghui Gu; Xiaochun Zheng (Food Research International, 2026)

Designing an enzymatic glycosidic bond rearrangement of corn starch to improve its freeze-thaw stability for tailored application in crystal dumpling wrappers - Haocun Kong; Kunrong Wu; Zhaofeng Li; Zhengbiao Gu; Lining Kang; Xiaofeng Ban; Yan Hong; Li Cheng; Caiming Li (Food Chemistry, 2026)

Emulsion gels based on OSA modified high amylose maize starch: Formation, interfacial properties, and stability - Chengchen Jiang; Danli Jin; Ziqi Chen; Zhengbiao Gu; Li Cheng; Zheming Zhang; Yan Hong (Food Hydrocolloids, 2026)

Inhibitory effect of gentisic acid on biofilm formation of Listeria monocytogenes in vitro and on food-related surfaces - Ailin Wang; Yunqi Gu; Yuanhang Cheng; Meihan Zhang; Xiaodong Xia (Food Microbiology, 2026)

Whales contribute to novel insight on poly- and perfluoroalkyl substances bioaccumulation in the East China sea - Tao Zhang; Tianhui Zhao; Ziyang Wei; Guang Yang; Cheng Gu; Bingyao Chen; Bo Zhang (Environmental Pollution, 2026)

A nanoengineered strategy combining deep oxygenation and immunogenicity regulation to unleash the power of anti-tumor immunity - Gang Cheng; Linlin Tao; Nian Huang; Xiaoxiao Hu; Mengmeng Yang; Fangnan Lv; Nan Yang; Siyuan Meng; Zuhang Xing; Boyu Gu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

hESC-EVs attenuates cellular senescence and promotes osteogenesis in periodontal ligament stem cells via miR-302b-3p - Jue Wang; Jun Wang; Jing Zhou; Jinpeng Xie; Shuaifei Zhao; Ting Zhang; Ying Chen; Yuxiu Ying; Xiaoshuang Xin; Xu Xu; Ting Kou; Lei Xu; et al. (Chemical Engineering Journal, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

“X” site heteroatom substitution induced Fermi-level restructuring and localized polarization in MXenes for optimized microwave absorption - Yudong Cheng; Zhongyan Gu; Yongpeng Wu; Chunhua Sun; Pengxu Chen; Fei Pan; Xiang Li; Wei Lu (Chemical Engineering Journal, 2026)

A New Water Demand Prediction Approach using Adjustable Self-Feedback Gain Elman Neural Networks Coupled with Enhanced Sparrow Search Algorithm - Liying Wang; Qiang Ge; Zhenxing Zhang; Shixiang Gu; Nima Khodadadi; Cheng-I Hsieh; Weiguo Zhao (Water Resources Management, 2026)

Screening of quorum Sensing-Dependent strong promoters in Pseudomonas bijieensis 2P24 for metabolic optimization and Recombinant protein production - Jie Li; Hongguang Ma; Na Tai; Yue Fan; Mengxue Nie; Xuanying Tao; Zhilin Wang; Jinxin Wang; Xiangpeng Deng; Cheng Shen; Xuanxuan Chen; Jin Wang; et al. (World Journal of Microbiology and Biotechnology, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Cyclic response analysis of suction anchors for floating wind turbine in clays under inclined loading - Wenbo Tu; Yaoyu Jia; Zhenhao Shi; Xiaoqiang Gu; Xinglei Cheng (Ocean Engineering, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

Nano-bio interaction determines the early progression of lung cancer by reshaping pulmonary epithelial microenvironment - Yu-Han Zhang; Jun Zhang; Lei Shi; Meng Xiang; Xue Han; Ling Zhu; Jia-Cheng Xie; Yan Chen; Qi Gu; Jing-Yu Li; Zhen Zou; Jian-Yu Wang (Journal of Hazardous Materials, 2026)

Multimedia tungsten contamination and health risk from tungsten mining and refining - Yifan Lin; Hongguang Cheng; Xiang Gu; Chunye Lin (Journal of Hazardous Materials, 2026)

Joint assessment of metal contamination and N2O yield in agricultural sediments (southwestern France): Factors, prediction, and management - Xinda Wu; Cheng Gu; Anne Probst (Journal of Environmental Chemical Engineering, 2026)

From laboratory to field: Temperature rise triggers increased release and toxicity of microcystins in Microcystis aeruginosa - Shihao Wang; Yurong Gu; Weilu Li; Qingju Xue; Xinfeng Cheng; Chen Cheng; Liqiang Xie (Harmful Algae, 2026)

Low-temperature co-gasification of rice husks and waste tires as an alternative fuel in the cement industry: Investigation of synergistic mechanisms and their targeted optimization - Shuchao Cheng; Baosheng Jin; Liye Wang; Songshan Cao; Yi Chen; Xiangchao Su; Qinyang Gu; Yaji Huang (Fuel, 2026)

Regulation mechanisms and effects of thermal processing methods on starch digestibility in cornmeal staples - Shuang Xu; Zhengbiao Gu; Li Cheng; Yan Hong; Lingjin Li (Food Research International, 2026)

Comparative effects of ultra-high pressure, ultra-high temperature, and thermal pasteurization processing on the flavor characteristics and nutritional components of freshly squeezed Hami melon juice - Jinxiao Cheng; Yining Xia; Xinli Geng; Lingling Pang; Di Shen; Limei Li; Yifan Gu; Yanfang Pan (Food Chemistry, 2026)

Disordered sphingolipid metabolism mediates cognitive impairment in juvenile mice on a high-glucose diet - Jian Yin; Chongxuan Shao; Li Cheng; Yan Hong; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Zhengbiao Gu (Food Bioscience, 2026)

Unlocking the potential of konjac (Amorphophallus konjac K. Koch) Starch: A review on extraction, structure, properties, and potential applications - Gangpeng Shi; Yan Hong; Li Cheng; Lingjin Li; Zhengbiao Gu (Food Hydrocolloids, 2026)

Seismic strengthening of rural masonry buildings via external precast RC subframes: Concept, experiment and application - Xu-Yang Cao; De-Cheng Feng; Dongsheng Gu; Xuliang Qian; Gang Wu (Engineering Structures, 2026)

Synergistic photovoltaic cooling and water-resource recovery enabled by a composite evaporation gel - Yuqing Su; Yi Lu; Ruonan Gu; Wei Wu; Xuyu Yu; Shaoan Cheng (Desalination, 2026)

Thermo-oxidative aging mechanism and machine learning-assisted lifetime prediction of CF/PPESK composites - Wenlong Yang; Kaiyuan Fan; Binggang Liu; Yuxiang Zhuang; Hongjian Gu; Xigao Jian; Cheng Liu (Chemical Engineering Journal, 2026)

Influence of structural changes of starch in starchy foods during storage on their edible quality: A review - Huan Xie; Yan Hong; Lingjin Li; Li Cheng; Jing Du; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Zhengbiao Gu (Carbohydrate Polymers, 2026)

Toward sustained and efficient n-caproate production: Insights into magnetite-encapsulated biochar mediated microbial chain elongation - Benteng Wu; Yangjuan Cheng; Jing Gu; Haoran Yuan; Jerry D. Murphy (Bioresource Technology, 2026)

Association between Lipid Accumulation Product and 3-Month Functional Outcome after Ischemic Stroke: the Obesity-Stroke Paradox - Yuan Ren; Ying Zhou; Tian-yu Gu; Yang Cheng; Wei-hua Wu; Xiao-guang Dong; Feng-e Li; Yu-sheng Zhang (Translational Stroke Research, 2026)

Model-Dependent Attenuation of Seizures by Cinnabar - Yuang Gu; Yu Yao; Qiuwen Lou; Xinyan Zhu; Ju Lan; Chenshu Gao; Shuangshuang Wu; Jingjia Liang; Cenglin Xu; Yi Wang; Heming Cheng; Zhong Chen (Neuroscience Bulletin, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Reinforcement learning-based winding capture and obstacle-avoidance path planning for rope-driven manipulator - Ziliang Zhao; Xiaofeng Li; Haiyu Gu; Kangjia Fu; Cheng Wei; Yatao Zhao (Advances in Space Research, 2026)

Analysis of Wave Height and Period in the Yangtze River Delta and Adjacent Waters Based on a 31-Year High-Resolution Wave Hindcast - Wenyun Guo; Jiepeng Gu; Tao Qin; Yu Zhang; Yi Zhou; Xinyi Shen; Cheng Li (Journal of Marine Science and Engineering, 2026)
This study presents a 31-year (1993–2023) wave hindcast using a high-resolution two-domain nested numerical wave model implemented with Simulating Waves Nearshore (SWAN). The spatiotemporal variability and long-term trends of two wave parameters (significant wave height Hs and spectral peak period Tpeak) are systematically analyzed for the Yangtze River Delta (YRD) and its adjacent waters. Validation against in situ buoy measurements confirms that the SWAN model effectively reproduces the regional wave conditions. Results indicate that mean wave conditions are primarily modulated by the Asian monsoon, whereas extreme wave events are predominantly influenced by typhoons. This leads to pronounced differences in spatial patterns and seasonal variability between mean and maximum Hs values. In addition, the regional interannual variations of Hs and Tpeak exhibit different degrees of correlation with the Niño 3.4 index, the Pacific Decadal Oscillation (PDO) index and the Western Pacific Subtropical High Ridge Position (WPSH) Index. Overall, both Hs and Tpeak exhibit positive trends over the study period, and both positive trends shift remarkably between seasons. The positive trends in mean wave conditions are mild during spring and summer but more pronounced in autumn and winter. Statistically significant increases in seasonal mean Hs are identified in parts of the East China Sea (0.35 cm a−1 in autumn) and the southern Yellow Sea (0.27 cm a−1 in winter). Notably, not all trends are positive: the 90th percentiles of both Hs and Tpeak during summer exhibit widespread declining trends, although they are not statistically significant.

Validated semi-supervised early and accurate screening for anterior segment diseases: a 3PM-guided conceptual and technological innovation - Mingyu Xu; Renshu Gu; Zhanyun Lu; Huimin Cheng; Yifan Zhou; Pengjie Chen; Yiming Sun; Jing Cao; Zhichu Chen; Gangyong Jia; Peifang Xu; Juan Ye (EPMA Journal, 2026)
Background/aims Ocular anterior segment diseases are major causes of global visual impairment. Early and accurate detection of anterior segment abnormalities is essential to support predictive diagnostics, targeted prevention, and individualized treatments management. Conventional slit-lamp assessments are often limited by human observation and inter-clinician variability, restricting their ability to achieve rapid and large-scale disease screening. To advance anterior segment care within the predictive, preventive, and personalized medicine (PPPM/3PM) framework, this study aimed to develop a comprehensive and validated semi-supervised object detection (SSOD) system for slit-lamp imaging–based screening of multiple anterior segment diseases. Methods A total of 7230 slit-lamp images from 3302 patients were retrospectively collected at the Second Affiliated Hospital of Zhejiang University between November 2016 and July 2024. The proposed SSOD integrated a Category Control Embed (CCE) module to mitigate class imbalance and an Out-of-distribution Detection Fusion Classifier (ODDFC) to identify previously unseen lesions. Model performance was quantitatively compared with YOLOv8 and ophthalmologists using quantitative metrics (average precision [AP], recall) and clinical assessments of diagnostic accuracy, lesion comprehensiveness, and localization precision. Results The SSOD achieved mAP comparable to YOLOv8 (0.729 vs. 0.725 for single-lesion; 0.538 vs. 0.543 for multi-lesion), but demonstrated substantially higher recall (0.893 vs. 0.656 for single-lesion; 0.679 vs. 0.477 for multi-lesion). In clinical evaluations, SSOD scored 2.430/3 for single-lesion and 1.942/3 for multi-lesion detection, outperforming YOLOv8 and approaching the performance of junior ophthalmologists in multi-lesion cases. Conclusion The SSOD framework offers an efficient and scalable solution for anterior segment disease screening, delivering reliable multi-lesion detection with minimal annotation. It supports early recognition of anterior segment lesions, guides targeted interventions to prevent irreversible vision loss, and facilitates patient-centered, individualized management that advances ophthalmic care from reactive assessment to proactive precision treatment, aligning with the principles of 3PM.

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Dynamic prediction of carbon and nitrogen accumulation in winter wheat grain: Source-sink theory integrated with UAV multispectral imagery - Zehua Fan; Cuiping Liu; Fengyuan Yu; Yongliang Lai; Qiang Wang; Zhiyong Zhang; Juanjuan Zhang; Jinpeng Cheng; Xinming Ma; Xiaohe Gu; Shuping Xiong (Computers and Electronics in Agriculture, 2026)

Role of multivalent iron in enhancing sodium percarbonate oxidation for alleviating membrane distillation fouling caused by shale gas produced water - Haiqing Chang; Yuan Huang; Suhua Gu; Xiaoxiang Cheng; Fangshu Qu (Water Research, 2026)

Ceritinib–ibuprofen synergistic hepatotoxicity: Insights from real-world data and liver organoid models - Shiyi Tan; Yun Yang; Li Ma; Xulei Zuo; Jianhua Rao; Yuepu Pu; Feng Cheng; Zhongze Gu; Juan Zhang (Toxicology, 2026)

Simultaneous and sequential inoculation of lactic acid bacteria to engineer the flavor profile of Chinese spicy cabbage: A machine learning and modeling study - Weiye Cheng; Qingyang Zhang; Xuan Wang; Yun Cen; Zifan Li; Yunjing Gu; Hui Guan; Kanghee Ko; Wenli Liu; Huamin Li (International Journal of Food Microbiology, 2026)

Integration of correlation analysis and untargeted metabolomics reveals microbial interactions driving flavor formation in bacteria-yeast Co-fermented Lithocarpus litseifolius [hance] chun (L. litseifolius) kombucha - Yajie Zhao; Chencheng Gu; Jiaqin Qian; Weirong Yao; He Qian; Yuliang Cheng (Food Bioscience, 2026)

Dietary Lycium barbarum polysaccharide attenuates ammonia-induced oxidative and immunological stress in Macrobrachium rosenbergii via activation of the Nrf2/Keap1 signaling pathway - Hengtong Liu; Yaqi Gu; Chao Liu; Ying Deng; Manjun Xiong; Hongyang Xiong; Dingdong Zhang; Wenbin Liu; Yingchun Xu; Cheng Chi (Fish & Shellfish Immunology, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Substrate-driven enrichment and mining of ligninolytic bacteria for efficient lignin-to-PHA conversion - Tao Xu; Chong Han; He Liu; Zi-Yi Zhao; Fan-Li Zeng; Yu-Cheng Gu; Zhi-Hua Liu; Bing-Zhi Li (Chemical Engineering Journal, 2026)

Soluble TREM1 Contributes to Aging-Related Neurodegeneration via ROBO2/ERK Pathway - Jing-Wen Qi; Xin-Yu He; Yu-Cheng Gu; Zi-Jian Luo; Rui Duan; Ying-Dong Zhang; Yi Xie; Teng Jiang (Molecular Neurobiology, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Regulated enzyme distribution for enhanced wearable sweat glucose monitoring - Yao Chu; Yangyang Chen; Zhen Gu; Xinyi Liu; Tao Cheng; Yichuan Shen; Jian Lv; Yiping Wu; Nan Chen; Haifeng Yang; Wanxin Tang (Analytica Chimica Acta, 2026)

Microscopic investigation on suffusion in granular soil subject to cyclic hydraulic reversal using CFD-DEM - Chuang Zhou; Jian-Gu Qian; Ma-Yao Cheng (European Journal of Environmental and Civil Engineering, 2025)

Magnetite-enhanced chain elongation via endogenous electron donors through a novel fungi-bacteria microbiome - Shuanglan Cheng; Yuchen Hu; Xia Gu; Xianbao Xu; Xu Duan; Xiang Li; Zhihong Liu; Qiwei Jian; Piotr Oleskowicz-Popiel; Pengfei Shen; Aijuan Zhou; Gang Xue; et al. (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Volcanic sulfur dioxide monitored from a constellation of FengYun hyperspectral infrared sounders in dawn-dusk, mid-morning, and afternoon sun-synchronous orbits - Zhao-Cheng Zeng; Lieven Clarisse; Bruno Franco; Cathy Clerbaux; Nicolas Theys; Chengli Qi; Lu Lee; Lin Zhu; Xiuqing Hu; Mingjian Gu; Peng Zhang (Remote Sensing of Environment, 2025)

A new bisbenzoquinone with cytotoxicity from Chaetomium trilaterale - Xin-Xin Liang; Lei Li; Jia-Yi Zhang; Xin-Yue Zhang; Yi-Kun Feng; Chen Gu; Si-Cheng Jin; Xiang-Guo Meng (Phytochemistry Letters, 2025)

Evaluation of quinazolin-4(3H)-one derivatives containing the bioactive acetohydrazide group as fungicidal candidates - Wenfei Zhang; Jiacheng Liu; Sifei Qi; Zihan Li; Yiwen Chen; Yufei Gong; Xiangkun Luo; Shuo Wang; Feng Liu; Yu-Cheng Gu; Xuewen Hua (Pesticide Biochemistry and Physiology, 2025)

Hydrodynamic characterization and efficient prediction of tapered trash-blocking nets for coastal nuclear intakes: Integration of experiment, simulation, and machine learning - Shaojian Guo; Nan Gu; Cheng Zhou; Liwen Liu; Rong Wan; Yucheng Wang; Zhiqiang Liu (Ocean Engineering, 2025)

Seasonal diversity of global flood changes and their drivers - Xihui Gu; Nan Cheng; Yansong Guan; Dongdong Kong (Journal of Hydrology, 2025)

A novel 450 nm blue laser-mediated sinoporphyrin sodium-based photodynamic therapy inactivates Cutibacterium acnes through stress-mediated metabolic alterations - Hengtong Fan; Zejun Ren; Shuqi Chen; Tingting Huang; Guoxiong Liu; Yashou Guo; Yan Zheng; Yifan Cheng; Xing Li; Yibo Mei; Yuhang Chen; Huihui Tuo; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Thermal decomposition characteristics, products, and thermal transformation mechanisms of fluorine-containing organic components in lithium-ion batteries - Hui Liu; Jingkun Han; Yuheng Feng; Chongqing Nong; Yu Liu; LeiLei Cheng; Jing Gu; Haoran Yuan (Journal of Environmental Chemical Engineering, 2025)

Harnessing visible light-activated humic acid and size-exclusion catalysis for efficient pollutant degradation in complex water system - Chenyong Liu; Xiufang Shen; Shaoqun Tao; Yu Liu; Zhonglin Chen; Weichuan Qiao; Cheng Gu; Ming Zhang (Journal of Environmental Chemical Engineering, 2025)

Electrochemical flow-through membrane electrodes for sequential H* reduction and HO• oxidation of nitrobenzene - Zhaoyue Sun; Yingyun Qiao; Yujing Yue; Yunping Tong; Yuanyu Tian; Longgang Chu; Cheng Gu (Journal of Environmental Chemical Engineering, 2025)

Construction of a machine learning-based prediction model for rice varieties—cooking—mastication - Mengjie Ma; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Mingyi Shen; Jinyi Wu; Jia Liu; Yan Hong (Food Research International, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

Micronization of defatted rice bran dietary fiber and its particle size effect on the structure and physicochemical properties of myofibrillar proteins - Shunfan Gu; Jinling Li; Yinghui Zhang; Jian Xia; Cheng Guo; Zhongze Hu; Weiping Jin; Wangyang Shen (Food Chemistry, 2025)

High-performance antifouling electrochemical aptsensor based on a Y-shaped glycopeptide and platinum nanoparticles for detecting aflatoxin B1 in food - Cheng Zhang; Xujun Pu; Xian Chen; Jinzhi Liang; Kun Ge; Yangyue Ding; Lunzhao Yi; Ying Gu; Shuo Wang (Food Chemistry, 2025)

Metabolomic and volatile organic compound characterization in the longissimus dorsi muscle of Duroc × Wujin × Yorkshire pigs - Zhanggui Zeng; Yingli Long; Cheng Meng; Yuhao Gao; Runhui Xu; Yiren Gu; Peng Shang; Shuquan Liu; Xun Zhou; Ling Zhao; Xun Wang; Mingzhou Li; et al. (Food Chemistry, 2025)

Deciphering the core microbiomes and associated genes and metabolites during the Shanxi aged vinegar making process - Rui Ma; Mingxia Cheng; Qiong Zhou; Xiaojie Nan; Min Zhu; Shang Guo; Zhibin Zhang; Fang Gao; Jingang Gu (Food Bioscience, 2025)

Butterfly-inspired ultraviolet vision chip based on ZnO memristor arrays for real-time dynamic plant motion tracking - Yang Liu; Junmeng Guo; Jiao Wang; Yuwei Zhao; Yatao Zhang; Guangxiang Gu; Haoran Ruan; Pengfei Li; Yu Sun; Luyao Zhang; Zuliang Du; Gang Cheng (Chemical Engineering Journal, 2025)

Complexation mechanism of high-amylose corn starch and myristic acid in CaCl2 aqueous solution: The role of Ca2+ coordination structure - Xinxin Lv; Yan Hong; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban (Carbohydrate Polymers, 2025)

Radiocarbon age offsets in loess sediments from the southern Tibetan Plateau: modulated by vegetation productivity and aeolian dynamics - Yan Hu; Weijian Zhou; Peng Cheng; Yuda Chui; Jie Zhou; Ling Yang; Wenli Li; Haiyan Zhao; Huachun Gu; Mengyu Li; Xuefeng Lu (CATENA, 2025)

A non-contact blood pressure measurement method based on face video - Lifeng Yang; Shaojie Gu; Binbin Liu; Junjie Wang; Junwei Cheng; Yuanxi Zhang; Zhengan Xia; Yan Yang (Physical and Engineering Sciences in Medicine, 2025)

Microalgae-induced changes in the rhizosphere microbiome improve saline-alkali tolerance of Perilla frutescens - Yunmei Zhang; Shuiwen Luo; Xuyang Gu; Wenshan Gao; Chenxing He; Ziyi Wang; Menghang Cheng; Yuling Liang; Dandan Cao; Jianfeng Liu (Journal of Applied Phycology, 2025)

Genome-wide identification and expression analysis of PP2C gene families in two Chimonanthus species - Xin-Chen He; Jie-Xin Shao; Wei Zou; Shu-Xiao Zhang; Li Zhu; Meng-Cheng Ji; Cui-Hua Gu; Li-Yuan Yang (Genetica, 2025)

Arbuscular Mycorrhizal Fungi Drive Soil Multifunctionality and Productivity Enhancement in Leymus Chinensis Grasslands Under Phosphate Fertilizer Condition - Xiaoguo Zhou; Yutong Hu; Junhui Cheng; Jiandong Sheng; Gu Feng (Journal of Soil Science and Plant Nutrition, 2025)

Fast Reverberation Suppression Method in Active Sonar Detection Using a Subspace Learning Model - Cheng Wang; Fangyong Wang; Xinyu Gu; Yuqing Mao; Guangping Zhu (Marine Geodesy, 2025)

Synergy of algal particle deposition and bioturbation amplifies the internal phosphorus loading - Fengrui Zhang; Lixian Tan; Wenxuan Han; Lei Zhang; Qiushi Shen; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Water Research, 2025)

Breaking the bitterness barrier: Cutting-Edge strategies combining computer screening, sensory science, and dual-path debittering technologies - Xiao Chen; Yiyue Chen; Kang Chen; Liyan Zhao; Leiqing Pan; Zixuan Gu; Zhi Cheng; Weijie Lan (Trends in Food Science & Technology, 2025)

Microplastics: an overlooked particle organic carbon in river systems - Xuke Liu; Weijian Zhou; Peng Cheng; Fei Zhang; Liangcheng Tan; Yunchong Fu; Yukun Fan; Jianghu Lan; Huachun Gu; Wen Liu; Ting Wang (Science Bulletin, 2025)

Quantification of per- and polyfluoroalkyl substances (PFASs) in aqueous film-forming foam (AFFF)-impacted water: Comparisons between methodologies and laboratories - Chuhui Zhang; Nicholas Gonda; Ashley N. Kimble; Eric Redman; Cynthia M. Grim; Siwei Gu; Anthony Bednar; Karen Dahl; Chenyi Yuan; Yue Zhi; Hefa Cheng; Christopher P. Higgins (Journal of Hazardous Materials, 2025)

Effect of waxy rice kernel structure on hydration behavior during the production of Zongzi - Ziqi Chen; Yi Chen; Zhengbiao Gu; Li Cheng; Zhaogui Chen; Yuhui Peng; Yan Hong (Journal of Cereal Science, 2025)

Corrigendum to “Comparative study on the quality characteristics of filter flours collected from different milling streams in a wheat flour milling system” [J. Cereal Sci. 126 (2025) 104283] - Yueyi Chen; Tiantian Li; Shunfan Gu; Jian Xia; Cheng Guo; Zhongze Hu; Weiping Jin; Jinling Li; Wangyang Shen (Journal of Cereal Science, 2025)

Comparative study on the quality characteristics of filter flours collected from different milling streams in a wheat flour milling system - Yueyi Chen; Tiantian Li; Shunfan Gu; Jian Xia; Cheng Guo; Zhongze Hu; Weiping Jin; Jinling Li; Wangyang Shen (Journal of Cereal Science, 2025)

Untargeted flavoromics and correlation analysis reveal microbial interactions driving flavor in LAB co-fermented Beita juice - Yajie Zhao; Chengjie Tong; Chencheng Gu; Qinwei Xu; Weirong Yao; He Qian; Yuliang Cheng (International Journal of Food Microbiology, 2025)

Study on the effects of high temperature on autophagy and apoptosis in different organs of Bombyx mori based on calcium ion homeostasis - Peilin Peng; Hongbin Zou; Jialu Cheng; Haoyi Gu; Guimin Nong; Xuelin Qin; Bing Li (Insect Biochemistry and Molecular Biology, 2025)

Slow starch digestibility promotes the development of favorable feeding behaviors and metabolic health in mice - Jian Yin; Li Cheng; Yan Hong; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Ling Zhu; Zhengbiao Gu (Food Research International, 2025)

Integrating data assimilation with chlorophyll fluorescence signatures: An innovative framework for real-time monitoring of crop nitrogen dynamics - Zhikai Cheng; Xiaobo Gu; Tongtong Zhao; Wenlong Li; Chunyu Wei; Yang Xu; Shikun Sun; Yadan Du; Huanjie Cai (Field Crops Research, 2025)

Tailored cocrystal architectures enable highly reversible actuation in crystalline polymer networks - Dequan Chi; Chao Wu; Haoyu Gu; Xinchao Sun; Ruoxi Zhao; Dongjie Zhang; Zhimin Xie; Zhongjun Cheng; Yuyan Liu (Chemical Engineering Journal, 2025)

Rotary thermal processing for enhanced surface coatings pyrolysis and char removal in waste aluminum can recycling - Jialiang Yang; Leilei Cheng; Ruizhe Chen; Jing Gu; Yuepeng Cai; Zhen Huang; Haoran Yuan (Chemical Engineering Journal, 2025)

Injectable GelMA microsphere-integrated hyaluronic acid-polyphenol hydrogel system with multifunctional injury microenvironment modulation promotes peripheral nerve regeneration - Bo Ma; Hailin Ma; Baixin Gu; Kangling Xu; Pei Cao; Xiaotong Wu; Tiantian Qi; Rou Wen; Tianze Sun; Junyu Su; Hanwen Cheng; Yujie Wang; et al. (Carbohydrate Polymers, 2025)

Hyaluronic acid and polyvinyl alcohol-based radioresponsive hydrogel for combined radioimmunotherapy of breast cancer bone metastasis - Liubing Li; Zenghui Gu; Yanxian Wu; Subin Lin; Xiaju Cheng; Leshuai W. Zhang; Jianzhong Qin; Qirong Dong; Yong Wang; Yangyun Wang (Carbohydrate Polymers, 2025)

Enzymatically modified starch: Structure, digestibility, energy supply, and applications - Yali Huang; Lingjin Li; Yan Hong; Li Cheng; Zhengbiao Gu (Carbohydrate Polymers, 2025)

New sesquiterpenoids from the flowers of pentanema britannicum (L.) D.Gut.Larr - Zhen Pei; Yan-Nan Ji; Xin-Yue Zhang; Yu-Qing Xie; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2025)

Quantifying tree-level peach flowering dynamics using UAV imagery and an optimized instance segmentation model - Qing Gu; Jiayu Cheng; Minghao Zhang; Xiongwei Li; Robert Jackson; Lei Ju; Weidong Lou; Miaojin Chen; Ji Zhou; Xiaobin Zhang (Computers and Electronics in Agriculture, 2025)

C3/C4 vegetation dynamics and hydroclimate variations in South China over the last two glacial-interglacial cycles - Xiaoyi Dong; Huayu Lu; Chenghong Liang; Hongyan Zhang; Michael Meadows; Cheng Zhao; Shuangwen Yi; Yao Wang; Yao Gu; Fan Yang; Fuzhi Lu (Quaternary Science Reviews, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Thiols regulate photo-transformed fates of anthracene at surfaces of minerals: Potential roles of sulfhydryl in oxidative coupling of polycyclic aromatic hydrocarbons - Zhaoyue Sun; Xinghao Wang; Longgang Chu; Yunping Tong; Cun Liu; Guodong Fang; Hong Chen; Cheng Gu; Juan Gao (Journal of Hazardous Materials, 2025)

Spatiotemporal variation and drivers of ecosystem service value: A case study in Ziwuling area, Loess plateau - Fengyou Gu; Guoce Xu; Bin Wang; Yuting Cheng; Mingzhu Xu; Jing Li (Journal of Environmental Management, 2025)

Antifouling electrochemical aptasensor based on a polyzwitterion copolymer for analyzing aflatoxin B1 in food - Meirong Niu; Xujun Pu; Xian Chen; Dabing Ren; Cheng Zhang; Lunzhao Yi; Yukun Yang; Ying Gu; Shuo Wang (Food Chemistry, 2025)

Improving dynamical downscaling simulations of western North Pacific tropical cyclones using bias-corrected CMIP6 data - Ying Han; Zhongfeng Xu; Meng-Zhuo Zhang; Chi-Yung Tam; Vincent S. Cheng; Hon-man Wong; Xiaofeng He; Yi Wang; Si-nan Gu (Climate Dynamics, 2025)

Occurrence and provenance of ion-adsorbed rare earth elements mineralization in alumina-rich rocks of the Permian Heshan formation, Western Guangxi, China - Chunfang Dong; Zhixuan Han; Xiaocheng Wei; Junhong Liu; Haonan Zhao; Zhiyan Gu; Bimin Zhang; Cheng Xu (Applied Geochemistry, 2025)

Seasonal Variations and Potential Sources of Black Carbon at a Mountain Site in the Central Yunnan Plateau, China - Yanli Wang; Yan Cheng; Song Liu; Feng Xiang; Limei Bi; Qiaoli Wu; Xuan Tian; Shiting Chen; Zechen Gu; Feng Wu (Aerosol Science and Engineering, 2025)

A method for generating obstacle sample datasets in coastal remote sensing scenes based on out-of-distribution detection - Chen Ji; Taotao Cheng; Sicong Li; Jiawei Gu; Liang Cheng (Marine Geodesy, 2025)

Galvanic bioleaching of chalcopyrite with additional power recovery - Luyuan Zhang; Yisheng Zhang; Chen Cheng; Guohua Gu; Hongbo Zhao (Minerals Engineering, 2025)

Galvanic effects between mackinawite and pyrogenic carbon: Enhancing radical-mediated ciprofloxacin transformation - Danning Lu; Longgang Chu; Haoran Yu; Zhaoyue Sun; Xiru Chen; Ruobing Wang; Xing Liu; Zhanghao Chen; Juan Gao; Cheng Gu (Journal of Hazardous Materials, 2025)

Control strategy to improve sustainable flux for a high-solid AnMBR in co-digesting food waste and sewage sludge - Hui Cheng; Kaiyi Gu; Yemei Li; Guangze Guo; Chang-Tang Chang; Wenshan Guo; Yu-You Li (Journal of Environmental Management, 2025)

Synergistic and antagonistic effects of ZnO/Zn2+ species and Brønsted/Lewis acid sites variations on the catalytic conversion of polyethylene to aromatics - Ruizhe Chen; Leilei Cheng; Wenbo Zhang; Jing Gu; Haoran Yuan; Yong Chen (Journal of Environmental Management, 2025)

TAM-Net: A deep network combining tabular diffusion algorithm, attention mechanism, and multi-task learning for monitoring crop water status from UAV multi-source images - Zhikai Cheng; Xiaobo Gu; Zhengtao Zhang; Yang Xu; Tongtong Zhao; Yupeng Li; Shikun Sun; Yadan Du; Huanjie Cai (European Journal of Agronomy, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Mechanically tuned dual-network scaffolds orchestrate neuro-angio-osteo coupling for enhanced bone regeneration” [chemical engineering journal 516 (2025) 1–22/CEJ_164176] - Mengmeng Yang; Yang Liu; Wenjie Li; Pengyin Li; Shaoqing Chen; Chun Liu; Bang An; Qiangsheng Dong; Cheng Wang; Feng Xue; Chenglin Chu; Jing Bai; et al. (Chemical Engineering Journal, 2025)

MXene-embedded nanocomposite hydrogels with triple-gradient architecture - Guang-Chang Xu; Yihan Nie; Chuang-wei Gu; Hong-Qing Liang; Hao-Cheng Yang; Haifei Zhan; Chao Zhang; Chaofeng Lü; Yunmin Chen; Zhi-Kang Xu (Chemical Engineering Journal, 2025)

Multilayer self-sensing hydrogel soft robot prepared via stereolithography for on-demand drug delivery - Xuewei Shi; Lidan Zhang; Lijin Cheng; Chenxing Xiang; Alamusi Lee; Huiming Ning; Kaiyan Huang; Haowen Liu; Hansheng Liao; Kexu An; Bo Yang; Jie Wen; et al. (Chemical Engineering Journal, 2025)

The regulatory effects of butyrylated starch on gut microbiota and metabolites during in vitro fermentation: advantages over exogenous butyrate and resistant starch - Yi Zhang; Lingjin Li; Yahui Gao; Li Cheng; Yan Hong; Zhengbiao Gu (Carbohydrate Polymers, 2025)

Biological soil crusts enhance nutrient availability and potential soil functions in waste dump soils - Yueheng Lu; Yazhou Gu; Qi Cheng; Yixin Zhao; Xinwei Hao; Pengfei Zhang; Shengzhi Guo; Yao Wang; Xingyu Liu; Xihui Shen (Plant and Soil, 2025)

Applying side-stream gas recirculation to promote anaerobic digestion of food waste under ammonia stress: Overlooked impact of gaseous atmospheres on microorganisms - Linyan He; Jinze Li; Lizhan Tang; Yifei Wang; Xueyu Zhao; Keke Ding; Linji Xu; Li Gu; Shang Cheng; Yi yuan Wei (Water Research, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Uncertainty analysis of wave loads for multi-connected domain large floating bodies near islands and reefs - Xi-zhao Wang; Xue-kang Gu; Jun Ding; Qi-bin Wang; Zhi-wen Cai; Xiao-ming Cheng; C. Guedes Soares (Ocean Engineering, 2025)

Machine learning analysis: Environmental and operational factors' influence on decay rate and organic sludge yield in full-scale wastewater treatment plants - Jinze Li; Lizhan Tang; Junyan Liu; Li-ping He; Li Gu; Shang Cheng; Yiyuan Wei; Binquan Jiao; Yongdong Chen (Journal of Water Process Engineering, 2025)

Formation of highly toxic p-benzoquinones byproducts during ozonation of cresols - Weixu Tang; Jianjian Wei; Shuting Wang; Qiang Cheng; Aroob Abid; Jia Gu; Min Zheng; Dehua Ma (Journal of Environmental Sciences, 2025)

Understanding the influence of the digestive characteristics of glycemic carbohydrates on eating behavior: Nutrient-sensing perspectives - Jian Yin; Li Cheng; Yan Hong; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Ling Zhu; Zhengbiao Gu (Food Research International, 2025)

Antimicrobial properties and preservation potential of Allium sativum L-derived extracellular vesicle-like particles for food applications - Chenqi Zhu; Xiaoxiao Ke; Yi Gu; Chunmeng Wang; Shangyang Lin; Yijie Qian; Jiale Cheng; Yan Chen; Liu Xu; Zhipeng Chen (Food Chemistry, 2025)

Millisecond dwell time enables closed-loop recycling of polypropylene waste plastics: effects of pyrolysis parameters on low-carbon olefin and carbon nanosphere formation - Wenbo Zhang; Leilei Cheng; Ruizhe Chen; Jing Gu; Jirui Zheng; Haoran Yuan; Yong Chen (Chemical Engineering Journal, 2025)

Enhanced phase-transfer kinetics achieved by atomic iron catalysts on hard carbon toward low-temperature sodium-ion batteries - Xinyi Qian; Ziling Wu; Jianan Gu; Yanli Wang; Xiaomin Cheng; Jing Zhang; Hongzhen Lin; Jian Wang; Liang Zhan; Yongzheng Zhang (Chemical Engineering Journal, 2025)

Bone marrow microenvironment-targeted yolk-shell nanoparticle enhances acute myeloid leukemia chemotherapy by preventing endothelial cell/ECM-mediated adhesion - Shiyi Hong; Pei Peng; Yutian Huang; Siying Cai; Cao Yao; Tongtong Huang; Yulu Ying; Wei Li; Yang Xiong; Mancang Gu; Guilin Cheng; Chaofeng Mu (Chemical Engineering Journal, 2025)

A state of art review on carbon, nitrogen, and phosphorus cycling and efficient utilization in paddy fields - Zeyu Zhang; Dongxing Xie; Wenhao Teng; Feng Gu; Rui Zhang; Kui Cheng; Zhuqing Liu; Ying Zhao; Fan Yang (Plant and Soil, 2025)

Trash or treasure? Unlocking dark matter of enantiomeric natural products in innovative drugs discovery for potent angiogenesis inhibitors - Yan-Wei Wu; Xiao-Feng Mou; Zhong-Yuan Chen; Xiao-Jia Xue; Wen-Hui Wang; Jin-Zhou Guo; Bo-Qi Zhang; Ting-Ting Xue; Qun Zhang; Mei-Yan Wei; Yu-Cheng Gu; Gulab Said; et al. (Marine Life Science & Technology, 2025)
The occurrence and development of tumors rely on the nutritional supply from blood vessels, which also serve as the main pathway for tumor metastasis. Inhibiting angiogenesis is one of the main strategies for cancer treatments. Chiral drugs, encouraged and inspired by chiral natural products, make up a major portion of marketed drugs. However, as an important source for synthetic chemistry and drug discovery, the counterpart of chiral natural products, the enantiomers, has received little attention. Here, we constructed a compound library containing 100 racemates ( ±)- 1 – 100 and 4 pairs of enantiomers ( 33 , 48 , 59 , 68 ) of 3,4-dioxygenated-4-aryl-quinolin-2(1 H )-one alkaloids. Through extensive activity screening, we found that the compounds with 3 R , 4 R configuration, opposite to the natural products, exhibited potent angiogenesis inhibitory activity in zebrafish, while the 3 S , 4 S -configured natural derivatives have no effects. More importantly, compound ( +)- 48 , named as (3 R , 4 R )-CHNQD-00728, significantly inhibited hepatic tumor growth in doxycin hydrochloride-induced liver-specific enlargement zebrafish. Examining the phenomenon and unlocking dark matter of enantiomeric natural products in innovative drugs discovery can provide a new perspective on organic synthesis and medicinal chemistry, thus enabling a broader exploration.

The impact of actively injecting bubbles on propeller performance - Wang Zhi-Bo; Gu Jin-Jing; Qian Hao-Cheng (Ocean Engineering, 2025)

Optimal location of free-floating bike-sharing dispatching hubs: A multi-scale perspective - Wendong Chen; Yu Gu; Xuewu Chen; Long Cheng; Jonas De Vos (Journal of Transport Geography, 2025)

Environmental concentrations of TCEP and TDCIPP induce dysbiosis of gut microbiotal and metabolism in the honeybee (Apis mellifera L.) - Tao Cang; Weijie Gu; Yu-Cheng Zhu; Mingcheng Guo; Lu Lv; Changxing Wu; Yuanxiang Jin; Yanhua Wang (Journal of Hazardous Materials, 2025)

Study on the influence mechanism of raw potato flour on the stability of ketchup - Boqing Fu; Jiahui Fang; Zhengbiao Gu; Yan Hong; Li Cheng; Xu Wang (Food Chemistry, 2025)

Mechanically tuned dual-network scaffolds orchestrate neuro-angio-osteo coupling for enhanced bone regeneration - Mengmeng Yang; Yang Liu; Wenjie Li; Pengyin Li; Shaoqing Chen; Chun Liu; Bang An; Qiangsheng Dong; Cheng Wang; Feng Xue; Chenglin Chu; Jing Bai; et al. (Chemical Engineering Journal, 2025)

Monitoring of aerosol optical-microphysical properties from DPC/GF-5(02): A case study of dust event in north China plain - Yujia Cao; Cheng Chen; Haixiao Yu; Xiaobing Sun; Xiao Liu; Haoran Gu; Yisong Xie; Jin Hong; Zhengqiang Li (Atmospheric Environment, 2025)

Clinical biomarkers of perioperative neurocognitive disorder: initiation and recommendation - Jianhui Liu; Cheng Li; Junyan Yao; Lei Zhang; Xuan Zhao; Xin Lv; Zhiqiang Liu; Changhong Miao; Yingwei Wang; Hong Jiang; Weifeng Yu; Tianlong Wang; et al. (Science China Life Sciences, 2025)

Correction to: Impacts of landscape patterns on habitat quality in coal resource‑exhausted cities: Spatial–temporal dynamics and non‑stationary scale effects - Zixuan Li; Ziqi Xu; Yedong Chen; Sihao Gu; Cheng Li (Environmental Monitoring and Assessment, 2025)

Electrocatalytic membrane-driven ozonation to reconstruct the extracellular polymeric substance for enhanced sludge dewatering - Yantao Song; Wei Zhang; Zhenao Gu; Yu Cheng; Haihua Bao; Jiaqi Wang; Ning Wang; Yuting Liu; Zongqiang Zhu; Chengzhi Hu (Journal of Water Process Engineering, 2025)

Unexpected Sr enrichment in karst lacustrine sediments associated with warming and rapid socio-economic development - Xiang Gu; Peng Xing; Cheng Zhao; Xiaotong Han; Di Xu; Qinglong L. Wu; Fengchang Wu (Journal of Cleaner Production, 2025)

Resource utilization of the waste lithium slag in oil-well cement under high temperature: Mechanical property, hydration behavior and environmental effect - Zhao Feng; Zeng Xueling; Long Dan; Gu Anlin; Mei Kaiyuan; Zhang Chunmei; Cheng Xiaowei (Journal of Environmental Chemical Engineering, 2025)

The mechanism of high-concentration florfenicol exposure inducing apoptosis in the midgut of Bombyx mori (Lepidoptera: Bombycidae) - Chao Tian; Jialu Cheng; Haoyi Gu; Hongbin Zou; Peilin Peng; Bing Li (Journal of Asia-Pacific Entomology, 2025)

Unraveling the genomic and metabolic mechanisms of pyrene and phenanthrene degradation by Mycolicibacterium sp. SCSIO 43805: A high-Efficiency bacterium isolated from seagrass sediment - Manzoor Ahmad; Tongyin Liang; Yuhang Zhang; Youshao Wang; Jidong Gu; Hao Cheng; Khaled Masmoudi; Weiguo Zhou; Qingsong Yang; Xiaofang Huang; Junde Dong; Juan Ling (International Biodeterioration & Biodegradation, 2025)

Effect of amorphous degree on the structure of octenyl succinate anhydride starch and emulsion stability - Zheming Zhang; Lingjin Li; Baoxin Gu; Zhengbiao Gu; Li Cheng; Yan Hong (Food Research International, 2025)

Chalcomoracin induces autophagy-mediated apoptosis in pancreatic cancer by suppressing the mTOR pathway - Xueli Hu; Zhipan Wu; Lin Cheng; Yuhang Shen; Luping Wang; Eman Shawky; Kaisa Sulaiman; Wei Zhu; Hua Gu; Jingkui Tian (Food Bioscience, 2025)

Antibiofilm efficacies and mechanism of perillaldehyde against Shewanella putrefaciens - Wenxiu Zhu; Yuanhang Cheng; Yankun Zhang; Mingxin Li; Yue Teng; Yunqi Gu; Haisong Wang; Xiaodong Xia (Food Microbiology, 2025)

Soil emissions of HONO and other nitrogen-containing gases: Insights into microbial pathways and moisture effects - Peng Cheng; Baobin Han; Zhilin Tian; Zhen Liu; Wenda Yang; Jianwei Gu; Xiaofang Yu; Hongli Wang; Min Zhou (Atmospheric Pollution Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Study on Acoustic Emission-Resistivity Response of Hydraulic Fracturing in Rock-Like Samples - Jisheng Sui; Lianchong Li; Wenqiang Mu; Jian Lu; Liming Liu; Cheng Gu (Rock Mechanics and Rock Engineering, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

Migrasome-related ITGA5 for predicting prognosis, immune infiltration and drug sensitivity of hepatocellular carcinoma - Wanjin Chen; Kailin Liu; Zhiling Wang; Hui Zhang; Ming Tan; Yuting Liu; Tingting Gao; Xiameng Su; Leirong Gu; Xinyan Chen; Shengtao Cheng (Apoptosis, 2025)

KDELR3 is transcriptionally activated by FOXM1 and accelerates lung adenocarcinoma growth and metastasis via inhibiting endoplasmic reticulum stress-induced cell apoptosis - Cheng Wang; Zhaoxuan Wang; Shiqing Wang; Lin Jing; Chundong Gu (Human Cell, 2025)

Highly efficient removal of per- and polyfluoroalkyl substances by extrusion-regenerated aminated polyurethane sponges - Xinhao Wang; Hanyang Chen; Wenran Wang; Xiufang Shen; Jiabao Wang; Sen Chen; Xueru Yu; Chew Tin Lee; Zhanghao Chen; Cheng Gu (Water Research, 2025)

A novel mean-value-based approach for correcting radiocarbon age anomalies in terrestrial gastropods: Insights from the Tibetan Plateau - Yan Hu; Weijian Zhou; Peng Cheng; Jibao Dong; Yuda Chui; Jie Zhou; Wenli Li; Haiyan Zhao; Mengyu Zang; Minwen Lan; Huachun Gu; Xuefeng Lu (Quaternary Science Reviews, 2025)

Effects of boiling time on physicochemical properties of refrigerated rice: Analysis of rice structure and broth gel composition in a boiled-then-steamed process - Yipin Wu; Li Cheng; Yan Hong; Ruixuan Li; Yi Wang; Yue Wang; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Xue Bian; Shufen Li; Zhengbiao Gu (Food Research International, 2025)

Efficient elimination of sulfamethoxazole by UV/peroxymonosulfate/sulfite process: Activation of peroxymonosulfate by sulfite via nucleophilic addition - Tongke Wang; Chen Sun; Yang Cheng; Zongli Huo; Jia Gu; Jun Ma (Chemical Engineering Journal, 2025)

Development of disease diagnosis technology based on coattention cross-fusion of multiomics data - Mingtao Wu; Chen Chen; Xuguang Zhou; Hao Liu; Yujia Ren; Jin Gu; Xiaoyi Lv; Cheng Chen (Analytica Chimica Acta, 2025)

Decomposition of Leymus chinensis root residues in restored grasslands increased soil faunal abundance - Zhiwei Gu; Cheng Wang; Luxin Li; Long Yan; Tianyue Yang; Hongyu Zhao; Mengqi Jiang; Xiaoqiang Li; Weihua Dong (Plant and Soil, 2025)

Formononetin-Loaded PLGA Large Porous Microparticles via Intratracheal Instillation for Bleomycin-Induced Pulmonary Fibrosis Treatment - Hongting Liu; Yao Sun; Shihao Cai; Conglu Zhao; Xiang xu; Aiguo Xu; Honggang Zhou; Cheng Yang; Xiaoting Gu; Xiaoyu Ai (AAPS PharmSciTech, 2025)

Sesquiterpene lactones from Carpesium abrotanoides L. fruits: characterization and bioactivity profiling - Peng-Bo Tang; Xin-Yu Zhang; Chao Zhang; Jiayi Zhang; Shuohong Liu; Francoise Sauriol; Yu-Cheng Gu; Yu-Fang Wang; Chang-Hong Huo (Natural Product Research, 2025)

Drivers of livestock manure nitrogen recycling on county scale in China - Binhui Chen; Baojing Gu; Xiuming Zhang; Luxi Cheng; Chen Wang; Hongmin Dong; Gerard H. Ros; Wim de Vries; Mengru Wang (Journal of Environmental Management, 2025)

Development of in vitro oral processing model for different rice: Effects of saliva volume and chewing time on physicochemical properties of rice boluses - Mengjie Ma; Lingjin Li; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Yan Hong (Food Chemistry, 2025)

Preparation, characterization, and solubility enhancement of octenyl succinate anhydride debranched starch/1-Octacosanol nanocomplex - Meiru Ji; Baoxin Gu; Junqing Han; Lingjin Li; Yahui Gao; Li Cheng; Zhengbiao Gu; Yan Hong (Food Bioscience, 2025)

Surface catalytic degradation of ciprofloxacin by ferrihydrite sulfidation under ambient conditions - Xiru Chen; Lihua Bai; Hongjian Li; Xinhao Wang; Chao Wang; Yanfen Fang; Cheng Gu (Environmental Pollution, 2025)

One-pot synthesis of hierarchical assembly of NiMoO4/MoS2/Ni3S2 on nickel foam for highly efficient and durable electrocatalytic hydrogen evolution reaction in a wide pH range - Senkai Han; Huiqin Yao; Jiayi Zhan; Chaonan Wang; Siqi Zhang; Qingyang Gu; Cheng Li; Shenghan Zhang; Hongliang Dong; Shulan Ma (Chemical Engineering Journal, 2025)

Dextran from human feces-derived Weissella cibaria facilitates intestinal mucosal barrier function by modulating gut bacteria and propionate levels - Huan Zhao; Sakandar Abbas; Jing Ren; Haibin Huang; Ying Song; Xiaoning Su; Qiuyang Wu; Yane Ma; Hao Tang; Yi-Zhou Gao; Yuanzhe Li; Xiaoming Gu; et al. (Carbohydrate Polymers, 2025)

Effect of anthocyanins on the in vitro fermentation of high-amylose starch - Yi Zhang; Zhiqiang Xu; Zhengbiao Gu; Li Cheng; Yan Hong; Lingjin Li (Carbohydrate Polymers, 2025)

Dek570-1, a PPR-DYW protein, is required for maize seed and plant development via modulation of C-to-U RNA editing in mitochondria and chloroplasts - Wenjie Li; Mengsha Zhao; Baiyu Liu; Yecan Liu; Jiaying Deng; Yu Gu; Min Liu; Wen Cheng; Zhaohua Ding; Kunpeng Li (Planta, 2025)

Stress-mediated Activation of Ferroptosis, Pyroptosis, and Apoptosis Following Mild Traumatic Brain Injury Exacerbates Neurological Dysfunctions - Lexin Zheng; Qiuyu Pang; Ruoyu Huang; Heng Xu; Hanmu Guo; Cheng Gao; Xueshi Chen; Ying Wang; Qun Cao; Yuan Gao; Zhiya Gu; Zufeng Wang; et al. (Molecular Neurobiology, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Treatment of Bleomycin-induced Pulmonary Fibrosis by Intratracheal Instillation Administration of Ellagic Acid-Loaded Chitosan Nanoparticles - Zhilin Luo; Yao Sun; Shihao Cai; Hongting Liu; Conglu Zhao; Xiang Xu; Aiguo Xu; Honggang Zhou; Cheng Yang; Xiaoting Gu; Xiaoyu Ai (AAPS PharmSciTech, 2025)

STRAW-YOLO: A detection method for strawberry fruits targets and key points - Zenghong Ma; Naishen Dong; Junyu Gu; Hongchao Cheng; Zhichao Meng; Xiaoqiang Du (Computers and Electronics in Agriculture, 2025)

Food-driven transformation of nitrogen fluxes with urbanization in China - Ouping Deng; Jiale Wei; Jinglan Cui; Shuai Huang; Luxi Cheng; Rong Huang; Baojing Gu (Resources, Conservation and Recycling, 2025)

Comparative analysis of chromatin accessibility in porcine oocytes from follicles of different sizes - Yazhuo Cheng; Jingyu Li; Jiyong Shang; Xilong Jia; Yeling Bi; Jiaxu Gu; Nan Jiang; Yanjun Huan; Youwei Li; Mingju Sun (Research in Veterinary Science, 2025)

Effect of scour-hole dimensions on the failure mechanism of suction caisson for offshore wind turbine in clay - Wenbo Tu; Daolong Shu; Xiaoqiang Gu; Xinglei Cheng; Yufan He; Shifang Ren (Ocean Engineering, 2025)

Corrigendum to “Mechanochemical destruction of perfluorooctane sulfonate (PFOS) using boron carbide (B4C)” [ J Hazard Mater 486 (2025) 137044] - Lijie Duan; Mengbin Gu; Minghao Wang; Liquan Liu; Xue Cheng; Xueqi Fan; Jun Huang (Journal of Hazardous Materials, 2025)

Mechanochemical destruction of perfluorooctane sulfonate (PFOS) using boron carbide (B4C) - Lijie Duan; Mengbin Gu; Minghao Wang; Liquan Liu; Xue Cheng; Xueqi Fan; Jun Huang (Journal of Hazardous Materials, 2025)

Development of 3D printed zanthoxylum oil waxy rice cake - Zepeng Gu; Junlin Li; Qiyun Zhang; Hangyan Dan; Wenjuan Wu; Cheng Li; Zhengfeng Fang; Fahad Al-Asmari; Manal Y. Sameeh; Yuntao Liu; Zhen Zeng (Journal of Food Engineering, 2025)

Study on rock-breaking mechanism of impact trenching in underground diaphragm wall with consideration of slurry effects - Ri-cheng Miao; Zi-han Gu; Cao Wang; Wei Cui (Computers and Geotechnics, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Enhancing thermal conductivity, electromagnetic interference shielding, and joule heating in polyether ether ketone composites using three-dimensional scaly carbon fibre structures and structural optimisation - Yifan Wang; Fengyu Wen; Yashu He; Lin Cheng; Haoyuan Tan; Jierun Ma; Pengbo Lian; Yuxuan Gu; Rui Chen; Jianxin Mu (Chemical Engineering Journal, 2025)

The effect of carbohydrates with different levels of digestibility on energy metabolism in vivo under hypobaric hypoxic conditions - Yali Huang; Lingjin Li; Yan Hong; Li Cheng; Zhengbiao Gu (Carbohydrate Polymers, 2025)

Changes in water conservation and a new estimation for its future potential - Mingzhu Xu; Guoce Xu; Shibo Liu; Jing Li; Zhanbin Li; Yuting Cheng; Jie Zhuang; Yutong Dang; Bin Wang; Fengyou Gu (CATENA, 2025)

CECA: An intelligent large-language-model-enabled method for accounting embodied carbon in buildings - Xierong Gu; Cheng Chen; Yuan Fang; Ron Mahabir; Lei Fan (Building and Environment, 2025)

Conditional Tnfaip6-Knockout in Inner Ear Hair Cells Does not Alter Auditory Function - Yue Qiu; Song Gao; Xiaoqiong Ding; Jie Lu; Xinya Ji; Wenli Hao; Siqi Cheng; Haolinag Du; Yajun Gu; Chenjie Yu; Cheng Cheng; Xia Gao (Neuroscience Bulletin, 2025)

Impacts of landscape patterns on habitat quality in coal resource-exhausted cities: Spatial–temporal dynamics and non-stationary scale effects - Zixuan Li; Ziqi Xu; Yedong Chen; Sihao Gu; Cheng Li (Environmental Monitoring and Assessment, 2025)
Coal resource–based cities were once pillars of significant economic and social development, but after resource exhaustion, these cities are at a critical crossroads and need to transition towards sustainable development and ecological urban renewal. The unique landscape patterns of these cities are associated with extensive coal mining, and their dynamic changes are intrinsically linked to habitat quality. However, this relationship has not been fully explored in existing research. Additionally, the spatial–temporal dynamics and non-stationary scale effects of landscape patterns on habitat quality are often overlooked. This study selects Jiawang, a typical coal resource–exhausted city in eastern China, as a case study. We focus on the ecological transition period from 2000 to 2020. Based on land cover data, the study quantitatively describes the spatiotemporal evolution of landscape patterns and habitat quality. A novel multiscale geographically and temporally weighted regression (MGTWR) model is used to analyze and quantify the complex effects of landscape patterns on habitat quality at different spatiotemporal scales. The study further elucidates the dynamic interaction between landscape patterns and habitat quality, emphasizing key non-stationary scale effects. The findings provide insights for strategic ecosystem management and spatial planning, offering a blueprint for the sustainable transformation of coal resource-exhausted cities.

Wheat Fusarium head blight severity grading using generative adversarial networks and semi-supervised segmentation - Guoqing Feng; Ying Gu; Cheng Wang; Dongyan Zhang; Rui Xu; Zhanwang Zhu; Bin Luo (Computers and Electronics in Agriculture, 2025)

MSCVI: An improved algorithm for mitigating LiDAR noise and occlusion effects in field wheat tiller number calculation - Tai Guo; Yongqing Wang; Yangyang Gu; Yuan Fang; Hengbiao Zheng; Xiaohu Zhang; Dong Zhou; Chongya Jiang; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao (Computers and Electronics in Agriculture, 2025)

Dry solidification of chloride salts and heavy metals in waste incineration fly ash by mayenite - Xin Li; Dongdong Ge; Nanwen Zhu; Yukai Zong; Shi Cheng; Pin Zhou; Min Jiang; Yun Gu; Shouqiang Huang (Waste Management, 2025)

Potentially harmful effects of micro-/nanoplastics on humans as well as protective actions of dietary natural products - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Dan-Dan Zhou; Si-Yu Huang; Si-Xia Wu; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan (Trends in Food Science & Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Multi-habitat utilization and diverse life history of the endangered Sea Carp (Cyprinus acutidorsalis) in the Wanquan Estuary, Hainan island, China: Evidence from otolith microchemistry - Yisi Luo; Zubing Yao; Lichuan Hong; Zheng Li; Xianning Wang; Xingwei Cai; Tao Jiang; Yuan Gu; Fangyuan Li; Yang Dong; Fei Cheng; Jian Yang; et al. (Marine Environmental Research, 2025)

The construction of coupling degradation system low temperature plasma and microbiological denitrification: Interfacial reaction process and synergistic mechanism - Zhonglin Chen; Weizhen Shao; Ming Zhang; Weichuan Qiao; Cheng Gu (Journal of Environmental Management, 2025)

Advances in hydrogen as a zero-carbon fuel for rotary engines: A review - Jian Lei; Junjie Niu; Guohong Tian; Gu Xin; Xiyu Yang; Cheng Shi (Fuel, 2025)

Microwaving plus enzymatic pretreatment of safflower seeds increases the phenolic content and oxidative stability of extracted oil - Zhi Qin; Yun-Long Chang; Zi-Cheng Yang; Wei Fan; Zi-Meng Chen; Ling-Biao Gu; Zhao Qin; Hua-Min Liu; Xin-Liang Zhu; Yu-Xiang Ma (Food Chemistry, 2025)

Mechanism of sodium alginate synergistically improving foaming properties of pea protein isolate: Air/water interface microstructure and rheological properties - Yanan Guo; Shuo Zhang; Yue Gu; Tianfu Cheng; Fuwei Sun; Yichang Wang; Daoying Wang; Zhongjiang Wang; Zengwang Guo (Food Hydrocolloids, 2025)

The mitigating role of lysophospholipids in hepatic lipid metabolism and intestinal immunity in juvenile black seabream (Acanthopagrus schlegelii) fed a high-fat diet - Jiayun Zhu; Yixin Gu; Yuedong Shen; Wenli Zhao; Yangguang Bao; Hao Cheng; Xinyan Zhi; Xinyu Hu; Óscar Monroig; Tingting Zhu; Peng Sun; Qicun Zhou; et al. (Aquaculture, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Understanding the influence of energy and chemical use on water treatment plants carbon emissions accounting - Mohamed Yateh; Cheng Li; Fengting Li; Chunping Gu; Shunjun Ma; Binbin Lu; Yulin Tang (Journal of Water Process Engineering, 2025)

High-efficient nanoemulsions separation by surface manipulation of sands - Yanzheng Ji; Zhikang Cheng; Yifan Zhuang; Chenxia Xie; Chunhui Liu; Wancheng Gu; Yage Xia; Weilin Deng; Wei Wang; Qiang Zhang; Xinquan Yu; Youfa Zhang (Journal of Hazardous Materials, 2025)

Metagenomics and metatranscriptomics insights into microbial enhancement of H2S removal and CO2 assimilation - Junjie Wang; Zhuowei Cheng; Yunfei Su; Jiade Wang; Dongzhi Chen; Jianmeng Chen; Xiaoming Wu; Aobo Chen; Zhenyu Gu (Journal of Environmental Management, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Correlation analysis of starch molecular structure and film properties via rearrangements of glycosidic linkages by 1,4-α-glucan branching enzyme - Yilin Dong; Zhaofeng Li; Haocun Kong; Xiaofeng Ban; Zhengbiao Gu; Hao Zhang; Yan Hong; Li Cheng; Caiming Li (Carbohydrate Polymers, 2025)

Integration of biogas and liquid recirculation enhance methane production in high-solid anaerobic digestion of pig manure and rice husks - Zhuoqi Xu; Wenbo Gu; Yuwei Shi; Baibing Li; Zhenya Zhang; Zhongfang Lei; Tian Yuan; Yanfei Cheng; Mijung Kim; Akio Shoji (Bioresource Technology, 2025)

Effects of maize/soybean intercropping on rhizosphere soil phosphorus availability and functional genes involved in phosphorus cycling in Northwest China - Wenmin Wang; Fating Yin; Jiacheng Gu; Zhen Wang; Fenghua Zhang; Luhua Li; Zhibo Cheng (Plant and Soil, 2025)

Impacts of land use/cover change on urban rainfall-flooding processes based on numerical simulations - Xiaosheng Lian; Liangwei Li; Jianmei Cheng; Xihui Gu (Hydrological Sciences Journal, 2024)

YOLO-CG-HS: A lightweight spore detection method for wheat airborne fungal pathogens - Tao Cheng; Dongyan Zhang; Chunyan Gu; Xin-Gen Zhou; Hongbo Qiao; Wei Guo; Zhen Niu; Jiyuan Xie; Xue Yang (Computers and Electronics in Agriculture, 2024)

Enhancing the overturning resistance capacity of high aspect ratio structure through hybrid base isolation and inter-storey isolation - Jingcai Zhang; Yingna Li; Hao Yang; Xin Ji; Lingxi Gu; Wangjingyi Li; Bo Wang; Liang Cheng; Chunwei Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Hydroconversion of waste polyethylene plastics under mild conditions using mechanically mixed bifunctional catalysts: Impact of metal-acid balance and proximity - Wenbo Zhang; Leilei Cheng; Weiqiang Zhu; Jing Gu; Shaonan Tian; Haoran Yuan; Yong Chen (Process Safety and Environmental Protection, 2024)

Fireball distribution characteristics and thermal radiation effects in the explosion of aviation kerosene storage tank - Cheng Wang; Shixiang Song; Gongtian Gu; Ming Gao; Yi Yang (Process Safety and Environmental Protection, 2024)

Using an ensemble Kalman filter method for a soil nitrogen transport model in the real rice field - Juxiu Tong; Yang Gu; Kuan Cheng (Journal of Hydrology, 2024)

Facet-induced fractionation of humic acid by hematite and the promoted-photodegradation of 17β-estradiol catalyzed by hematite-humic complex - Ziyan Zhou; Hao Wu; Boming Fu; Dingding Wu; Xinhao Wang; Davide. Vione; Xin Jin; Yanfen Fang; Cheng Gu (Journal of Hazardous Materials, 2024)

Removal of 48 per- and polyfluoroalkyl substances (PFAS) throughout processes in domestic and general industrial wastewater treatment plants: Implications for emerging alternatives risk control - Yueqing Zhang; Ruochen Dong; Feng Ge; Minghui Hong; Zhanghao Chen; Yunqiao Zhou; Jing Wei; Cheng Gu; Deyang Kong (Journal of Hazardous Materials, 2024)

Exploring the effect of part differences on metabolite molecule changes in refrigerated pork: Identifying key metabolite compounds and their conversion pathways - Minghui Gu; Cheng Li; Yuqing Ren; Li Chen; Shaobo Li; Dequan Zhang; Xiaochun Zheng (Food Chemistry, 2024)

Vine tea kombucha ameliorates non-alcoholic fatty liver disease in high-fat diet fed mice via antioxidation, anti-inflammation and regulation of gut microbiota - Jin Cheng; Si-Yu Huang; Ruo-Gu Xiong; Si-Xia Wu; Zhi-Jun Yang; Dan-Dan Zhou; Adila Saimaiti; Cai-Ning Zhao; Hui-Lian Zhu; Hua-Bin Li (Food Bioscience, 2024)

Predicting plateau atmospheric ozone concentrations by a machine learning approach: A case study of a typical city on the southwestern plateau of China - Qiyao Wang; Huaying Liu; Yingjie Li; Wenjie Li; Donggou Sun; Heng Zhao; Cheng Tie; Jicang Gu; Qilin Zhao (Environmental Pollution, 2024)

Modeling obliquely incident seismic wave propagation in rocks via the FDM-DEM coupling scheme: Algorithms and applications - Kunsheng Gu; Jian Zhou; Fuchu Dai; Luqing Zhang; Wei Cheng; Zhenhua Han (Computers and Geotechnics, 2024)

Design and operation of a demonstration plant for fluidized bed low-temperature gasification of alternative fuels applied to cement production - Shuchao Cheng; Baosheng Jin; Liye Wang; Songshan Cao; Tengfei He; Yi Chen; Xiangchao Su; Qinyang Gu; Weiguo Zhang; Peida Sheng; Yaji Huang (Chemical Engineering Journal, 2024)

Confined pyrolysis to transfer MXene-like MOF into 2D carbon nanosheet boosting the ozone oxidation of antibiotic: Degradation behavior and intrinsic mechanism - Wenhui Li; Xiufang Shen; Zhonglin Chen; Tian Tian; Chenyong Liu; Cheng Gu; Weichuan Qiao; Ming Zhang (Chemical Engineering Journal, 2024)

Ru induced charge redistribution of MnO2 spheric nanozyme boosted hydrogen sulfide selective detection and cystathionine γ-lyase activity sensitive evaluation - Zhao Li; Xuan Zhang; Haorong Cheng; Zhongyuan Gu; Changchun He; Ju Wang; Xinxin Shi; Weidan Na; Tongxiang Li; Lin Tian (Chemical Engineering Journal, 2024)

Efficient separation of per- and polyfluoroalkyl substances (PFAS) from water by aminated polyacrylamide hydrogel foam - Yichen Xu; Xueru Yu; Xinhao Wang; Yiqian Song; Wenran Wang; Ming Zhang; Deyang Kong; Zhanghao Chen; Cheng Gu (Chemical Engineering Journal, 2024)

Tetraphenylborate enhanced enzymatic production of γ-cyclodextrin: System construction and its mechanism - Zihang Jiang; Yu Xiao; Zhengyao Xu; Zhengbiao Gu; Zhaofeng Li; Xiaofeng Ban; Yan Hong; Li Cheng; Caiming Li (Carbohydrate Polymers, 2024)

Highly efficient adventitious root regeneration and Agrobacterium rhizogenes-mediated hairy root transformation in pear - Cheng Xue; Liyan Chang; Junjun Liu; Kaidi Gu; Pengfei Zheng; Jun Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Source Apportionment of Carbonaceous Aerosols during PM2.5 Pollution Episodes in Xi’an, Northwestern China: Estimation of the Potential of Carbon Emission Reduction by Rural Household Energy Substitution - Yunxuan Gu; Hongmei Xu; Liyan Liu; Mengyun Yang; Zhenxing Shen; Xiaojian Chang; Peng Cheng (Aerosol Science and Engineering, 2024)

Synergistic adsorption and UV degradation of perfluorooctanoic acid by amine-functionalized A-center sphalerite - Zhanghao Chen; Shuoqi Zhang; Na Mi; Xinhao Wang; Yichen Xu; Longlong Qiu; Cheng Gu; Guixiang Zeng (Water Research, 2024)

Simple preparation of nitenpyram-intercalated clay nanosheets with reduced leaching risk and improved safety to insect pollinators - Chengshuai He; Jiao Liu; Jikang Cheng; Zhe Yu; Hui Zhang; Aiguo Gu; Song Yang; Yunhao Gao; Congfen Gao (Journal of Hazardous Materials, 2024)

In-depth metaproteomics analysis reveals the protein profile and metabolism characteristics in pork during refrigerated storage - Minghui Gu; Dequan Zhang; Cheng Li; Yuqing Ren; Guangchun Song; Li Chen; Shaobo Li; Xiaochun Zheng (Food Chemistry, 2024)

Emulsions stabilized by okra polysaccharides: Physicochemical, interfacial, and emulsification properties - Yue Lv; Xiujuan Cai; Ting Xv; Hongxu Gao; Yuan Xv; Yuchao Gu; Dan Cheng; Mingyan Yan; Yinping Li (Food Hydrocolloids, 2024)

Optimizing nitrogen application patterns and amounts to improve maize yield and water-nitrogen use efficiencies in the Loess Plateau of China: A meta-analysis - Rui Yin; Xiaobo Gu; Zhikai Cheng; Wenlong Li; Yuming Wang; Tongtong Zhao; Wenjing Cai; Yadan Du; Huanjie Cai (Field Crops Research, 2024)

Monitoring aboveground organs biomass of wheat and maize: A novel model combining ensemble learning and allometric theory - Zhikai Cheng; Xiaobo Gu; Chunyu Wei; Zhihui Zhou; Tongtong Zhao; Yuming Wang; Wenlong Li; Yadan Du; Huanjie Cai (European Journal of Agronomy, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

Simplification and verification of chemical reaction mechanism of RP-3 aviation kerosene - Cheng Wang; Xiaoli Li; Gongtian Gu; Tonghui Yang (Process Safety and Environmental Protection, 2024)

A hydrothermal-assisted strategy to transform Fe-doped MOF into 3D interwoven network structure of CNTs boosting the degradation of antibiotics via peroxymonosulfate activation - Tian Tian; Xiufang Shen; Ming Zhang; Zhonglin Chen; Weizhen Shao; Chenyong Liu; Wenhui Li; Cheng Gu; Weichuan Qiao (Journal of Environmental Chemical Engineering, 2024)

Novel fire-resistant SiBCN fiber paper with efficient electromagnetic interference shielding and Joule-heating performance - Qi Ding; Jiahao Yang; Shijia Gu; Chutong Chen; Zhi Cheng; Yongping Liu; Peng Yan; Mingming Si; Sijia Lu; Zongbo Zhang; Lianjun Wang; Yuchi Fan; et al. (Chemical Engineering Journal, 2024)

Correction to: Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

Image compression–based DS-InSAR method for landslide identification and monitoring of alpine canyon region: a case study of Ahai Reservoir area in Jinsha River Basin - Xiaona Gu; Yongfa Li; Xiaoqing Zuo; Jinwei Bu; Fang Yang; Xu Yang; Yongning Li; Jianming Zhang; Cheng Huang; Chao Shi; Mingze Xing (Landslides, 2024)

Effects of Cu Stress on Root Growth and Proteomics of Vetiver (Vetiveria zizanioides L.) - Dongheng Li; Huaqiu Wang; Tianyue Gu; Shuai Liu; Wenguang Xiong; Wei Cheng (Journal of Plant Growth Regulation, 2024)

WNT2B high‑expressed fibroblasts induce the fibrosis of IBD by promoting NK cells secreting IL-33 - Yanling Cheng; Shuzhe Xiao; Lin Lan; Danqiong Liu; Rui Tang; Jianbiao Gu; Li Ma; Zhihua He; Xirong Chen; Lanlan Geng; Peiyu Chen; Huiwen Li; et al. (Journal of Molecular Medicine, 2024)

Photochemical Transformation of Ibuprofen and Chlorophene Induced by Dissolved Organic Matter - Na Mi; Liuqing Huang; Xinhao Wang; Xueru Yu; Zhenfeng Shi; Xuan Ni; Hanyang Chen; Yong Shang; Xiufang Shen; Cheng Gu; Zhanghao Chen (Bulletin of Environmental Contamination and Toxicology, 2024)

Development of a TLR-Based Model That Can Predict Prognosis, Tumor Microenvironment, and Drug Response for Esophageal Squamous Cell Carcinoma - Tao Cheng; Xiaolong Huang; Huiqin Yang; Jie Gu; Chunlai Lu; Cheng Zhan; Fengkai Xu; Di Ge (Biochemical Genetics, 2024)

Cortical microstructural alterations in different stages of Parkinson’s disease - Xueqin Bai; Tao Guo; Xiaojun Guan; Cheng Zhou; Jingjing Wu; Haoting Wu; Xiaocao Liu; Chengqing Wu; Jingwen Chen; Jiaqi Wen; Jianmei Qin; Sijia Tan; et al. (Brain Imaging and Behavior, 2024)

Crop aboveground biomass monitoring model based on UAV spectral index reconstruction and Bayesian model averaging: A case study of film-mulched wheat and maize - Zhikai Cheng; Xiaobo Gu; Zhihui Zhou; Rui Yin; Xiaobo Zheng; Wenlong Li; Wenjing Cai; Tian Chang; Yadan Du (Computers and Electronics in Agriculture, 2024)

The vertical partitioning between denitrification and dissimilatory nitrate reduction to ammonium of coastal mangrove sediment microbiomes - Yijun Fan; Zhengyuan Zhou; Fei Liu; Lu Qian; Xiaoli Yu; Fangjuan Huang; Ruiwen Hu; Hualong Su; Hang Gu; Qingyun Yan; Zhili He; Cheng Wang (Water Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Controllable preparation of graphene glass fiber fabric towards mass production and its application in self-adaptive thermal management - Ruojuan Liu; Fan Yang; Shuting Cheng; Xianghe Yue; Fushun Liang; Wenjuan Li; Jingnan Wang; Qinchi Zhang; Liangyu Zou; Hao Yuan; Yuyao Yang; Kangyi Zheng; et al. (Science Bulletin, 2024)

Novel 3D photosynthetic traits derived from the fusion of UAV LiDAR point cloud and multispectral imagery in wheat - Yangyang Gu; Yongqing Wang; Yapeng Wu; Timothy A. Warner; Tai Guo; Hongxu Ai; Hengbiao Zheng; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao (Remote Sensing of Environment, 2024)

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

Greenhouse gas emissions and carbon and water footprints during processing of Lei bamboo shoots - Zixiang Weng; Shuiqin Lu; Xuekun Cheng; Chunyu Pan; Guangyu Wang; Dejin Dong; Zhengcai Li; Ziliang Zhao; Lei Gu; Linghui Dong; Zhengwen Niu; Chong Li; et al. (Journal of Cleaner Production, 2024)

A preliminary integrated analysis of regional paleoclimate variations in China over the past ∼ 21 ka - Huayu Lu; Yan Zhao; Xiangdong Yang; Haibing Wu; Cheng Zhao; Jingjing Wang; Xiaoyong Wang; Xueyuan Kuang; Xiaojian Zhang; Chunmei Ma; Fuzhi Lu; Xiayun Xiao; et al. (Global and Planetary Change, 2024)

Improved stability and antibacterial activity of cinnamaldehyde emulsion co-stabilized by cyclodextrin glycosyltransferase-catalyzed starch products and Tween 80 - Shuangdi Chen; Zhaofeng Li; Bimal Chitrakar; Zhengbiao Gu; Xiaofeng Ban; Yan Hong; Li Cheng; Caiming Li (Food Hydrocolloids, 2024)

Non-covalent sorption properties of porous starch materials: Enhancement strategy and applications - Beibei Zhao; Zhengbiao Gu; Li Cheng; Yan Hong (Food Hydrocolloids, 2024)

Correlation between emulsification and butyryl group distribution in various butyrylated starches - Yibing Jiao; Lingjin Li; Li Cheng; Zhaofeng Li; Caiming Li; Zhengbiao Gu; Yan Hong (Food Hydrocolloids, 2024)

Recent progress on the organelle targeted AlEgens for bioimaging and treatment of diseases - Qihang Ding; Yan Luo; Jun Hu; Shuai Zhang; Wenzhe Zhang; Yuanyuan Feng; Kun Qian; Xin Li; Zhen Cheng; Meijia Gu (Chemical Engineering Journal, 2024)

Heat-moisture treatment of freshly harvested high-amylose maize kernels improves its starch thermal stability and enzymatic resistance - Zhonghua Gu; Gaomin Cheng; Xianying Sha; Haochen Wu; Xinwei Wang; Renyong Zhao; Qiang Huang; Yinong Feng; Jihua Tang; Hongxin Jiang (Carbohydrate Polymers, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Soil microplastic analysis: a harmonized methodology - Piumi Amasha Withana; Sachini Supunsala Senadheera; Defu He; Michael S. Bank; Cheng Gu; Sung Yeon Hwang; Yong Sik Ok (Critical Reviews in Environmental Science and Technology, 2024)

Microplastics weaken the digestion and absorption functions in the golden pompano (Trachinotus blochii) by affecting the intestinal structure, bacteria and metabolites - Fu Cheng Yao; Chun Xiu Jin; Huan Liang; Yu Zhang; Yue Gu; Fei Biao Song; Zhi Zhou; Jun Long Sun; Jian Luo (Chemosphere, 2024)

Omics analysis of ‘Shine Muscat’ grape grafted on different rootstocks in response to cadmium stress - Yafeng Gu; Xiaobin Fan; Ke Jiang; Pin Liu; Huiqing Chang; Okbagaber Andom; Jieshan Cheng; Zhaojun Li (Science of The Total Environment, 2024)

Research on the flow characteristics and self-ignition mechanism of high-pressure hydrogen jets in bifurcated tubes - Xuhai Pan; Qi Cheng; Xin Gu; Yiming Jiang; Zhilei Wang; Min Hua; Jianjun Xiao; Thomas Jordan; Juncheng Jiang (Process Safety and Environmental Protection, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Natural-inspired hierarchic double-Janus solar evaporator for stable clean water production from high-salinity emulsions - Zhen Yu; Ruonan Gu; Yuqing Su; Yihang Li; Guangli Liu; Shaoan Cheng (Journal of Hazardous Materials, 2024)

Heterogeneous coupling of δ13Corg and δ13Ccarb during the Shuram Excursion: Implications for a large dissolved organic carbon reservoir in the Ediacaran ocean - Haodong Gu; Jun Hu; Meng Cheng; Haiyang Wang; Matthew S. Dodd; Zihu Zhang; Thomas J. Algeo; Chao Li (Global and Planetary Change, 2024)

Development of a rhodamine-based fluorescent probe for ATP detection for potential applications in meat freshness assessment - Yuanyuan Su; Minghui Gu; Cheng Li; Dequan Zhang; Yuqing Ren; Li Chen; Shaobo Li; Xiaochun Zheng (Food Chemistry, 2024)

Influence of increasing acclimation temperature on growth, digestion, antioxidant capacity, liver transcriptome and intestinal microflora of Ussruri whitefish Coregonus ussuriensis Berg - Kaibo Ge; Ze Fan; Tianqing Huang; Wei Gu; Gaochao Wang; Enhui Liu; Runlei Pan; Datian Li; Yunchao Sun; Zuochun Yao; Liwei Wang; Cheng Zhao; et al. (Fish & Shellfish Immunology, 2024)

A tumor-responsive nanostrategy for reducing the risk of immunotherapy-related myocarditis - Mengjun Sui; Simeng Wang; Ye Zhou; Hui Dang; Zekun Zeng; Kunrong Gu; Hongxin Cao; Meiju Ji; Penggao Dai; Yangyang Cheng; Peng Hou (Chemical Engineering Journal, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Vitamin e succinate-glycol chitosan modified copper ferrite nanocomposites for lung cancer: Targeted oxidative stress regulation induces cuproptosis and ferroptosis - Guansong Hu; Weibin Cheng; Miao Gu; Lifeng Hang; Weiyang Yang; Tao Liu; Wuming Li; Xiudong Shi; Min Liu; Junzhang Tian (Chemical Engineering Journal, 2024)

Multi-modal fusion and multi-task deep learning for monitoring the growth of film-mulched winter wheat - Zhikai Cheng; Xiaobo Gu; Yadan Du; Chunyu Wei; Yang Xu; Zhihui Zhou; Wenlong Li; Wenjing Cai (Precision Agriculture, 2024)

Hydroxysafflor Yellow A and Tenuigenin Exhibit Neuroprotection Effects Against Focal Cerebral Ischemia Via Differential Regulation of JAK2/STAT3 and SOCS3 Signaling Interaction - Lu Yu; Cheng Zhang; Lingling Gu; Hong Chen; Yan Huo; Shuyan Wang; Jie Tao; Chuan Xu; Qiujuan Zhang; Mingliang Ma; Jun Zhang (Molecular Neurobiology, 2024)

Characteristics of T cell premature senescence in maintenance hemodialysis patients - Wangshu Wu; Ahui Song; Kewei Xie; Jiayue Lu; Bingru Zhao; Cheng Qian; Minzhou Wang; Lulin Min; Wenkai Hong; Huihua Pang; Renhua Lu; Leyi Gu (Inflammation Research, 2024)

Facilities pond aquaculture system construction and the ecological economy analyzed - Hao Zhu; Zhao-Jun Gu; Guo-Feng Cheng; Xing-Guo Liu; Rong Tang (Aquacultural Engineering, 2024)

Assessment of co-benefits from on-road vehicle electrification in Suzhou City, China - Feiyue Qian; Cui Da; Chunchen Lu; Xinyu Gu; Junjian Yang; Chaowei Shi; Zhen Feng; Yuanyuan Cheng (Urban Climate, 2024)

Expression of genes related to gonadal development and construction of gonadal DNA methylation maps of Trachinotus blochii under hypoxia - Yue Gu; Chun Xiu Jin; Zai Hui Tong; Tian Jiang; Fu Cheng Yao; Yu Zhang; Jie Huang; Fei Biao Song; Jun Long Sun; Jian Luo (Science of The Total Environment, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Smart reconfigurable electromagnetic metamaterials based on thermadapt shape memory Poly(ethylene–vinyl acetate) - Haoyu Gu; Tong Lv; Qiankun Zhang; Dequan Chi; Yang Zhang; Zhongjun Cheng; Zhimin Xie; Yongjun Xu; Dongjie Zhang; Yuyan Liu (Chemical Engineering Journal, 2024)

Regulation of gene expression in the secondary metabolic synthesis pathway of Lonicera japonica Flos by yeast polysaccharides - Xu-peng Gu; Lin-lin Yang; Da-ming Qi; Di Zhang; Tian-liang Liu; Cheng-ming Dong (Physiology and Molecular Biology of Plants, 2024)

The Type Strain of Bifidobacterium indicum Scardovi and Trovatelli 1969 (Approved Lists 1980) is ATCC 25912, not DSM 20214, and Rejection to Reclassify Bifidobacterium coryneforme as Bifidobacterium indicum - Cheng-Shan Jiang; Chun Yan Li; Chun Tao Gu (Current Microbiology, 2024)

Porcine kobuvirus enhances porcine epidemic diarrhea virus pathogenicity and alters the number of intestinal lymphocytes in piglets - Simin Wu; Fang Gou; Jie Meng; Xin Jin; Wanchen Liu; Weishuai Ding; Weihang Xu; Changqin Gu; Xueying Hu; Guofu Cheng; Pan Tao; Wanpo Zhang (Veterinary Microbiology, 2024)

Role of low-molecular-weight organic compounds on photochemical formation of Mn(III)-ligands in aqueous systems: Implications for BPA removal - Song Gao; Xinghao Wang; Xinhao Wang; Xiru Chen; Sijia Liang; Ziyan Zhou; Shuxia Xu; Yanfen Fang; Juan Gao; Cheng Gu (Science of The Total Environment, 2024)

Metal-enzyme nanogel biochemical composite: An efficient platform for one-pot dynamic kinetic resolution of amines - Meng Wang; Jie Sheng; Leyi Gu; Xiaoxu Wang; Weihua Cheng; Peiyi Ji; Shenfang Jiang; Yuanzhe Huang; Zonglin Li; Chenhao Zhang; Hui Li (Journal of Cleaner Production, 2024)

Carbon pools in forest systems and new estimation based on an investigation of carbon sequestration - Bin Wang; Guoce Xu; Zhanbin Li; Yuting Cheng; Fengyou Gu; Mingzhu Xu; Yixin Zhang (Journal of Environmental Management, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Effect of hydrocolloids on starch digestion: A review - Mengjie Ma; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Yan Hong (Food Chemistry, 2024)

Sono-assembly of ellagic acid into nanostructures significantly enhances aqueous solubility and bioavailability - Wei Gu; Ruolin Kong; Shuyang Qi; Xuxi Cheng; Xuyi Cai; Ziyun Zhou; Shunan Zhang; Hongyu Zhao; Jinyun Song; Qinglian Hu; Huiwen Yu; Huangjin Tong; et al. (Food Chemistry, 2024)

Effects of heat moisture treatment on the structure and digestibility of high amylose starch-lauric acid complexes - Haoran Zhang; Shenglin Sun; Li Cheng; Zhaofeng Li; Caiming Li; Yan Hong; Zhengbiao Gu (Food Hydrocolloids, 2024)

Stabilization of Pickering emulsions by oxidized starch/zein nanoparticle complexes - Zhaoxi Zhang; Zhengbiao Gu; Li Cheng; Caiming Li; Zhaofeng Li; Yan Hong (Food Bioscience, 2024)

Unveiling the biointerfaces characteristics and removal pathways of Cr(Ⅵ) in Bacillus cereus FNXJ1-2-3 for the Cr(Ⅵ)-to-Cr(0) conversion - Zhaoxia Li; Entian Cui; Naipeng Gu; Weixing Ma; Qingyuan Guo; Xuan Li; Jianxiang Jin; Qun Wang; Cheng Ding (Environmental Research, 2024)

Stabilizing high-Ni cathodes with gradient surface Ti-enrichment - Wenchang Zhu; Xiaotian Zhu; Jizhen Qi; Junyi Yao; Yanbin Shen; Guanjian Cheng; Xue Huang; Shiqi Yang; Hao Zhang; Chao-Lung Chiang; Yan-Gu Lin; Jianming Bai; et al. (Chemical Engineering Journal, 2024)

A freestanding rotating triboelectric nanogenerator with large area and high efficiency for triboelectric plasma CO2 reduction - Hongjie Cao; Qinglong Ru; Dongyang Fang; Sumin Li; Nannan Liu; Wei Jiang; Hui Hu; Yongcui Yang; Guangqin Gu; Bao Zhang; Gang Cheng; Sanjun Yang; et al. (Chemical Engineering Journal, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

Dictyosphaerium sp.-treated aerobic digestate of perishable waste as substitution for vegetable hydroponic nutrient solution - Mengjie Zhang; Xiaoyan Zhang; Qilu Cheng; Feifan Shi; Yuan Fu; Jianlin Xu; Bing Gu; Junwei Ma; Li Yang; Qifa Zhou; Hui Lin (Algal Research, 2024)

Penetration Characteristics of Mono-Column Composite Bucket Foundation for Offshore Wind Turbines - Jiandong Xiao; Xiaoqiang Gu; Yifeng Lin; Haifeng Cheng; Xin Qi; Puyang Zhang; Shuyang Wang (Journal of Marine Science and Engineering, 2024)
To address the issue of seepage and soil plugging during the sinking of mono-column composite bucket foundations (MCCBFs), experiments were conducted on the installation of foundations under a variety of complex geological conditions. The effect of negative pressure sinking mode on the foundation’s seepage field was analyzed, the formation mechanism of soil plugging in sand was explained, and an efficient method for calculating the height of soil plugging was proposed in conjunction with these investigations. The findings demonstrate that the finite element method simulation of the soil’s seepage field is the most accurate, that the pumping volume of the foundation during sinking through is high, that the formation of the soil plug height is high, and that clear depressions can be seen on the foundation manifold’s exterior. The equation presented in this study makes it easier to forecast the height of a foundation plug and can offer direction for engineering design.

Crosstalk among proximal tubular cells, macrophages, and fibroblasts in acute kidney injury: single-cell profiling from the perspective of ferroptosis - Yulin Wang; Ziyan Shen; Shaocong Mo; Han Zhang; Jing Chen; Cheng Zhu; Shiqi Lv; Di Zhang; Xinhui Huang; Yulu Gu; Xixi Yu; Xiaoqiang Ding; et al. (Human Cell, 2024)
The link between ferroptosis, a form of cell death mediated by iron and acute kidney injury (AKI) is recently gaining widespread attention. However, the mechanism of the crosstalk between cells in the pathogenesis and progression of acute kidney injury remains unexplored. In our research, we performed a non-negative matrix decomposition (NMF) algorithm on acute kidney injury single-cell RNA sequencing data based specifically focusing in ferroptosis-associated genes. Through a combination with pseudo-time analysis, cell–cell interaction analysis and SCENIC analysis, we discovered that proximal tubular cells, macrophages, and fibroblasts all showed associations with ferroptosis in different pathways and at various time. This involvement influenced cellular functions, enhancing cellular communication and activating multiple transcription factors. In addition, analyzing bulk expression profiles and marker genes of newly defined ferroptosis subtypes of cells, we have identified crucial cell subtypes, including Egr1 + PTC-C1, Jun + PTC-C3, Cxcl2 + Mac-C1 and Egr1 + Fib-C1. All these subtypes which were found in AKI mice kidneys and played significantly distinct roles from those of normal mice. Moreover, we verified the differential expression of Egr1, Jun, and Cxcl2 in the IRI mouse model and acute kidney injury human samples. Finally, our research presented a novel analysis of the crosstalk of proximal tubular cells, macrophages and fibroblasts in acute kidney injury targeting ferroptosis, therefore, contributing to better understanding the acute kidney injury pathogenesis, self-repairment and acute kidney injury-chronic kidney disease (AKI-CKD) progression.

Assessment of the influence of UAV-borne LiDAR scan angle and flight altitude on the estimation of wheat structural metrics with different leaf angle distributions - Yangyang Gu; Yongqing Wang; Tai Guo; Caili Guo; Xue Wang; Chongya Jiang; Tao Cheng; Yan Zhu; Weixing Cao; Qi Chen; Xia Yao (Computers and Electronics in Agriculture, 2024)

Molecular insights into the catabolism of dibutyl phthalate in Pseudomonas aeruginosa PS1 based on biochemical and multi-omics approaches - Huan Du; Ji-Liang Cheng; Zhi-Yong Li; Huai-Ning Zhong; Shuang Wei; Yu-Juan Gu; Can-Can Yao; Miaoyue Zhang; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Amendment of straw with decomposing inoculants benefits the ecosystem carbon budget and carbon footprint in a subtropical wheat cropping field - Cheng Ji; Jidong Wang; Cong Xu; Yian Gu; Jie Yuan; Dong Liang; Lei Wang; Yunwang Ning; Jie Zhou; Yongchun Zhang (Science of The Total Environment, 2024)

Prediction of SO2 emission concentration in industrial flue gas based on deep learning: The ammonia desulfurization system of the Yunnan aluminum carbon plant as the research object - Qiyao Wang; Heng Zhao; Qilin Zhao; Jie Hou; Senlin Tian; Yingjie Li; Cheng Tie; Jicang Gu (Process Safety and Environmental Protection, 2024)

The mechanisms of ·OH formation in MnO2 and oxalate system: Implication for ATZ removal - Jinjin Zhou; Xinghao Wang; Zhaoyue Sun; Cheng Gu; Juan Gao (Journal of Hazardous Materials, 2024)

Prolonged evolution of syn-collisional progressive deformation of the Trans-North China Orogen: Structural and geochronological evidence from the Xiaoqinling region, central China - Yunjian Li; Guang Zhu; Chengchuan Gu; Cheng Liu; Shuai Zhang; Xiaodong Wu; Tian Zhao; Chao Li; Menglong Dong (Gondwana Research, 2024)

Time-dependent hormesis transfer from five high-frequency personal care product components to mixtures - Rujun Cheng; Peng Huang; Ting-Ting Ding; Zhong-Wei Gu; Meng-Ting Tao; Shu-Shen Liu (Environmental Research, 2024)

Enhancing in-season yield forecast accuracy for film-mulched wheat: A hybrid approach coupling crop model and UAV remote-sensing data by ensemble learning technique - Zhikai Cheng; Xiaobo Gu; Zhihui Zhou; Yuanling Zhang; Haowei Yin; Wenlong Li; Tian Chang; Yadan Du (European Journal of Agronomy, 2024)

Study on non-isothermal reaction and sintering kinetics of Ca(OH)2 particle cluster dehydration with temperature distribution modification - Yishi Gu; Yuxiang Cheng; Zhongjie Shen; Feng Lv; Dayang Wan; Yongchuan Gao; Yuezhang Duan; Jianliang Xu; Qinfeng Liang; Xiaolei Guo; Haifeng Liu (Chemical Engineering Journal, 2024)

Poly(vinylidene fluoride)-based composite membranes with continuous metal–organic framework layer for high-performance separators of lithium-ion batteries - Mengying Li; Sha Cheng; Jisong Zhang; Cheng Huang; Jiapei Gu; Jin Han; Xu Xu; Xiao Chen; Pengchao Zhang; Ya You (Chemical Engineering Journal, 2024)

Evaluation of benefits and risks of immunosuppressive drugs in biomaterial-based neural progenitor cell transplantation for spinal cord injury repair - Bo Guo; Xinhao Zhao; Yunlong Zou; Xiaokang Cheng; Zheng Sun; Xiaoyu Xue; Man Yin; Chen Jin; Zhenni Chen; Rui Quan; Wenbin Liu; Bin Chen; et al. (Chemical Engineering Journal, 2024)

Analysis of human health effects under ozone exposure in the oasis area of Hetao Plain - Lanzhi Wang; Tianzhen Ju; Bingnan Li; Xuhui Xia; Cheng Huang; Zhichao Lv; Zhenrong Gu (Environmental Monitoring and Assessment, 2024)

Optimization Analysis of the Arrangement of the Submerged Floating Tunnel Subjected to Waves - Wenbo Pan; Cheng Cui; Chun Chen; Mingxiao Xie; Qian Gu; Zhiwen Yang (Journal of Marine Science and Engineering, 2024)
The motion responses, mooring tensions, and submergence depth are the dominant factors for the arrangement of the Submerged Floating Tunnel (SFT) subjected to waves. Generally, the maximum values of motion responses, mooring tensions, and absolute submergence depth are mainly focused on. In the present study, experiments are implemented to measure the motion responses and mooring tensions of the SFT with different mooring patterns and submergence depths under waves with different characteristic wave heights and periods. In order to evaluate the arrangement of the SFT more effectively and comprehensively, besides the maximum values, several new characteristic parameters are introduced. Such parameters account for the motion responses in the frequency domain, the uniformity of the tension distribution, the length of time during which the cable reaches a relaxed condition during wave action, the KC number, the dimensionless period, the wave height, and the submergence depth. The results from the optimization analysis show the following: according to the characteristic values of motion responses and mooring tensions, the pattern of diagonal cables is better than that of diagonal cables + vertical cables; and within the range of the present experiments, there are optimal dimensionless parameters—the dimensionless submergence depth d0/LP ≥ 0.15, the KC number ≤ 0.8, or the dimensionless wave height Hs/d0 ≤ 0.10—for the condition of which the dynamic responses and mooring tensions vary slightly.

Time-dependent nonmonotonic concentration-response and synergism of alkyl glycosides with different alkyl side chain to Vibrio qinghaiensis sp. -Q67 - Meng-Ting Tao; Shu-Shen Liu; Ting-Ting Ding; Zhong-Wei Gu; Ru-Jun Cheng (Science of The Total Environment, 2024)

Analysis of factors influencing the energy efficiency in Chinese wastewater treatment plants through machine learning and SHapley Additive exPlanations - Jinze Li; Zexuan Du; Junyan Liu; Linji Xu; Li-ping He; Li Gu; Hong Cheng; Qiang He (Science of The Total Environment, 2024)

Effect of ammonia on N migration and transformation characteristics during coal pyrolysis: Quantum chemical calculations and pyrolysis experiments - Ping Chen; Longxiang Qiao; Cheng Gong; Mingyan Gu; Kun Luo; Jianren Fan (Fuel, 2024)

Enhanced hydroconversion of polyethylene via dual-functional catalysis: Exploiting ZSM-22 pore-mouth catalysis and Ru electronic effect - Leilei Cheng; Shaonan Tian; Dong Liang; Jing Gu; Ruizhe Chen; Xueru Chen; Haoran Yuan; Yong Chen (Chemical Engineering Journal, 2024)

Structural characteristics, digestion properties, fermentation properties, and biological activities of butyrylated starch: A review - Yi Zhang; Lingjin Li; Shenglin Sun; Li Cheng; Zhengbiao Gu; Yan Hong (Carbohydrate Polymers, 2024)

Effect of solution on starch structure: New separation approach of amylopectin fraction from gelatinized native corn starch - Xinxin Lv; Yan Hong; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban (Carbohydrate Polymers, 2024)

Investigation of influential variations among variables in daylighting glare metrics using machine learning and SHAP - Zhaoyang Luo; Xuanning Qi; Cheng Sun; Qi Dong; Jian Gu; Xinting Gao (Building and Environment, 2024)

Bronchoalveolar Lavage Fluid Microbiota is Associated with the Diagnosis and Prognosis Evaluation of Lung Cancer - Chen Cheng; Zhifeng Wang; Chao Ding; Pingli Liu; Xiaoqiang Xu; Yan Li; Yi Yan; Xiaocong Yin; Bi Chen; Bing Gu (Phenomics, 2024)

Production improvement and photoprotection of melanin produced by Bacillus thuringiensis - Baoju An; Yunda Zhan; Qian Cheng; Jun Cai; Xiaofei Gu (BioControl, 2024)

Measuring ecosystem services and ecological sensitivity for comprehensive conservation in Giant Panda National Park - Cheng Li; Rong Hou; Ziqiang Bao; Wei Wu; Jacob R. Owens; Wenlei Bi; Qiang Xu; XiaoDong Gu; Zuofu Xiang; Dunwu Qi (Conservation Biology, 2024)
China announced the development of its first 5 national parks in 2021, the primary objective of which is to conserve the natural state and integrity of natural ecosystems. As such, ecosystem services and biodiversity levels are crucial assessment factors for the parks. For Giant Panda National Park (GPNP), we evaluated ecological sensitivity based on water and soil erosion and rocky desertification; ecosystem services based on headwater conservation, soil and water conservation, and biodiversity conservation; and presence of giant panda ( Ailuropoda melanoleuca ) and sympatric species (e.g., takin [ Budorcas taxicolor ], Asiatic black bear [ Ursus thibetanus ]) habitat suitability derived from niche modeling to identify the ecosystem status and assess ecological problems within the park. From our results, we proposed ecologically critical areas to target to meet the park's goals. The suitable habitat for pandas and sympatric species encompassed 62.98% of the park and occurred mainly in the Minshan Mountains. One quarter of the total area (25.67%) contained areas important for ecosystem services. Ecologically sensitive and extremely sensitive areas covered 88.78% of the park and were distributed mainly in Qionglaishan and Minshan Mountains. This coverage indicated that there was much habitat for pandas and sympatric species but that the ecosystems in GPNP are vulnerable. Therefore, ecologically critical areas encompassed all suitable habitats for all the species examined and areas important and extremely important to ecosystem service provision,ecologically sensitive and extremely sensitive areas, encompassed 15.17% of panda habitat, accounted for 16.37% of the GPNP area, and were distributed mainly in the Minshan Mountains. Our results indicated where conservation efforts should be focused in the park and that by identifying ecologically critical areas managers can provide targeted protection for wildlife habitat and ecosystems and effectively and efficiently protect the composite ecosystem. Additionally, our methods can be used to inform development of new national parks.

Energy Characteristics in the Flow Channel of the Shaft-Type Tubular Pumping Station Considering Tides - Yufan He; Can Luo; Li Cheng; Yandong Gu; Bin Gu (Journal of Marine Science and Engineering, 2024)
The shaft-type tubular pumping station has the remarkable characteristics of a large flow rate and high efficiency. It can realize the functions of irrigation, pumping, and drainage through pumping and generating conditions considering tides. Moreover, it is widely used in the plain area of eastern China and the tidal area along the marine region. Due to the different topological features of the airfoil of the impeller, the energy evolution characteristics of the shaft-type tubular pumping station during pumping and generating conditions remain unclear. The entropy generation theory was introduced to numerically simulate the flow pattern and energy characteristics in the shaft-type channel, impeller, and straight channel in operation conditions. The results show that the flow pattern is stable when the shaft-type channel and the straight-type channel are used as the inlet channel under pumping and generating conditions, and a low-pressure region occurs in the contraction section of the shaft-type channel. The velocity of sections of the inlet and outlet and the middle section of the impeller in the generating condition is larger than that in the pumping condition. In addition, the difference in the static pressure on the blade surface nearby the hub is large. With a change in the position of the wingspan, the difference gradually decreases from the small flow condition to the large flow condition. There is a high-entropy production rate zone in the channel contraction section and the shaft-type wall surface of the shaft-type flow channel. When the straight-type channel is used as the outlet flow channel, a high-entropy production region appears near the inlet water surface. In the pumping condition, a high-entropy production area is found at the inlet of the impeller, the blade groove channel, and the inlet of the guide vane. In the generating condition, a high-entropy production area is found at the out-of-impeller outlet, the blade groove channel, and the outlet of the guide vane. These research achievements have some reference value for the design of the shaft-type tubular pumping station considering tides and the study of hydraulic performance, along with the energy characteristics of the channels.

Immune strategies of silver pomfret (Pampus argenteus) infected with Nocardia seriolae at different infection stages - Youyi Zhang; Jiabao Hu; Yuanbo Li; Feirong Yuan; Kaiheng Yan; Weiwei Gu; Man Zhang; Yaya Li; Xiang Huang; Cheng Zhang; Dingyuan Zhang; Shanliang Xu; et al. (Aquaculture, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Spatiotemporally continuous PM2.5 dataset in the Mekong River Basin from 2015 to 2022 using a stacking model - Debao Chen; Xingfa Gu; Hong Guo; Tianhai Cheng; Jian Yang; Yulin Zhan; Qiming Fu (Science of The Total Environment, 2024)

Quantitative identification of the co-exposure effects of e-waste pollutants on human oxidative stress by explainable machine learning - Luhan Yang; Tao Zhang; Yanxia Gao; Dairui Li; Rui Cui; Cheng Gu; Lei Wang; Hongwen Sun (Journal of Hazardous Materials, 2024)

Upcycling of epoxy resin from waste wind turbine blades: Pyrolysis-methylation tandem reaction to methylated phenols and hexamethylbenzene - Jialiang Yang; Leilei Cheng; Jing Gu; Shaonan Tian; Jun Yang; Taoli Huhe; Haoran Yuan; Yong Chen (Journal of Cleaner Production, 2024)

Preparation and evaluation of liquorice (Glycyrrhiza uralensis) and ginger (Zingiber officinale) kombucha beverage based on antioxidant capacities, phenolic compounds and sensory qualities - Ruo-Gu Xiong; Dan-Dan Zhou; Jin Cheng; Si-Xia Wu; Adila Saimaiti; Si-Yu Huang; Qing Liu; Ao Shang; Hua-Bin Li; Sha Li (International Journal of Gastronomy and Food Science, 2024)

Experimental and mechanism study on NO formation characteristics and N chemical reaction mechanism in ammonia-coal co-firing - Ping Chen; Cheng Gong; Changhao Hua; Peipei Wang; Mingyan Gu; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2024)

Insights on the NF-κB system in polycystic ovary syndrome, attractive therapeutic targets - Wei Tan; Jie Zhang; Fangfang Dai; Dongyong Yang; Ran Gu; Lujia Tang; Hua Liu; Yan-xiang Cheng (Molecular and Cellular Biochemistry, 2024)

Recent strategies, progress, and prospects of two-dimensional metal carbides (MXenes) materials in wastewater purification: A review - Pengcheng Gu; Shengsheng Liu; Xiangmei Cheng; Sai Zhang; Chuanying Wu; Tao Wen; Xiangke Wang (Science of The Total Environment, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Degradation mechanism of antibiotics by flower-like Bi2S3 sensitized anatase/rutile TiO2 coupled with SiO2 photonic crystals - Ruizhen Liu; Huaiyuan Jiang; Ping Li; Jianfei Yin; Zhengrui Xu; Xiaoyu Chen; Jian Cheng; Shuangxi Gu; Renliang Lyu (Journal of Water Process Engineering, 2024)

Highly-branched modification of starch: An enzymatic approach to regulating its properties - Kunrong Wu; Caiming Li; Zexi Li; Zhaofeng Li; Zhengbiao Gu; Xiaofeng Ban; Yan Hong; Li Cheng; Haocun Kong (Food Hydrocolloids, 2024)

Physicochemical characterization of debranched waxy rice starches and their effect on the quality of low-fat ice cream mixtures - Yuzhen Jin; Zhengbiao Gu; Li Cheng; Caiming Li; Zhaofeng Li; Yan Hong (Food Bioscience, 2024)

Dimensional design of Fe0.9Co0.1 nano-alloys with enhanced low-frequency microwave absorption - Renchao Hu; Li Li; Xinwei Xu; Desheng Pan; Jiufeng Dong; Cheng Zhen; M. Danny Gu; Hong Wang (Chemical Engineering Journal, 2024)

Self-regulation of bed temperature field of the fixed-bed reactor unit by composite-filled oxygen carriers for chemical looping combustion of methane - Xianming Cheng; Zonghao Xu; Li Jiang; Min Zheng; Zhenhua Gu; Dong Tian; Kongzhai Li; Hua Wang (Chemical Engineering Journal, 2024)

The Transcription Factor Ets1 Influences Axonal Growth via Regulation of Lcn2 - Miao Gu; Xiaodi Li; Ronghua Wu; Xiao Cheng; Songlin Zhou; Xiaosong Gu (Molecular Neurobiology, 2024)
Transcription factors are essential for the development and regeneration of the nervous system. The current study investigated key regulatory transcription factors in rat spinal cord development via RNA sequencing. The hub gene Ets1 was highly expressed in the spinal cord during the embryonic period, and then its expression decreased during spinal cord development. Knockdown of Ets1 significantly increased the axonal growth of cultured spinal cord neurons. Luciferase reporter assays and chromatin immunoprecipitation assays indicated that Ets1 could directly bind to the Lcn2 promoter and positively regulate Lcn2 transcription. In conclusion, these findings provide the first direct evidence that Ets1 regulates axon growth by controlling Lcn2 expression, and Ets1 may be a novel therapeutic target for axon regeneration in the central nervous system.

Self-Assembled FeIII-TAML-Based Magnetic Nanostructures for Rapid and Sustainable Destruction of Bisphenol A - Ruochen Dong; Lihua Bai; Sijia Liang; Shuxia Xu; Song Gao; Hongjian Li; Ran Hong; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2024)

Genetic diversity and population structure of the near threatened fish Harpadon nehereus in the Northwest Pacific: implications for conservation - Qun Zhang; Cheng-He Sun; Xiao-Ying Huang; Yang-Liang Gu; Shu-Hui Zhang; Ye-Ling Lao; Jin-Long Huang; Hong-Wei Du (Marine Biodiversity, 2024)

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Segmentation of wheat scab fungus spores based on CRF_ResUNet++ - Dongyan Zhang; Wenhao Zhang; Tao Cheng; Yu Lei; Hongbo Qiao; Wei Guo; Xue Yang; Chunyan Gu (Computers and Electronics in Agriculture, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Emergent symmetry in quantum phase transition: From deconfined quantum critical point to gapless quantum spin liquid - Wen-Yuan Liu; Shou-Shu Gong; Wei-Qiang Chen; Zheng-Cheng Gu (Science Bulletin, 2024)

Soil deformation and failure analysis of suction caisson in marine clay under combined loading - Wenbo Tu; Yuanhang Tu; Linya Liu; Xiaoqiang Gu; Pengfei Zhang; Xinglei Cheng (Ocean Engineering, 2024)

Comparative study of the photooxidation of arsenite mediated by dissolved and mineral-associated humic acid under light irradiation - Xinghao Wang; Lirong Pu; Zhaoyue Sun; Guodong Fang; Yujun Wang; Cheng Gu; Juan Gao (Journal of Hazardous Materials, 2024)

Highly effective degradation of ibuprofen by alkaline metal-doped copper oxides via peroxymonosulfate activation: Mechanisms, degradation pathway and toxicity assessments - Meng-Wei Zheng; Cheng-Wei Lin; Pei-Hsin Chou; Chao-Lung Chiang; Yan-Gu Lin; Shou-Heng Liu (Journal of Hazardous Materials, 2024)

Suspect and nontarget screening of per- and polyfluoroalkyl substances based on ion mobility mass spectrometry and machine learning techniques - Hongxin Mu; Zhongchao Yang; Ling Chen; Cheng Gu; Hongqiang Ren; Bing Wu (Journal of Hazardous Materials, 2024)

A novel multiplex PCR based method for the detection of Listeria monocytogenes clonal complex 8 - Jianheng Cheng; Shi Wu; Qinghua Ye; Qihui Gu; Ying Zhang; Qinglei Ye; Ruoqin Lin; Xinwen Liang; Zihao Liu; Jianling Bai; Jumei Zhang; Moutong Chen; et al. (International Journal of Food Microbiology, 2024)

Changes in microcystin concentration in Lake Taihu, 13 years (2007–2020) after the 2007 drinking water crisis - Kaiye Zhang; Yurong Gu; Chen Cheng; Qingju Xue; Liqiang Xie (Environmental Research, 2024)

Optimizing nitrogen application rate by establishing a unified critical nitrogen dilution curve for maize under different mulching planting patterns - Wenlong Li; Xiaobo Gu; Heng Fang; Tongtong Zhao; Rui Yin; Zhikai Cheng; Chuandong Tan; Zhihui Zhou; Yadan Du (European Journal of Agronomy, 2024)

Chemical recycling of plastic wastes via homogeneous catalysis: A review - Xueru Chen; Leilei Cheng; Jing Gu; Haoran Yuan; Yong Chen (Chemical Engineering Journal, 2024)

Fluorine modification regulation of D-A ambipolar conducting polymers towards high-performance energy storage device - Weiwei Hou; Shenglian Yao; Yusheng Chen; Dianyu Tang; Yijing Gao; Xiangyu Zhang; Ling Zhang; Zhenliang Zhang; Mi Ouyang; Junlei Liu; Lin Gu; Cheng Zhang (Chemical Engineering Journal, 2024)

Versatile closed-cell SiC/C foam for microwave absorption under medium temperature, icing and mechanical conditions - Yansong Gu; Jiaqi Tao; Jun Liu; Lvtong Duan; Haoshan Jin; Cheng Luo; Guiyu Peng; Zhengjun Yao; Jintang Zhou (Chemical Engineering Journal, 2024)

Intensified denitrification in a fluidized-bed reactor with suspended sulfur autotrophic microbial fillers - Zhenao Gu; Zheying Liu; Yu Cheng; Zongqiang Zhu; Jiayu Tian; Chengzhi Hu; Jiuhui Qu (Bioresource Technology, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

An automatic progressive chromosome segmentation approach using deep learning with traditional image processing - Ling Chang; Kaijie Wu; Hao Cheng; Chaocheng Gu; Yudi Zhao; Cailian Chen (Medical & Biological Engineering & Computing, 2024)

Proposal to Reclassify Companilactobacillus futsaii subsp. chongqingensis as a Later Heterotypic Synonym of Companilactobacillus futsaii subsp. futsaii - Cheng-Shan Jiang; Chun Tao Gu (Current Microbiology, 2024)

Content analysis and drug safety evaluation of four furanocoumarins in six pomelos produced in China - Weiling Chen; Zeqi Li; Yujiao Cheng; Guijie Li; Jiaqi Li; Linhua Huang; Qiuming Gu; Houjiu Wu (Natural Product Research, 2023)

Early-life exposure to lead changes cardiac development and compromises long-term cardiac function - Qian Liu; Cheng Xu; Jing Jin; Wenxiang Li; Jingjia Liang; Shijie Zhou; Zhenkun Weng; Yong Zhou; Xudong Liao; Aihua Gu (Science of The Total Environment, 2023)

Silver metallization-triggered liposome-embedded AIE fluorophore for dual-mode detection of biogenic amines to fight food freshness fraud - Xiang Gao; Peng Nie; Peiran Li; Zhi Zheng; Jieshun Cheng; Ying Gu; Yizhong Shen (Food Chemistry, 2023)

New insights of crude oil biodegradation construction by microbial consortium B10: Responded substrates, genomics, biodegradation mechanism and pathways - Fang Tang; Hang Zhang; Hao Cheng; Yaru Wang; Qiyou Liu; Chaocheng Zhao; Yingying Gu; Jiguo Wang (Chemical Engineering Journal, 2023)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

Pathological observation and transcriptomic analysis of thymus injury in PRRSV-infected piglets - Naying Su; Zhengdan Lin; Xi Liu; Xiuxiu Sun; Xinxin Jin; Helong Feng; Cunlin Zhan; Xueying Hu; Changqin Gu; Wanpo Zhang; Guofu Cheng (Veterinary Research Communications, 2023)
The thymus, the central immune organ in mammals, plays an important role in immune defense. Porcine reproductive and respiratory syndrome virus (PRRSV) infection in piglets can cause thymus injury and immunosuppression. However, the mechanisms of thymus injury remain unknown. This study was aimed at investigating the specific manifestations of thymus injury through the construction of a PRRSV-infected piglet model and histopathological observation. In this study, fourteen 40-day-old PRRSV-free piglets were randomly divided into two groups, eleven of which were intramuscularly injected with 3 mL of PRRSV WUH3 virus suspension (10 6 PFU /mL) in the infection group, and three of which were sham-inoculated with 3 mL of RPMI-1640 medium in the control group. Clinical necropsy and samples collection were performed on day 8 after artificial infection. With the Illumina platform, the transcriptomes of piglet thymus tissues from infected and control piglets were sequenced to explore the relationships of differentially expressed genes (DEGs) and signaling pathways with thymus injury. The immune organs of PRRSV-infected piglets were severely damaged. The histopathological findings in the thymus indicated that PRRSV infection was associated with a large decrease in lymphocytes, cell necrosis and cell apoptosis; an increase in blood vessels and macrophages; thymic corpuscle hyperplasia; and interstitial widening of the thymic lobules. The transcriptomic analysis results revealed that the Gene Ontology functions of DEGs were enriched primarily in biological processes such as angiogenesis, regulation of angiogenesis and positive regulation of cell migration. Moreover, greater numbers of blood vessels and macrophages were observed in the thymus in PRRSV-infected than control piglets. KEGG pathway enrichment analysis revealed that the DEGs were significantly enriched in the Toll-like receptor signaling pathway, chemokine signaling pathway, IL-17 signaling pathway and TNF signaling pathway. The expression of TLR8, IRF5, the chemokines CCL2, CCL3L1 and CCL5; and their receptors CCR1, CCR2 and CCR5 was significantly up-regulated in PRRSV infection, thus suggesting that these cytokines were associated with the pathological processes of thymus injury.

Centrifuge modeling and numerical analysis of reservoir bank landslides triggered by a fast two-step drop in water level - Chaojun Jia; Fanlei Chen; Qiang Zhang; Jianyong GU; Jing Hu; Hongjie Chen; Wei Cheng (Bulletin of Engineering Geology and the Environment, 2023)

Altered connectivity in the cognitive control-related prefrontal cortex in Parkinson’s disease with rapid eye movement sleep behavior disorder - Jinjing Liu; Xiaoya Zou; Jinming Gu; Qian Yu; Zhaoying Dong; Hongzhou Zuo; Xiaocui Chen; Xinyi Du; Dezhi Zou; Yu Han; Juan Peng; Oumei Cheng (Brain Imaging and Behavior, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Inhalation Lenalidomide-Loaded Liposome for Bleomycin-Induced Pulmonary Fibrosis Improvement - Zhilin Luo; Liyuan Ji; Hongting Liu; Yao Sun; Conglu Zhao; Xiang Xu; Xiaoting Gu; Xiaoyu Ai; Cheng Yang (AAPS PharmSciTech, 2023)

Effect of common low-molecular-weight organic acid on the photodegradation of sertraline by ferrihydrite - Ziyan Zhou; Dingding Wu; Hao Wu; Boming Fu; Xinhao Wang; Jingyi Ling; Xin Jin; Cheng Gu (Chemosphere, 2023)

Selective oxidation of organic pollutants based on reactive oxygen species and the molecular structure: Degradation behavior and mechanism analysis - Ming Zhang; Jingqi Ruan; Xinhao Wang; Weizhen Shao; Zhonglin Chen; Zhanghao Chen; Cheng Gu; Weichuan Qiao; Jiansheng Li (Water Research, 2023)

Carnosol analogue WK-63 alleviated cancer cachexia by inhibiting NF-κB and activating AKT pathways in muscle while inhibiting NF-κB and AMPK pathways in adipocyte - Xiaojuan Pan; Gang Zhang; Kun Wei; Xiaofan Gu; Jiahuan Dan; Yun Zhao; Xuan Liu; Chunru Cheng; Xiongwen Zhang (Toxicology and Applied Pharmacology, 2023)

Cadmium promotes colorectal cancer metastasis through EGFR/Akt/mTOR signaling cascade and dynamics - Mayu Sun; Zheshun Jiang; Pengfei Gu; Bao Guo; Jingquan Li; Shujun Cheng; Qian Ba; Hui Wang (Science of The Total Environment, 2023)

Projecting future labor losses due to heat stress in China under climate change scenarios - Liangliang Cheng; Kuiying Gu; Liang Zhao; Huibin Wang; John S. Ji; Zhao Liu; Jianbin Huang; Yidan Chen; Xuejie Gao; Ying Xu; Can Wang; Yong Luo; et al. (Science Bulletin, 2023)

Low concentration chlorantraniliprole-promoted Ca2+ release drives a shift from autophagy to apoptosis in the silk gland of Bombyx mori - Haoyi Gu; Qilong Shu; Minli Dai; Hongbin Zou; Yuanfei Wang; Jialu Cheng; Yue Su; Fanchi Li; Bing Li (Pesticide Biochemistry and Physiology, 2023)

Analysis of bucket foundation installation in clay considering soil large deformation - Wenbo Tu; Yufan He; M. Hesham El Naggar; Linya Liu; Xiaoqiang Gu; Xinglei Cheng (Ocean Engineering, 2023)

Quantitative proteomic analysis of cattle-yak and yak longissimus thoracis provides insights into the differential mechanisms of meat quality - Xinping Chang; Yisha Xu; Lei Cheng; Kaige Yi; Xuedong Gu; Zhang Luo; Jiamin Zhang; Jinqiu Wang; Fang Geng (Food Research International, 2023)

Cyclodextrin glycosyltransferase-catalyzed products from starch enhance the stability of microencapsulated cinnamaldehyde emulsion - Shuangdi Chen; Zhaofeng Li; Zhengbiao Gu; Xiaofeng Ban; Yan Hong; Li Cheng; Caiming Li (Food Hydrocolloids, 2023)

Mechanical energy-driven triboelectric plasma catalytic CO2 reduction over oxygen-vacancy-introduced In2O3 nanoparticles - Xiaochen Xiang; Jiao Wang; Qinglong Ru; Sumin Li; Ke Zhao; Yifei Zhu; Zhenpan Chen; Liangliang Liu; Guangqin Gu; Yu Jia; Bao Zhang; Gang Cheng; et al. (Chemical Engineering Journal, 2023)

SO42− immobilization regulated by reaction atmosphere over ABS poisoned α-Fe2O3 catalysts for efficient NOx removal - Zhiwen Gu; Chong Tan; Baiyun Zhu; Songil Sin; Jiawei Ji; Yan Wang; Lijun Cheng; Wang Song; Chunkai Huang; Meilin Tao; Changjin Tang (Chemical Engineering Journal, 2023)

Promoting oxygen reduction kinetics of single Fe sites for robust neutral Zn-air batteries via engineering synergistic Fe nanocluster as proton-feeding center - Ren Xu; Xingkun Wang; Mingzi Sun; Canhui Zhang; Cheng Li; Zhengwen Cao; Meng Gu; Bolong Huang; Minghua Huang (Chemical Engineering Journal, 2023)

Effects of microplastics on denitrification and associated N2O emission in estuarine and coastal sediments: insights from interactions between sulfate reducers and denitrifiers - Cheng Chen; Guoyu Yin; Qiuxuan Li; Youran Gu; Dongyao Sun; Soonmo An; Xia Liang; Xiaofei Li; Yanling Zheng; Lijun Hou; Min Liu (Water Research, 2023)

Targeted isolation of ursane-type triterpenoids from Tragopogon porrifolius based on Feature-Based Molecular Networking - Hong-bing Sun; Hai-fei Zou; Bing Xia; Yu-cheng Gu; Wen-lin Wu; Yan Zhou (Phytochemistry Letters, 2023)

Role and mechanism of WNT5A in benzo(a)pyrene-induced acute lung injury and lung function decline - Lieyang Fan; Bin Wang; Jixuan Ma; Zi Ye; Xiuquan Nie; Man Cheng; Yujia Xie; Pei Gu; Yingdie Zhang; Xiaojie You; Yun Zhou; Weihong Chen (Journal of Hazardous Materials, 2023)

Dissolved black carbon incorporating with ferric minerals promoted photo-Fenton-like degradation of triclosan in acidic conditions - Ziyan Zhou; Hao Wu; Boming Fu; Zhe Wang; Ran Hong; Liuqing Huang; Xinyue Gu; Cheng Gu; Xin Jin (Journal of Hazardous Materials, 2023)

An energetic MOF-assistant confined expansion strategy to fabricate Fe-doped porous carbon beads for advanced oxidation processes: Interfacial reaction mechanism and biological toxicity - Weizhen Shao; Ming Zhang; Zhonglin Chen; Jingqi Ruan; Zhanghao Chen; Wuxiang Zhang; Cheng Gu; Weichuan Qiao (Journal of Environmental Chemical Engineering, 2023)

Extended construction strategies of Ag3PO4-based heterojunction photocatalysts for robust environmental applications - Cheng Zhang; Chuchu Feng; Junwei Yuan; Zhiyun Wang; Yanan Wang; Shiyuan Zhou; Peiyang Gu; Yang Li (Journal of Environmental Chemical Engineering, 2023)

Insight from untargeted metabolomics: Revealing the potential marker compounds changes in refrigerated pork based on random forests machine learning algorithm - Minghui Gu; Cheng Li; Li Chen; Shaobo Li; Naiyu Xiao; Dequan Zhang; Xiaochun Zheng (Food Chemistry, 2023)

Colon targeted releases and uptakes of paclitaxel loaded in modified porous starch - Beibei Zhao; Zhengbiao Gu; Zhaofeng Li; Li Cheng; Caiming Li; Yan Hong (Carbohydrate Polymers, 2023)

Impacts of fatty acid type on binding state, fine structure, and in vitro digestion of debranched starch-fatty acid complexes with different debranching degrees - Shenglin Sun; Yan Hong; Zhengbiao Gu; Li Cheng; Xiaofeng Ban; Zhaofeng Li; Caiming Li (Carbohydrate Polymers, 2023)

Burial or mineralization: Origins and fates of organic matter in the water–suspended particulate matter–sediment of macrophyte- and algae-dominated areas in Lake Taihu - Cheng Liu; Qiushi Shen; Xiaozhi Gu; Lei Zhang; Chao Han; Zhaode Wang (Water Research, 2023)

Spin state modulation on dual Fe center by adjacent Ni sites enabling the boosted activities and ultra-long stability in Zn-air batteries - Canhui Zhang; Xingkun Wang; Zhentao Ma; Hanxu Yao; Hengjun Liu; Cheng Li; Jian Zhou; Ren Xu; Xusheng Zheng; Huanlei Wang; Qiang Li; Meng Gu; et al. (Science Bulletin, 2023)

Parallel paired electrolysis-enabled asymmetric catalysis: simultaneous synthesis of aldehydes/aryl bromides and chiral alcohols - Bing Sun; Zhen-Hua Wang; Yun-Zhao Wang; Yu-Cheng Gu; Cong Ma; Tian-Sheng Mei (Science Bulletin, 2023)

PbrWRKY70 increases pear (Pyrus bretschneideri Rehd) black spot disease tolerance by negatively regulating ethylene synthesis via PbrERF1B-2 - Caihua Xing; Qiming Chen; Qinghai Qiao; Shenao Gu; Xiangyu Cheng; Huizhen Dong; Likun Lin; Feng Zhang; Chenyang Han; Zan Zhang; Hao Yin; Kaijie Qi; et al. (Plant Science, 2023)

The vertically-stratified resistomes in mangrove sediments was driven by the bacterial diversity - Jiaxiong Zeng; Yu Pan; Ruiwen Hu; Fei Liu; Hang Gu; Jijuan Ding; Songfeng Liu; Shengwei Liu; Xueqin Yang; Yisheng Peng; Yun Tian; Qiang He; et al. (Journal of Hazardous Materials, 2023)

Destabilization of oil-in-water emulsions: Influences of interfacial assembly of octenyl succinic anhydride starch and chitosan - Tian Xu; Zhengbiao Gu; Li Cheng; Caiming Li; Zhaofeng Li; Yan Hong (Food Hydrocolloids, 2023)

Spillover effects of urbanization on carbon emissions: A global view from 2000 to 2019 - Wanxu Chen; Guanzheng Wang; Liyan Yang; Cheng Huang; Ning Xu; Tianci Gu; Jie Zeng (Environmental Impact Assessment Review, 2023)

A three-dimensional folded multistage distillation device with enhanced air convection for efficient solar interface evaporation - Yihang Li; Shaoan Cheng; Beichen Jin; Zhen Yu; Ruonan Gu (Desalination, 2023)

Synergistic strategy based on mild phototherapy and deep tumor hypoxia reversal comprehensively remodels the tumor microenvironment for improved immunotherapy - Linlin Tao; Gang Cheng; Fangnan Lv; Ruiqi Wang; Nan Yang; Zuhang Xing; Boyu Gu; Siyuan Meng; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2023)

Endowing V6O13/CeVO4 heterojunction with substantial improvements on zinc ion storage performance - Jingyun Cheng; Shuai Nan; Shuang Yu; Kaitao Liu; Huaiqiang Gu; Lei Tan; Zhulin Niu; Dan Li; Hongqiang Wang (Chemical Engineering Journal, 2023)

High- and low-temperature resistant and intrinsically flame retardant poly(bisphthalazinone thioether sulfone ketone)s: Synthesis, structures and properties - Hongjian Gu; Cheng Liu; Qian Liu; Hang Jia; Yue Qiao; Wenqi Zhao; Yousi Chen; Xigao Jian (Chemical Engineering Journal, 2023)

Influence of adaptive inverse distance weighting method under membership function mapping on the interpolation accuracy of geological boreholes - Huan Liu; Weitao Li; Weibo Zeng; Ling Bao; Yuqing Mei; Jing Guo; Lei Cheng; Shuangxi Gu (Earth Science Informatics, 2023)

A review of controlled release from cyclodextrins: release methods, release systems and application - Yan Feng; Shuangdi Chen; Zhaofeng Li; Zhengbiao Gu; Shude Xu; Xiaofeng Ban; Yan Hong; Li Cheng; Caiming Li (Critical Reviews in Food Science and Nutrition, 2023)

Enhancing wheat Fusarium head blight detection using rotation Yolo wheat detection network and simple spatial attention network - Dong-Yan Zhang; Han-Sen Luo; Tao Cheng; Wei-Feng Li; Xin-Gen Zhou; Wei-Guo; Chun-Yan Gu; Zhihua Diao (Computers and Electronics in Agriculture, 2023)

New insights into the protection of dietary components on anxiety, depression, and other mental disorders caused by contaminants and food additives - Ruo-Gu Xiong; Jiahui Li; Jin Cheng; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan; Yibin Feng (Trends in Food Science & Technology, 2023)

Combined effect of heating and enzymatic hydrolysis on the dispersibility and structure properties of egg white powder - Tingting Wang; Cuihua Chang; Wanying Cheng; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Journal of Food Engineering, 2023)

Different starch varieties influence the complexing state and digestibility of the resulting starch-lipid complexes - Shenglin Sun; Yan Hong; Zhengbiao Gu; Li Cheng; Xiaofeng Ban; Zhaofeng Li; Caiming Li (Food Hydrocolloids, 2023)

Infection dynamic of Micropterus salmoides rhabdovirus and response analysis of largemouth bass after immersion infection - Shunfa Yi; Youjun Wu; Xie Gu; Yan Cheng; Zesheng Zhang; Zhenzhen Yuan; Hongbao Xie; Shichao Qian; Mengmeng Huang; Hui Fei; Shun Yang (Fish & Shellfish Immunology, 2023)

Transcriptome analysis of response mechanism to Microcystin-LR and microplastics stress in Asian clam (Corbicula fluminea) - Jiahua Zhang; Wang Jie; Guofeng Cheng; Zhaojun Gu; Xingguo Liu (Fish & Shellfish Immunology, 2023)

Thulium-Doped Fiber Laser and Its Application in Urinary Lithotripsy - Runyan Gu; Zhilong Li; Cheng Lei; Sheng Li; Du Wang; Xinghuan Wang (Journal of Medical and Biological Engineering, 2023)

Exploring the Potential of GPT-4 in Biomedical Engineering: The Dawn of a New Era - Kunming Cheng; Qiang Guo; Yongbin He; Yanqiu Lu; Shuqin Gu; Haiyang Wu (Annals of Biomedical Engineering, 2023)

Bacterial community assembly and antibiotic resistance genes in soils exposed to antibiotics at environmentally relevant concentrations - Zeyou Chen; Wei Zhang; Anping Peng; Yike Shen; Xin Jin; Robert D. Stedtfeld; Stephen A. Boyd; Brian J. Teppen; James M. Tiedje; Cheng Gu; Dongqiang Zhu; Yi Luo; et al. (Environmental Microbiology, 2023)
Understanding how bacterial community assembly and antibiotic resistance genes (ARGs) respond to antibiotic exposure is essential to deciphering the ecological risk of anthropogenic antibiotic pollution in soils. In this study, three loam soils with different land management (unmanured golf course, dairy‐manured pasture, and swine‐manured cornfield) were spiked with a mixture of 11 antibiotics at the initial concentration of 100 and 1000 μg kg −1 for each antibiotic and incubated over 132 days, mimicking a scenario of pulse disturbance and recovery in soils, with unspiked soil samples as the control treatment. The Infer Community Assembly Mechanisms by Phylogenetic‐bin‐based null model (iCAMP) analysis demonstrated that drift and dispersal limitation contributed to 57%–65% and 16%–25%, and homogeneous selection 12%–16% of soil bacterial community assembly. Interestingly, antibiotic exposure to 1000 μg kg −1 level significantly increased the contribution of drift to community assembly, largely due to the positive response from Acidobacteria‐6 in the golf course and pasture soils and from Chthoniobacteraceae in the cornfield soil to the antibiotic exposure. However, ARG abundance and diversity in the three soils exhibited antibiotics‐independent temporal fluctuations, but were associated with the changes in soil bacterial communities over time. This study provides the first insight into the relative contributions of different bacterial community assembly processes in soils upon antibiotic exposure at environmentally relevant concentrations.

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Dry-to-wet fluctuation of moisture contents enhanced the mineralization of chloramphenicol antibiotic - Shuhan Huang; Qilin Wang; Zhenhui Fan; Min Xu; Rong Ji; Xin Jin; Cheng Gu (Water Research, 2023)

Heavy metal(loid)s in agriculture soils, rice, and wheat across China: Status assessment and spatiotemporal analysis - Cheng-Chen Wang; Qiao-Chu Zhang; Chang-An Yan; Guo-Yong Tang; Meng-Yan Zhang; Lena Q. Ma; Rong-Hui Gu; Ping Xiang (Science of The Total Environment, 2023)

Spatiotemporal characteristics of ozone and the formation sensitivity over the Fenwei Plain - H.H. Ren; Y. Cheng; F. Wu; Z.L. Gu; J.J. Cao; Y. Huang; Y.G. Xue; L. Cui; Y.W. Zhang; J.C. Chow; J.G. Watson; R.J. Zhang; et al. (Science of The Total Environment, 2023)

Big-sized trees and higher species diversity improve water holding capacities of forests in northeast China - Yanbo Yang; Lixin Jing; Qi Li; Chentao Liang; Quanxing Dong; Shuting Zhao; Yuwen Chen; Danqi She; Xu Zhang; Lei Wang; Guanchao Cheng; Xiting Zhang; et al. (Science of The Total Environment, 2023)

Abrupt warming of the equatorial intermediate Pacific during Heinrich Stadial 1 - Shuai Zhang; Tiegang Li; Zhoufei Yu; Fengming Chang; Sifan Gu; Zhifang Xiong; Heng Liu; Fang Qian; Junru Zhang; Xuhua Cheng; Baohua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Spatial-Transformer and Cross-Scale Fusion Network (STCS-Net) for Small Object Detection in Remote Sensing Images - Jinhui Lan; Cheng Zhang; Weijian Lu; Naiwei Gu (Journal of the Indian Society of Remote Sensing, 2023)

The structure of biodegradable surfactants shaped the microbial community, antimicrobial resistance, and potential for horizontal gene transfer - Chen-Wei Zheng; Yi-Hao Luo; Xiangxing Long; Haiwei Gu; Jie Cheng; Lei Zhang; Yen Jung Sean Lai; Bruce E. Rittmann (Water Research, 2023)

Photochemical degradation of perfluorooctanoic acid under UV irradiation in the presence of Fe (III)-saturated montmorillonite - Yutong Zhang; Xinhao Wang; Yichen Xu; Liuqing Huang; Wenran Wang; Cheng Gu; Ming Zhang; Zhanghao Chen (Science of The Total Environment, 2023)

The tanshinones from the plant of Salvia miltiorrhiza - Jian-Shuang Jiang; Quan-chang Gu; Zi-Ming Feng; Xiang Yuan; Xu Zhang; Pei-Cheng Zhang; Ya-Nan Yang (Phytochemistry, 2023)

Field, plant, to leaf: A meta-analysis on crop water use efficiency response to potassium fertilization - Cheng Yang; Wanyang Zhang; Hehe Gu; Aihua Liu; Qi Guo; Yizhou Chen; Jianwei Lu; Tao Ren; Rihuan Cong; Zhifeng Lu; Yangyang Zhang; Shipeng Liao; et al. (Journal of Hydrology, 2023)

Selective catalytic reduction of NO with NH3 over MnOx-CeO2 catalysts: The great synergy between CeO2 and crystalline phase of Mn3O4 - Lijun Cheng; Songil Sin; Jiawei Ji; Shan Yang; Chong Tan; Zhiwen Gu; Wang Song; Chunkai Huang; Chuanzhi Sun; Changjin Tang; Lin Dong (Fuel, 2023)

Mechanism analysis of fuel-N oxidation during ammonia-coal co-combustion: Influence of H2O - Ping Chen; Cheng Gong; Changhao Hua; Mingyan Gu; Boyu Jiang; Jianren Fan; Yi Wang (Fuel, 2023)

Bioactive compounds and health benefits of pomegranate: An updated narrative review - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Yibin Feng; Ren-You Gan; Hua-Bin Li (Food Bioscience, 2023)

Effect of water saturation on dynamic behavior of sandstone after wetting-drying cycles - Hongru Li; Yafei Qiao; Manchao He; Rongxi Shen; Zhoujie Gu; Tai Cheng; Yingming Xiao; Jie Tang (Engineering Geology, 2023)

Poly(L-lactic acid)/graphene composite films with asymmetric sandwich structure for thermal management and electromagnetic interference shielding - Ting Gu; Zhu Zeng; Shuang Wu; De-xiang Sun; Cheng-shou Zhao; Yong Wang (Chemical Engineering Journal, 2023)

Loss of ndrg2 Function Is Involved in Notch Activation in Neuromast Hair Cell Regeneration in Zebrafish - Xin Wang; Xiaodong Gu; Cheng Wang; Yingzi He; Dong Liu; Shan Sun; Huawei Li (Molecular Neurobiology, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Japanese encephalitis virus induces apoptosis by activating the RIG-1 signaling pathway - Mingxing Gao; Zelin Liu; Xiaoyan Guo; Jinhua Zhang; Guofu Cheng; Xueying Hu; Wanpo Zhang; Changqin Gu (Archives of Virology, 2023)

Potential Use of Artificial Intelligence in Infectious Disease: Take ChatGPT as an Example - Kunming Cheng; Zhiyong Li; Yongbin He; Qiang Guo; Yanqiu Lu; Shuqin Gu; Haiyang Wu (Annals of Biomedical Engineering, 2023)

An extensive review: How starch and gluten impact dough machinability and resultant bread qualities - Xiaohui Hu; Li Cheng; Yan Hong; Zhaofeng Li; Caiming Li; Zhengbiao Gu (Critical Reviews in Food Science and Nutrition, 2023)

Bamboo-based magnetic activated carbon for efficient removal of sulfadiazine: Application and adsorption mechanism - Fan Yang; Can Jin; Sen Wang; Yujie Wang; Lu Wei; Longhui Zheng; Haiping Gu; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Chemosphere, 2023)

Estimating leaf nitrogen and chlorophyll content in wheat by correcting canopy structure effect through multi-angular remote sensing - Yuanyuan Pan; Wenxuan Wu; Jiawen Zhang; Yuejiao Zhao; Jiayi Zhang; Yangyang Gu; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Computers and Electronics in Agriculture, 2023)

Novel insights from protein degradation: Deciphering the dynamic evolution of biogenic amines as a quality indicator in pork during storage - Minghui Gu; Cheng Li; Yuanyuan Su; Li Chen; Shaobo Li; Xin Li; Xiaochun Zheng; Dequan Zhang (Food Research International, 2023)

Influence of degree of substitution of octenyl succinic anhydride starch on complexation with chitosan and complex-stabilized high internal phase Pickering emulsions - Tian Xu; Zhengbiao Gu; Li Cheng; Caiming Li; Zhaofeng Li; Yan Hong (Food Hydrocolloids, 2023)

Autochthonous bioaugmentation accelerates phenanthrene degradation in acclimated soil - Haiping Gu; Jie Yan; Yuhao Liu; Xuewei Yu; Yan Feng; Xuanyi Yang; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Environmental Research, 2023)

LncRNA PVT1 influences breast cancer cells glycolysis through sponging miR-145-5p - Huan Qu; Xingxing Li; Fei Chen; Min Zhang; Xun Lu; Yun Gu; Mingming Lv; Cheng Lu (Genes & Genomics, 2023)
Background Long-non-coding RNA PVT1 (lncRNA PVT1) can be used as an oncogenic regulatory non-coding RNA (ncRNA) for many cancers. However, its function and mechanism in breast cancer (BRCA) are still not clearly elucidated. Objective We attempt to explain the mechanism of PVT1’s role in breast cancer from different perspectives. Methods We analyzed the expression of PVT1 and its correlation with the breast cancer related clinical data in the The Cancer Genome Atlas (TCGA) database. We used PVT1 overexpression and knockdown lentivirus to infect breast cancer MDA-MB-231 cell line for cell function verification, in vitro using CCK-8 to measure proliferation, flow cytometry to measure apoptosis, transwell test to measure invasion and migration ability, detecting cell extracellular acidification rate (ECAR) to assess glycolysis metabolism and explore the biological functions of PVT1 in breast cancer cells. Transcriptome sequencing was used to analyze the changes of related genes in cells after overexpression of PVT1. In vivo we used a xenograft model to study the effect of PVT1 on breast cancer. Results PVT1 was up-regulated in breast cancer tissues and was positively correlated with the clinical stage of breast cancer patients. Overexpression of PVT1 in vitro promoted cell proliferation, migration and invasion, and promoted tumor growth in vivo. Knockdown of PVT1 led to the opposite biological consequence. Further bioinformatics analysis showed that PVT1 changes the glycolysis metabolism of tumors through regulation of glycolysis-related genes. In addition, the expression of miR-145-5p is negatively correlated with PVT1. We consider the possibility of PVT1 promoting cell proliferation and metastasis by regulating the aerobic glucose metabolism in breast cancer cells through sponging the miR-145-5p. Conclusion Our results reveal a potential pathway for competing endogenous RNA to regulate breast cancer glucose metabolism. PVT1 regulates glycolysis related genes expression by competitively binding to endogenous miR-145-5p in breast cancer cells to change the metabolic phenotype. This may Provide new ideas for precise molecular therapy targets for breast cancer.

A one-pot CRISPR-Cas12a-based toolbox enables determination of terminal deoxynucleotidyl transferase activity for acute leukemia screening - Ming Yi; Yao Gong; Qian Zhan; Yulian Dai; Tiantian Yang; Xiaoxue Cheng; Shijia Ding; Bing Gu; Wei Cheng; Decai Zhang (Analytica Chimica Acta, 2023)

Talk with ChatGPT About the Outbreak of Mpox in 2022: Reflections and Suggestions from AI Dimensions - Kunming Cheng; Yongbin He; Cheng Li; Ruijie Xie; Yanqiu Lu; Shuqin Gu; Haiyang Wu (Annals of Biomedical Engineering, 2023)

Novel insights into the predominant factors affecting the bioavailability of polycyclic aromatic hydrocarbons in industrial contaminated areas using PLS-developed model - Zhihua Jin; Chenggang Gu; Xiuli Fan; Jun Cai; Yongrong Bian; Yang Song; Cheng Sun; Xin Jiang (Chemosphere, 2023)

Mechanistic insights into surface catalytic oxidation of fluoroquinolone antibiotics on sediment mackinawite - Xiru Chen; Zeyu Xian; Song Gao; Lihua Bai; Sijia Liang; Haoting Tian; Chao Wang; Cheng Gu (Water Research, 2023)

TMAO promotes dementia progression by mediating the PI3K/Akt/mTOR pathway - Xiaojuan Hu; Yamin Zhang; Cheng Gu; Ruipeng Wu; Yuping Yao; Fulin Gao; Lulu Luo; Yi Zhang (Tissue and Cell, 2023)

Sluggish lithium isotopic response of continental intraplate basalts to recycled sedimentary carbonate - Yang-Yang Wang; Cheng-Long Yu; Dong-Bo Tan; He Sun; Hai-Ou Gu; Fengtai Tong; Li-Hui Chen; Yilin Xiao (Lithos, 2023)

Performance characteristics and bacterial community analysis of a novel two-step-feed three-stage A/O-MBBR system for nitrogen removal in municipal wastewater - Xiaolin Zhou; Zijian Jiang; Jinzhao Gu; Xuejun Bi; Jingmiao Liu; Xuyi Wang; Tang Yang; Xueqing Shi; Lihua Cheng; Shujuan Huang; Xiaodong Wang; Harsha Ratnaweera; et al. (Journal of Water Process Engineering, 2023)

Emphasizing egalitarianism in the allocation of China's provincial carbon emission allowances - Yonglong Cheng; Xianchun Tan; Baihe Gu; Chen Huang; Hongshuo Yan; Miaomiao Niu (Journal of Cleaner Production, 2023)

Comparative evaluation and prioritization of key influences on biodegradation of 2,2′,4,4′-tetrabrominated diphenyl ether by bacterial isolate B. xenovorans LB400 - Chenggang Gu; Zhihua Jin; Xiuli Fan; Qingqing Ti; Xinglun Yang; Cheng Sun; Xin Jiang (Journal of Environmental Management, 2023)

The N-terminus of 1,4-α-glucan branching enzyme plays an important role in its non-classical secretion in Bacillus subtilis - Tao Xu; Zhaofeng Li; Zhengbiao Gu; Caiming Li; Li Cheng; Yan Hong; Xiaofeng Ban (Food Bioscience, 2023)

Different reoxygenation rates induce different metabolic, apoptotic and immune responses in Golden Pompano (Trachinotus blochii) after hypoxic stress - Tian Jiang; Ye Song Liang; Yue Gu; Fu Cheng Yao; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Jun Long Sun; Jian Luo (Fish & Shellfish Immunology, 2023)

Aggregation-induced color fine-tunable carbon dot phosphorescence covering from green to near-infrared for advanced information encryption - Qijun Li; Dengke Cheng; Hailing Gu; Daiqi Yang; Yuchen Li; Shuai Meng; Yunyang Zhao; Zikang Tang; YiBo Zhang; Jing Tan; Songnan Qu (Chemical Engineering Journal, 2023)

Stability, oxidizability, and topical delivery of resveratrol encapsulated in octenyl succinic anhydride starch/chitosan complex-stabilized high internal phase Pickering emulsions - Tian Xu; Zhengbiao Gu; Li Cheng; Caiming Li; Zhaofeng Li; Yan Hong (Carbohydrate Polymers, 2023)

Truncated glycoprotein E of varicella-zoster virus is an ideal immunogen for Escherichia coli-based vaccine design - Tingting Chen; Jie Sun; Sibo Zhang; Tingting Li; Liqin Liu; Wenhui Xue; Lizhi Zhou; Siting Liang; Zhili Yu; Qingbing Zheng; Hai Yu; Tong Cheng; et al. (Science China Life Sciences, 2023)

Exosomes from Inflamed Macrophages Promote the Progression of Parkinson’s Disease by Inducing Neuroinflammation - Yan Jin; Runze Wu; Li Li; Lihua Shen; Yunjuan Gu; Cheng Sun (Molecular Neurobiology, 2023)

Three-dimensional modeling of fault geological structure using generalized triangular prism element reconstruction - Huan Liu; Weitao Li; Shuangxi Gu; Lei Cheng; Yanxia Wang; Jianhui Xu (Bulletin of Engineering Geology and the Environment, 2023)

Stability analysis of gravity anchor foundation of layered argillaceous sandstone under dry-wet cycles - Jing-cheng Zheng; Wei Chen; Ke-ren Zheng; Yu-peng Gu; Fei Wang; Zhen Huang; Yun Li (Journal of Mountain Science, 2023)

Effect of PVC microplastics on soil microbial community and nitrogen availability under laboratory-controlled and field-relevant temperatures - Hangru Shen; Yuhan Sun; Hongbing Duan; Jinliu Ye; Aoyu Zhou; Han Meng; Fengxiao Zhu; Huan He; Cheng Gu (Applied Soil Ecology, 2023)

As3MT is related to relative RNAs and base modifications of p53 in workers exposed to arsenic - Weihua Wen; Shun Zha; Huirong Cheng; Jun Qi; Qian Chen; Yun Gu (Environmental Science and Pollution Research, 2023)

A molecular level understanding of antimony immobilization mechanism on goethite by the combination of X-ray absorption spectroscopy and density functional theory calculations - Qian Sun; Cun Liu; Tingting Fan; Hu Cheng; Peixin Cui; Xueyuan Gu; Lina Chen; Syed Tahir Ata-Ul-Karim; Dongmei Zhou; Yujun Wang (Science of The Total Environment, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

A large-scale proteogenomic atlas of pear - Peng Wang; Xiao Wu; Zebin Shi; Shutian Tao; Zhe Liu; Kaijie Qi; Zhihua Xie; Xin Qiao; Chao Gu; Hao Yin; Mengyu Cheng; Xiaoyu Gu; et al. (Molecular Plant, 2023)

Combination of colorimetry, inner filter effect-induced fluorometry and smartphone‑based digital image analysis: A versatile and reliable strategy for multi-mode visualization of food dyes - Shuangshou Wang; Yuwen Ding; Lu Zhang; Yingle Cheng; Ying Deng; Qin Jiang; Hongrui Gao; Jing Gu; Ganggang Yang; Lei Zhu; Tingxuan Yan; Qi Zhang; et al. (Journal of Hazardous Materials, 2023)

Insight into the key role of oxygen dopants over ball-milled boron nitride for efficient degradation of PFOS alternative 6:2 fluorotelomer sulfonic acid - Lijie Duan; Jian Wei; Jinshan Wei; Minghao Wang; Yong Wang; Xue Cheng; Mengbin Gu; Xinyi Zhang; Xianghua Wen; Yonghui Song (Journal of Hazardous Materials, 2023)

Enhanced evaporation performance of solar interface evaporator by modifying the evaporation layer surface with hydrophobic fumed silica - Yihang Li; Shaoan Cheng; Zhen Yu; Ruonan Gu; Yangxi Li; Hua Chen (Journal of Cleaner Production, 2023)

Particle size of biochar significantly regulates the chemical speciation, transformation, and ecotoxicity of cadmium in biochar - Shiguo Gu; Wei Zhang; Fei Wang; Zhanhang Meng; Yu Cheng; Zexuan Geng; Fei Lian (Environmental Pollution, 2023)

Multilevel design strategies of high-performance interfacial solar vapor generation: A state of the art review - Xiaobin Gu; Cheng Fan; Yongjun Sun (Chemical Engineering Journal, 2023)

Effects of fertilizer and weed species richness on soil nematode community in a microcosm field experiment - Xinli Niu; Yongfan Cheng; Xiaopei Feng; Feng Sun; Yanfang Gu (Soil Ecology Letters, 2023)

DGT method for the in situ measurement of triazines and the desorption kinetics of atrazine in soil - Siheng Zheng; Feng Sheng; Cheng Gu; Yanying Li; Zhou Fang; Jun Luo (Environmental Science and Pollution Research, 2023)

Growth and clearance rate of Corbicula fluminea in relation to fine sediment resuspension in eutrophic shallow lakes - You Zhang; Long Cheng; Wei Li; Yanqing Han; Jiao Gu; Kuanyi Li; Erik Jeppesen (Hydrobiologia, 2023)

Congener-specificity, dioxygenation dependency and association with enzyme binding for biodegradation of polybrominated diphenyl ethers by typical aerobic bacteria: Experimental and theoretical studies - Chenggang Gu; Lei Wang; Zhihua Jin; Xiuli Fan; Zhengyuan Gao; Xinglun Yang; Cheng Sun; Xin Jiang (Chemosphere, 2023)

Identification and characterization of diverse isomers of per- and polyfluoroalkyl substances in Chinese municipal wastewater - Hongxin Mu; Jiawei Wang; Ling Chen; Haidong Hu; Jinfeng Wang; Cheng Gu; Hongqiang Ren; Bing Wu (Water Research, 2023)

Four new Myrioneuron alkaloids from Mycetia effusa (Myrioneuron effusum) - Xiao-Hui Li; Jia-Hui Zhang; Yu Zhang; Ying-Tong Di; Yu-Cheng Gu; Mingming Cao; Xiao-Jiang Hao (Phytochemistry Letters, 2023)

Effect of endogenous proteins and heat treatment on the in vitro digestibility and physicochemical properties of corn flour - Wendong Li; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Yan Hong (Food Hydrocolloids, 2023)

Octenyl succinate anhydride debranched starch-based nanocarriers for curcumin with improved stability and antioxidant activity - Shangyun Liang; Jing Du; Yan Hong; Li Cheng; Zhengbiao Gu; Zhaofeng Li; Caiming Li (Food Hydrocolloids, 2023)

Effect of Tribute citrus essential oil nanoemulsion-loaded gelatin on the gel behavior and gelation surface morphologies - Guoqiang Li; Qingqing Zhou; Shuxun Liu; Cheng Qian; Jiarun Han; Tao Zhou; Ping Li; Qing Gu (Food Bioscience, 2023)

Enhancement mechanism of magnetite on the ball-milling destruction of perfluorooctane sulfonate by iron - Jun Hu; Yifan Qiu; Bing Gu; Nv Yao; Zimo Lou; Zhuowei Cheng; Xianzhao Zhang; Jianming Yu (Environmental Pollution, 2023)

Photoactivatable metal organic framework for synergistic ferroptosis and photodynamic therapy using 450 nm laser - Yuhang Chen; Lijiang Gu; Bohan Ma; Xing Li; Yibo Mei; Jinlai Zhou; Yue Chong; Minghai Ma; Mengzhao Zhang; Lu Wang; Yifan Cheng; Kaijie Wu; et al. (Chemical Engineering Journal, 2023)

Structure and morphology control of amorphous Mn-doped Fe oxide composite using soft-templates for efficient Sb(V) removal in textile wastewater: Mechanism of solid-liquid interface regulation and Sb(V) adsorption - Kunlun Yang; Cheng Li; Xiaorui Wang; Zengshuai Zhang; Peng Gu; Hengfeng Miao; Xinhua Xu (Chemical Engineering Journal, 2023)

A topical platelet-independent multilevel clotting initiator for intraoperative hemostasis - Fenglin Miao; Huirong Lin; Tianhong Yao; Ruyi Zhang; Xinfei Sun; Hongwei Cheng; Lingwei Gu; Xiaogang Xia; Ting Wu; Wengang Li; Gang Liu (Chemical Engineering Journal, 2023)

Mercury adsorption and reduction by nonlinear optical material (NLOM) DMABR loaded on Sepiolite: A mechanism study - Yuncheng Wang; Tingyuan Xu; En Song; Ziquan Wang; Hu Cheng; Zhiyong Ma; Yongrong Bian; Yujie Hu; Fang Wang; Yang Song; Chenggang Gu; Xinglun Yang; et al. (Chemical Engineering Journal, 2023)

National Civil Space Infrastructure Satellite Aerosol Product Validation Network (SIAVNET) measurements: Supporting satellite aerosol product validation for different surface types over China - Tianhai Cheng; Hao Zhu; Xingfa Gu; Shuaiyi Shi; Xiang Zhou; Jian Yang (Atmospheric Research, 2023)

S100A4-dependent glycolysis promotes lymphatic vessel sprouting in tumor - Anqi Li; Linyu Zhu; Ningjing Lei; Jiajia Wan; Xixi Duan; Shuangqing Liu; Yanru Cheng; Ming Wang; Zhuoyu Gu; Huilei Zhang; Yueyue Bai; Li Zhang; et al. (Angiogenesis, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Sharply and simultaneously increasing pollutant accumulations in cells of organisms induced by rare earth elements in the environment of Nanjing - Qing Yang; Mengzhu Cheng; Qing Zhou; Lihong Wang; Yunlong Jiao; Yongqiang Liu; Shuya Zhang; Li Tan; Zhenhong Gu; Hong Zhu; Hongli Luo; Daozhe Lin; et al. (Chemosphere, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Combination of hyperspectral imaging and machine learning models for fast characterization and classification of municipal solid waste - Junyu Tao; Yude Gu; Xiaoling Hao; Rui Liang; Biyu Wang; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Resources, Conservation and Recycling, 2023)

Enhanced photodegradation of tylosin in the presence of natural montmorillonite: Synergistic effects of adsorption and surface hydroxyl radicals - Yichen Xu; Yutong Zhang; Xinhao Wang; Zhe Wang; Liuqing Huang; Hao Wu; Jinghua Ren; Cheng Gu; Zhanghao Chen (Science of The Total Environment, 2023)

Prospect of China's ambient air quality standards - Zongshuang Wang; Yufei Tan; Min Guo; Miaomiao Cheng; Yanyue Gu; Siyu Chen; Xuefang Wu; Fahe Chai (Journal of Environmental Sciences, 2023)

Physical and mechanical properties of recycled aggregates modified by microbially induced calcium carbonate precipitation - Qiang Tang; Angran Tian; Cheng Ling; Yucheng Huang; Fan Gu (Journal of Cleaner Production, 2023)

Heavy metal-mediated adsorption of antibiotic tetracycline and ciprofloxacin on two microplastics: Insights into the role of complexation - Fei Tong; Di Liu; Zhenhua Zhang; Wei Chen; Guangping Fan; Yan Gao; Xueyuan Gu; Cheng Gu (Environmental Research, 2023)

MOF-derived N-Co/Fe-PC composite as heterogeneous electro-Fenton catalysis combined with electrocoagulation process for enhanced degradation of Cu-CIP complexes from wastewater - Chengye Sun; Jun Wang; Cheng Gu; Chao Wang; Shuai Sun; Peipei Song (Chemical Engineering Journal, 2023)

Bisulfite-assisted surface Fenton-like degradation of dimethyl phthalate by ferrihydrite-H2O2 system - Xiru Chen; Xinyue Gu; Chao Wang; Liuqing Huang; Dingding Wu; Hao Wu; Sijia Liang; Jingyi Ling; Cheng Gu (Chemical Engineering Journal, 2023)

Flow pattern transition and wave characteristics of impinging jet flow on a spinning disk reactor - Dongxiang Wang; Chengjun Gu; Cheng Sun; Xiang Ling; Hao Peng; Xinjun Yang; Fangyang Yuan; Jiyun Du; Wei Yu (Chemical Engineering Journal, 2023)

Formation, stability and the application of Pickering emulsions stabilized with OSA starch/chitosan complexes - Tian Xu; Chengchen Jiang; Zehao Huang; Zhengbiao Gu; Li Cheng; Yan Hong (Carbohydrate Polymers, 2023)

Coassisted carbonization with HCOOK/(HCOO)2Ca for the fabrication of bamboo-derived oxygen-doped porous carbons exhibiting high-performance sorption of diethyl phthalate from aqueous solutions - Fei Gu; Rongting Ji; Qian Sun; Shengcun Chen; Rong Bai; Yuying Shen; Xinran Liu; Yang Song; Jiangang Han; Xin Jiang; Hu Cheng; Jianming Xue (Bioresource Technology, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

Genome-wide analysis of growth-regulating factor genes in grape (Vitis vinifera L.): identification, characterization and their responsive expression to osmotic stress - Qiang Hu; Binyu Jiang; Liru Wang; Yanjing Song; Xiaoli Tang; Yanhong Zhao; Xiaobin Fan; Yafeng Gu; Qiuling Zheng; Jieshan Cheng; Hongxia Zhang (Plant Cell Reports, 2023)

Aquaculture farm largely increase indirect nitrous oxide emission factors of lake - Qitao Xiao; Cheng Hu; Xiaohong Gu; Qingfei Zeng; Zhenjing Liu; Wei Xiao; Mi Zhang; Zhenghua Hu; Wei Wang; Juhua Luo; Yinguo Qiu; Xuhui Lee; et al. (Agriculture, Ecosystems & Environment, 2023)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

High-Efficient Visible-Light Photocatalysis Performance and Light-Corrosion Resistance of Ag3PO4 Constructed by double-Z System Composites - Wenran Wang; Xueru Yu; Yutong Zhang; Liuqing Huang; Hongyi Wang; Cheng Gu; Zhanghao Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Experimental Study on Pyrolysis of Rice Straw Catalyzed by CaO/Al2O3-Phosphate Mixture - Lianlian Xu; Zhongwen Xu; Feng Zhang; Yinmei Yuan; Bin Cheng; Chuang Zhang; Ping Chen; Xiangyong Huang; Yuyu Lin; Mingyan Gu (BioEnergy Research, 2022)

Distribution and ecological risk assessment of heavy metals in sediments of Dajiuhu Lake Wetland in Shennongjia, China - Jiumei Wang; Jiwen Ge; Xiaojing Yang; Dandan Cheng; Chenhao Yuan; Ziwei Liu; Shiyu Yang; Yan Guo; Yansheng Gu (Environmental Science and Pollution Research, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

Cell-based carrier for targeted hitchhiking delivery - Tonggong Liu; Cheng Gao; Dayong Gu; Huanwen Tang (Drug Delivery and Translational Research, 2022)

High temperature induced metabolic reprogramming and lipid remodeling in a high-altitude fish species, Triplophysa bleekeri - Dengyue Yuan; Haoyu Wang; Xiaoqin Liu; Siya Wang; Jinfeng Shi; Xinkai Cheng; Haoran Gu; Shijun Xiao; Zhijian Wang (Frontiers in Marine Science, 2022)
The effect of thermal changes on the physiology and behavior of fish is a major research focus in the face of ongoing global warming. There is little information about the effects of temperature increase on fish in the wild. However, the consequences of temperature increase on fish in controlled laboratory conditions can provide insights into what can be expected in the wild. Triplophysa bleekeri , a high-plateau fish, exhibits high sensitivity to high temperatures, suggesting it to be a good model to investigate the impact of temperature increase on fish. In this study, we analyzed the effect of gradual temperature increase on transcriptional and metabolic levels of T. bleekeri subjected to a gradual temperature change of 0.5°C/day until temperatures of 10°C, 13°C, 16°C, and 19°C were reached. Transcriptomics results of the liver, gut, spleen, and trunk kidney showed that metabolic pathways are widely involved in the response to increased temperatures in T. bleekeri . Lipidomics results further indicated that the lipid composition was altered by increased temperatures, and three lipids (PC 14:0e/22:1, PC 18:0e/22:5, and TAG 14:3-21:2-21:2) were identified as potential biomarkers of heat stress in T. bleekeri . Moreover, a decline in unsaturated fatty acid levels was observed in T. bleekeri under high temperatures. These results suggest that high temperatures modify the metabolomic pathways. Overall, our results help improve the understanding of physiological responses in fish to increased temperatures, and provide valuable information predicting the consequences of global warming on fish.

Xylomexicanins K-N: limonoids from the leaves and twigs of Xylocarpus granatum - Shao-Jing Li; Li-Kang Zhao; Jin-Jun Chen; Chun-Hua Zhou; Xin-Li Huang; Yi-Bing Wu; Françoise Sauriol; Yu-Cheng Gu; Hiromasa Kiyota (Natural Product Research, 2022)

Greenhouse gas emission benefits of adopting new energy vehicles in Suzhou City, China: A case study - Cui Da; Xinyu Gu; Chunchen Lu; Ruiqi Hua; Xinyue Chang; Yuanyuan Cheng; Feiyue Qian; Yiheng Wang (Environmental Science and Pollution Research, 2022)

Control, Treatment and Restoration of Contaminated Soils - Hong-Bo Li; Changsheng Qu; Xinyi Cui; Yang Song; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2022)

A review for recent advances on soil washing remediation technologies - Fei Gu; Jiapeng Zhang; Ziqi Shen; Yang Li; Rongting Ji; Wei Li; Longjiang Zhang; Jiangang Han; Jianming Xue; Hu Cheng (Bulletin of Environmental Contamination and Toxicology, 2022)

Bioaccessibility and Toxicity Assessment of Polycyclic Aromatic Hydrocarbons in Two Contaminated Sites - Huihui Cao; Xiaona Li; Changsheng Qu; Meng Gao; Hu Cheng; Ni Ni; Shi Yao; Yongrong Bian; Chenggang Gu; Xin Jiang; Yang Song (Bulletin of Environmental Contamination and Toxicology, 2022)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

The impact of the accumulation of algal blooms on reed wetlands in the littoral zones of Chaohu Lake - Shuzhan Ma; Yue Wu; Siwen Chen; Bingfa Chen; Cheng Liu; Xiaozhi Gu; Xiaoli Shi; Kaining Chen (Journal of Oceanology and Limnology, 2022)

Development of an Escherichia coli whole cell biocatalyst for the production of hyperoside - Guo-Si Li; Fu-Cheng Zhu; Pei-Pei Wei; Fang-Li Gu; Qi-Ling Xu; Meng-Hua Ma (Biotechnology Letters, 2022)

CRIF1 promotes the progression of non-small-cell lung cancer by SIRT3- mediated deacetylation of PYCR1 - Qi Wang; Zhuolin Xie; Chang Li; Chun Xu; Cheng Ding; Sheng Ju; Jun Chen; Zihan Cui; Chen Chen; Biao Gu; Tengteng Wei; Jun Zhao (Journal of Molecular Histology, 2022)

Asynchronous variations of East Asian summer monsoon, vegetation and soil formation at Yulin (North China) in the Holocene - CHENGHONG LIANG; HUAYU LU; YAO GU; CHENG ZHAO; WEIGUO LIU; XIAOJIAN ZHANG; HONGYAN ZHANG (Journal of Quaternary Science, 2022)
In the East Asian monsoon region, Chinese speleothem δ 18 O records exhibit a maximum monsoon strength during the early Holocene. However, other proxy data from lakes or loess, interpreted as monsoon rainfall, show a mid‐Holocene monsoon optimum. This discrepancy may come from specific climate interpretation of different proxies. Here we report multiproxy records from a single loess–palaeosol sequence at Yulin in the monsoon marginal northern China, based on an independent and high‐precision chronology. Our long‐chain n ‐alkane δD values, together with related biomarker proxies including the average chain length and concentration of long‐chain n‐ alkanes, reveal a weakening trend in monsoon strength and less woody vegetation since ~6 ka. However, other soil formation‐related proxies, such as magnetic susceptibility, grain‐size distribution and total organic carbon, show a decreasing trend since 4–3 ka. We find that monsoon and vegetation are controlled by insolation variation, while soil formation is more related to temperature and humidity changes. Our multiple proxy comparison reveals different controlling mechanisms leading to different interpretations in monsoon, vegetation and soil formation reconstructions. This finding suggests that previous debates on Holocene monsoon changes in East Asia probably stem from the specific proxy interpretation.

A Three-Dimensional Slip Velocity Model for Water-Lubricated Hydrodynamic Journal Bearings - Yandong Gu; Jinwu Cheng; Hao Sun; Ao Liang; Li Cheng (Journal of Marine Science and Engineering, 2022)
Hydrodynamic journal bearings, coated with polytetrafluoroethylene (PTFE) and lubricated by water, have been widely used in ships and large-scale pumps, and the function is to maintain the stability of rotor system. However, slip velocity exists on the PTFE-coated surface, whose effect is still an open question. This study aims to investigate the static characteristics of water-lubricated hydrodynamic journal bearings under three-dimensional slip velocity boundary conditions. Firstly, under the non-slip boundary condition, the CFD (computational fluid dynamics) method with ANSYS Fluent is verified based on the Reynolds lubrication equation and the open literature. Then, a three-dimensional slip velocity equation that is based on the Navier slip velocity boundary condition is proposed and embedded into Fluent. Finally, the effects of slip length on the static characteristics are analyzed. Under the same eccentricity ratio, with the increase in slip length, the load capacity decreases due to the decrease of the pressure circumferential gradient, and the friction power decreases. Under the same eccentricity ratio and the same slip length, with the increase in the attitude angle, the load capacity and friction power increase. However, under the non-slip boundary condition, the effects of attitude angle on the load capacity and friction power are insignificant. This paper could provide a reference for studying slip velocity in the hydrodynamic journal bearing.

Heterologous expression, refolding, and characterization of a calcium-independent phospholipase A1 from Streptomyces albidoflavus - Shi Cheng; Zitao Guo; Chaojuan Liang; Yi Shi; Peng Geng; Yu Xin; Zhenghua Gu; Liang Zhang (Systems Microbiology and Biomanufacturing, 2022)

Temporal dynamics of fine root production, mortality and turnover deviate across branch orders in a larch stand - Changfu Huo; Jiacun Gu; Lizhong Yu; Peng Wang; Weixin Cheng (Oecologia, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

DeepStack-DTIs: Predicting Drug–Target Interactions Using LightGBM Feature Selection and Deep-Stacked Ensemble Classifier - Yan Zhang; Zhiwen Jiang; Cheng Chen; Qinqin Wei; Haiming Gu; Bin Yu (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Association between urinary cadmium concentrations and liver function in adolescents - Zining Xu; Zhenkun Weng; Jingjia Liang; Qian Liu; Xin Zhang; Jin Xu; Cheng Xu; Aihua Gu (Environmental Science and Pollution Research, 2022)

Cholinergic relevant functional reactivity is associated with dopamine responsiveness of tremor in Parkinson’s disease - Jingjing Wu; Cheng Zhou; Tao Guo; Xiaojun Guan; Ting Gao; Xueqin Bai; Haoting Wu; Jingwen Chen; Jiaqi Wen; Xiaocao Liu; Luyan Gu; Zhe Song; et al. (Brain Imaging and Behavior, 2022)
Tremor in Parkinson’s disease (PD) has distinct responsiveness to dopamine, which is supposed not be exclusively related to dopamine deficiency but has a close relationship with cholinergic system. This phenomenon indicates that cholinergic system may be an important regulatory for distinct dopamine responsiveness of parkinsonian tremor. Through investigating the alterations of cholinergic and dopaminergic network during levodopa administration, we aimed at exploring the mechanisms of differed dopamine responsiveness of parkinsonian tremor. Fifty-two PD patients with tremor were enrolled. MRI scanning, UPDRS III and its sub-symptom scores were collected in OFF and ON status (dopaminergic challenge test). Then, patients were divided into two groups (dopamine-resistant tremor and dopamine-responsive tremor) according to the tremor change rate median score. Dopaminergic and cholinergic network were obtained. LASSO regression was conducted to identify functional connectivity with distinct reactivity during levodopa administration between groups. Afterwards, detailed group comparisons, interaction and correlation analyses were performed. The reactivity of cholinergic connectivity showed the highest possibility to distinguish two groups, especially connectivity of right basal forebrain 123 to right parietal operculum cortex (R.BF123-R.PO). After levodopa administration, connectivity of R.BF123-R.PO was decreased for dopamine-responsive tremor while which remained unchanged for dopamine-resistant tremor. The reactivity of R.BF123-R.PO was negatively correlated with tremor change rate. Reduced cholinergic connectivity to parietal operculum may be an underlying mechanism for the responsive tremor in PD and the distinct cholinergic reactivity of parietal operculum to levodopa may be a core pathophysiology for the differed DA responsiveness of tremor in PD.

AKT/GSK-3β signaling is altered through downregulation of mTOR during cerebral Ischemia/Reperfusion injury - Shengwei Peng; Jin-hua Gu; Chun-ling Dai; Khalid Iqbal; Fei Liu; Cheng-Xin Gong (Molecular Biology Reports, 2022)

Total cholesterol: a potential mediator of the association between exposure to acrylamide and hypertension risk in adolescent females - Jingjia Liang; Cheng Xu; Qian Liu; Zhenkun Weng; Xin Zhang; Jin Xu; Aihua Gu (Environmental Science and Pollution Research, 2022)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Xidaosterols A and B, two new steroids with unusual α -keto-enol functionality from the South China Sea sponge Neopetrosia chaliniformis - Bao Chen; Yu-Cheng Gu; Nicole J. de Voogd; Chang-Yun Wang; Yue-Wei Guo (Natural Product Research, 2022)

Flavonoid components and gene expression analysis reveal flower pigmentation difference between Magnolia biondii and its variety M. biondii var. purpurascens - Ning-hang Wang; Meng-yi Dai; Gang Zheng; Peng-jie Chang; Ling-juan Xuan; Zhi-gao Liu; Ya-ling Wang; Shao-yu Cheng; Zhuo-wei Wang; Hai-long Wang; Cui-hua Gu; Chao Zhang; et al. (Trees, 2022)

IKKβ Alleviates Neuron Injury in Alzheimer’s Disease via Regulating Autophagy and RIPK1-Mediated Necroptosis - Wei Wang; Xunhu Gu; Zhijuan Cheng; Xiaoqing Lu; Shuhua Xie; Xu Liu (Molecular Neurobiology, 2022)

Colon tissue image segmentation with MWSI-NET - Hao Cheng; Kaijie Wu; Jie Tian; Kai Ma; Chaocheng Gu; Xinping Guan (Medical & Biological Engineering & Computing, 2022)

Discovery of a Natural Product with Potent Efficacy Against SARS-CoV-2 by Drug Screening - Daixi Li; Cheng Wang; Shaobo Wang; Aamir Mehmood; Jiang Gu; Xin Cheng; Peiqin Chen; JingFei Qiu; Jinghong Zhao; Junping Wang; Dongqing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Circular RNA circ_0008934 promotes hepatocellular carcinoma growth and metastasis through modulating miR-1305/TMTC3 axis - Jia-Xi Li; Jin-Jiang Wang; Zhou-Feng Deng; Hao Zheng; Chun-Mei Yang; Ying Yuan; Cheng Yang; Fang-Fang Gu; Wei-Qi Wu; Guang-Lei Qiao; Li-Jun Ma (Human Cell, 2022)

Autophagy inhibitors alleviate Japanese encephalitis virus-induced cerebral inflammation in mice - Jinhua Zhang; Wei Han; Changqing Xie; Mingxing Gao; Xugang Wang; Xueying Hu; Wanpo Zhang; Shengbo Cao; Xiaoli Liu; Guofu Cheng; Changqin Gu (Archives of Virology, 2022)

Structure modification, antialgal, antiplasmodial, and toxic evaluations of a series of new marine-derived 14-membered resorcylic acid lactone derivatives - Wei-Feng Xu; Na-Na Wu; Yan-Wei Wu; Yue-Xuan Qi; Mei-Yan Wei; Laura M. Pineda; Michelle G. Ng; Carmenza Spadafora; Ji-Yong Zheng; Ling Lu; Chang-Yun Wang; Yu-Cheng Gu; et al. (Marine Life Science & Technology, 2022)
Marine natural products play critical roles in the chemical defense of many marine organisms and are essential, reputable sources of successful drug leads. Sixty-seven 14-membered resorcylic acid lactone derivatives 3 – 27 and 30 – 71 of the natural product zeaenol ( 1 ) isolated from the marine-derived fungus Cochliobolus lunatus were semisynthesized by chlorination, acylation, esterification, and acetalization in one to three steps. The structures of these new derivatives were established by HRESIMS and NMR techniques. All the compounds ( 1 – 71 ) were evaluated for their antialgal and antiplasmodial activities. Among them, 14 compounds displayed antifouling activities against adhesion of the fouling diatoms. In particular, 9 and 34 exhibited strong and selective inhibitory effects against the diatoms Navicula laevissima and Navicula exigua (EC 50 = 6.67 and 8.55 μmol/L), respectively, which were similar in efficacy to those of the positive control SeaNine 211 (EC 50 = 2.90 and 9.74 μmol/L). More importantly, 38 , 39 , and 69 – 71 showed potent antiplasmodial activities against Plasmodium falciparum with IC 50 values ranging from 3.54 to 9.72 μmol/L. Very interestingly, the five antiplasmodial derivatives displayed non-toxicity in the cytotoxicity assays and the zebrafish embryos model, thus, representing potential promising antiplasmodial drug agents. The preliminary structure–activity relationships indicated that biphenyl substituent at C-2, acetonide at positions C-5′ and C-6′, and tri- or tetra-substituted of acyl groups increased the antiplasmodial activity. Therefore, combining evaluation of chemical ecology with pharmacological models will be implemented as a systematic strategy, not only for environmentally friendly antifoulants but also for structurally novel drugs.

Diversity of arbuscular mycorrhiza fungi in rhizosphere soil and roots in Vetiveria zizanioides plantation chronosequence in coal gangue heaps - Tianyue Gu; Yuanyuan Mao; Chao Chen; Yong Wang; Qi Lu; Huaqiu Wang; Wei Cheng (Symbiosis, 2022)

Dissolved Nitrous Oxide and Hydroxylamine in the South Yellow Sea and the East China Sea During Early Spring: Distribution, Production, and Emissions - Xueji Gu; Fang Cheng; Xiaolei Chen; Guanxiang Du; Guiling Zhang (Frontiers in Marine Science, 2021)
Coastal marine systems are active regions for the production and emission of nitrous oxide (N 2 O), a potent greenhouse gas. Due to the inherently high variability in different coastal biogeochemical cycles, the factors and mechanisms regulating coastal N 2 O cycling remain poorly understood. Hydroxylamine (NH 2 OH), a potential precursor of N 2 O, has received less attention than other compounds in the coastal areas. Here, we present the spatial distribution of N 2 O and the first reported NH 2 OH distribution in the South Yellow Sea (SYS) and the East China Sea (ECS) between March and April 2017. The surface N 2 O concentrations in the SYS and the ECS varied from 5.9 to 11.3 nmol L –1 (average of 8.4 ± 1.4 nmol L –1 ) and were characterized by offshore and north–south decreasing gradients. NH 2 OH showed patchy characteristics and was highly variable, fluctuating between undetectable to 16.4 nmol L –1 . We found no apparent covariation between N 2 O and NH 2 OH, suggesting the NH 2 OH pathway, i.e., nitrification (ammonium oxidation), was not the only process affecting N 2 O production here. The high NH 2 OH values co-occurred with the greatest chlorophyll- a and oxygen levels in the nearshore region, along with the relationships between NO 2 – , NO 3 – , and NH 2 OH, indicating that a “fresh” nitrifying system, favoring the production and accumulation of NH 2 OH, was established during the phytoplankton bloom. The high N 2 O concentrations were not observed in the nearshore. Based on the correlations of the excess N 2 O (ΔN 2 O) and apparent oxygen utilization, as well as ΔN 2 O vs. NO 3 – , we concluded that the N 2 O on the continental shelf was mainly derived from nitrification and nitrifier denitrification. Sea-to-air fluxes of N 2 O varied from −12.4 to 6.6 μmol m –2 d –1 (−3.8 ± 3.7 μmol m –2 d –1 ) using the Nightingale et al. (2000) formula and −13.3 to 6.9 μmol m –2 d –1 (−3.9 ± 3.9 μmol m –2 d –1 ) using the Wanninkhof (2014) formula, which corresponds to 75–112% in saturation, suggesting that the SYS and the ECS acted overall as a sink of atmospheric N 2 O in early spring, with the strength weakening. Our results reveal the factors and potential mechanisms controlling the production and accumulation of NH 2 OH and N 2 O in the SYS and the ECS during early spring.

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Fiber-optic wireless sensor network using ultra-weak fiber Bragg gratings for vertical subsurface deformation monitoring - Su-Ping Liu; Bin Shi; Kai Gu; Cheng-Cheng Zhang; Jian-Hui He; Jing-Hong Wu; Guang-Qing Wei (Natural Hazards, 2021)

Secondary Sulfate Minerals from Pyrite Oxidation in Lanmuchang Hg-Tl Deposit, Southwest Guizhou Province, China: Geochemistry and Environmental Significance - Fengqi Zhao; Shangyi Gu; Likai Hao; Hongguang Cheng; Lingfei Liu (Bulletin of Environmental Contamination and Toxicology, 2021)

Climate change may interact with nitrogen fertilizer management leading to different ammonia loss in China’s croplands - Xiangrui Xu; Xiao Ouyang; Yining Gu; Kun Cheng; Pete Smith; Jianfei Sun; Yunpeng Li; Genxing Pan (Global Change Biology, 2021)
Despite research into the response of ammonia (NH 3 ) volatilization in farmland to various meteorological factors, the potential impact of future climate change on NH 3 volatilization is not fully understood. Based on a database consisting of 1063 observations across China, nonlinear NH 3 models considering crop type, meteorological, soil and management variables were established via four machine learning methods, including support vector machine, multi‐layer perceptron, gradient boosting machine and random forest (RF). The RF model had the highest R 2 of 0.76 and the lowest RMSE of 0.82 kg NH 3 ‐N ha − 1 , showing the best simulation capability. Results of model importance indicated that NH 3 volatilization was mainly controlled by total input of N fertilizer, followed by meteorological factors, human managements and soil characteristics. The NH 3 emissions of China's cereal production (paddy rice, wheat and maize) in 2018 was estimated to be 3.3 Mt NH 3 ‐N. By 2050, NH 3 volatilization will increase by 23.1−32.0% under different climate change scenarios (Representative Concentration Pathways, RCPs), and climate change will have the greatest impact on NH 3 volatilization in the Yangtze river agro‐region of China due to high warming effects. However, the potential increase in NH 3 volatilization under future climate change can be mitigated by 26.1−47.5% through various N fertilizer management optimization options.

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

Two new nor-sesquiterpenoids from Fusarium tricinctum , an endophytic fungus isolated from Ligusticum chuanxiong - Yu-Mei Cao; Da-Le Guo; Meng-Ying Jin; Lu Tan; Tian-Long Yang; Fang Deng; Yu-Cheng Gu; Xiao-Hua Li; Zhi-Xing Cao; Yun Deng (Natural Product Research, 2021)

The intriguing chemistry and biology of sulfur-containing natural products from marine microorganisms (1987–2020) - Yang Hai; Mei-Yan Wei; Chang-Yun Wang; Yu-Cheng Gu; Chang-Lun Shao (Marine Life Science & Technology, 2021)
Natural products derived from marine microorganisms have received great attention as a potential resource of new compound entities for drug discovery. The unique marine environment brings us a large group of sulfur-containing natural products with abundant biological functionality including antitumor, antibiotic, anti-inflammatory and antiviral activities. We reviewed all the 484 sulfur-containing natural products (non-sulfated) isolated from marine microorganisms, of which 59.9% are thioethers, 29.8% are thiazole/thiazoline-containing compounds and 10.3% are sulfoxides, sulfones, thioesters and many others. A selection of 133 compounds was further discussed on their structure–activity relationships, mechanisms of action, biosynthesis, and druggability. This is the first systematic review on sulfur-containing natural products from marine microorganisms conducted from January 1987, when the first one was reported, to December 2020.

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Effect of mangrove restoration on sediment properties and bacterial community - Xiao-Xia Ma; Zhao-Yu Jiang; Peng Wu; Yong-Fei Wang; Hao Cheng; You-Shao Wang; Ji-Dong Gu (Ecotoxicology, 2021)

Effect of Polyvinyl Chloride Microplastics on Bacterial Community and Nutrient Status in Two Agricultural Soils - Yuanyuan Yan; Zhanghao Chen; Fengxiao Zhu; Changyin Zhu; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2021)

Non-coding RNA: insights into the mechanism of methamphetamine neurotoxicity - Ying-Jian Gu; Lei Chen; Lin Cheng; Ming-Yuan Zhou; Yun Wang (Molecular and Cellular Biochemistry, 2021)

Mapping of geomorphic dynamic parameters for analysis of landslide hazards: A case of Yangbi river basin on the upper Lancang-Mekong of China - Zhen-kui Gu; Xin Yao; Chuang-chuang Yao; Cheng-gang Li (Journal of Mountain Science, 2021)

Mineralogy, fluid inclusions, H-O isotopes, and trace element of the Dongzigou Pb-Zn deposit in the Sangmuchang metallogenic belt, China - Ying Gu; Cuihua Chen; Yulong Yang; Xuhao Kang; Yin Li; Xiaojie Chen; Xiang Lai; Zhijiao Song; Deping Yang; Cheng Jin; Shuyue Liu (Arabian Journal of Geosciences, 2021)

Design and synthesis of sinomenine isoxazole derivatives via 1,3-dipolar cycloaddition reaction - Hongmei Pan; Tong Lu; Xuedan Wu; Chengwen Gu; Naili Tao; Biao Zhang; Ao Wang; Guangmei Chen; Kehua Zhang; Jie Cheng; Jie Jin (Natural Product Research, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Fusarium solani G6, a novel vitexin-producing endophytic fungus: characterization, yield improvement and osteoblastic proliferation activity - Pei-jia Tang; Zhi-hui Zhang; Li-li Niu; Cheng-bo Gu; Wen-yi Zheng; Hai-chao Cui; Xiao-han Yuan (Biotechnology Letters, 2021)

PHD Finger Protein 19 Promotes Cardiac Hypertrophy via Epigenetically Regulating SIRT2 - Wei Gu; Yutong Cheng; Su Wang; Tao Sun; Zhizhong Li (Cardiovascular Toxicology, 2021)
Epigenetic regulations essentially participate in the development of cardiomyocyte hypertrophy. PHD finger protein 19 (PHF19) is a polycomb protein that controls H3K36me3 and H3K27me3. However, the roles of PHF19 in cardiac hypertrophy remain unknown. Here in this work, we observed that PHF19 promoted cardiac hypertrophy via epigenetically targeting SIRT2. In angiotensin II (Ang II)-induced cardiomyocyte hypertrophy, adenovirus-mediated knockdown of Phf19 reduced the increase in cardiomyocyte size, repressed the expression of hypertrophic marker genes Anp and Bnp , as well as inhibited protein synthesis. By contrast, Phf19 overexpression promoted Ang II-induced cardiomyocyte hypertrophy in vitro. We also knocked down Phf19 expression in mouse hearts in vivo. The results demonstrated that Phf19 knockdown reduced Ang II-induced decline in cardiac fraction shortening and ejection fraction. Phf19 knockdown also inhibited Ang II-mediated increase in heart weight, reduced cardiomyocyte size, and repressed the expression of hypertrophic marker genes in mouse hearts. Further mechanism studies showed that PHF19 suppressed the expression of SIRT2, which contributed to the function of PHF19 during cardiomyocyte hypertrophy. PHF19 bound the promoter of SIRT2 and regulated the balance between H3K27me3 and H3K36me3 to repress the expression of SIRT2 in vitro and in vivo. In human hypertrophic hearts, the overexpression of PHF19 and downregulation of SIRT2 were observed. Of importance, PHF19 expression was positively correlated with hypertrophic marker genes ANP and BNP but negatively correlated with SIRT2 in human hypertrophic hearts. Therefore, our findings demonstrated that PHF19 promoted the development of cardiac hypertrophy via epigenetically regulating SIRT2.

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Selection and optimum fertilization of Betula platyphylla hybrid clones for growth - Shuyuan Song; Siqi Cheng; Zhen Jia; Minghui Li; Jiabao Ji; Yifan Yang; Chu Wang; Chenrui Gu; Qibin Yu; Yuhui Weng; Guifeng Liu (Trees, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

ZEB1: New advances in fibrosis and cancer - Lin Cheng; Ming-Yuan Zhou; Ying-Jian Gu; Lei Chen; Yun Wang (Molecular and Cellular Biochemistry, 2021)

The metabolic and immunological characteristics of pregnant women with COVID-19 and their neonates - Jingjiao Zhou; Yudie Wang; Juan Zhao; Lixing Gu; Cheng Yang; Jun Wang; Heng Zhang; Yu Tian; Hu Tuo; Dan Li; Min Wei; Bing He (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Ecological engineering in pond aquaculture: a review from the whole‐process perspective in China - XingGuo Liu; Zhengyi Shao; Guofeng Cheng; Shimin Lu; Zhaojun Gu; Hao Zhu; Hongye Shen; Jie Wang; Xiaolong Chen (Reviews in Aquaculture, 2021)
Pond aquaculture undeniably offers the potential for food production worldwide. In China, 45.83% of aquatic production is currently from pond aquaculture. However, with the continuous expansion of this practice, environmental problems such as a high level of water consumption, aquaculture water deterioration, pollution from effluent and aquatic product quality decline seriously restrict the sustainable development of pond aquaculture. In this review, we summarise the (i) the impacts of pond aquaculture on the environment, (ii) research progress in pond aquaculture ecological engineering, (iii) existing technologies regarding pond aquaculture ecological engineering systems, (iv) effects of applying pond aquaculture ecological engineering and (v) summary and prospects. Moreover, we discuss the merits and drawbacks of each method and technology, and future research priorities are reviewed. With this, an understanding of the role played by ecological engineering in pond aquaculture is provided, as well as guidance for precisely managing aquaculture water and effluent, aquaculture practices, and technological developments. In summary, the pond aquaculture ecological engineering can be managed so as to improve animal welfare and the stability of water treatment systems, reducing the adverse effects on the environment and public health, and enabling the sustainable development of pond aquaculture.

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Identification of reproduction-related genes and pathways in the Culter alburnus H-P-G axis and characterization of their expression differences in malformed and normal gynogenetic ovaries - Yong Y. Jia; Mei L. Chi; Wen P. Jiang; Shi L. Liu; Shun Cheng; Jian B. Zheng; Zhi M. Gu (Fish Physiology and Biochemistry, 2021)

Sustained effects of one-time sewage sludge addition on rice yield and heavy metals accumulation in salt-affected mudflat soil - Wengang Zuo; Yanchao Bai; Ming Lv; Zehui Tang; Cheng Ding; Chuanhui Gu; Yuhua Shan; Qigen Dai; Min Li (Environmental Science and Pollution Research, 2021)

Correction to: Effect of Polyvinyl Chloride Microplastics on Bacterial Community and Nutrient Status in Two Agricultural Soils - Yuanyuan Yan; Zhanghao Chen; Fengxiao Zhu; Changyin Zhu; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Calcium-sensing receptor in the development and treatment of pulmonary hypertension - Ming-Yuan Zhou; Lin Cheng; Lei Chen; Ying-Jian Gu; Yun Wang (Molecular Biology Reports, 2021)

Characterization of a recombinant sucrose isomerase and its application to enzymatic production of isomaltulose - Feng Zhang; Feng Cheng; Dong-Xu Jia; Yue-Hao Gu; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2021)

Estimation of surface energy fluxes in the permafrost region of the Tibetan Plateau based on in situ measurements and the surface energy balance system model - Jimin Yao; Lianglei Gu; Cheng Yang; Hao Chen; Jiemin Wang; Yongjian Ding; Ren Li; Lin Zhao; Yao Xiao; Yongping Qiao; Jianzong Shi; Caiping Chen (International Journal of Climatology, 2020)
The surface energy balance is a key issue in land surface process research and important for studies of climate and hydrology. In this paper, the surface energy fluxes (net radiation, ground heat flux, sensible heat flux and latent heat flux) at the Tanggula (TGL) and Xidatan (XDT) sites were measured and the distributions of the regional surface energy fluxes on the Tibetan Plateau were obtained using a revised surface energy balance system (SEBS) model. The results show that the surface energy fluxes have obvious seasonal variations. At both sites, the sensible heat flux is highest in spring and lowest in summer, and the latent heat flux is highest in summer and lowest in winter. The high elevation, snow cover, freeze–thaw process, precipitation, vegetation and soil texture are important influencing factors for land surface energy fluxes. The time‐phase difference between the net radiation and ground heat flux for bare soils is estimated to be 2–3 hr. The ratio of ground heat flux and net radiation ranged from approximately 0.18 to 0.33, and a parameterization scheme for the remote sensing of ground heat flux over the Tibetan Plateau bare soil in summer is developed. The simulation results of the regional surface energy fluxes show that the distributions of surface parameters, such as vegetation, soil texture and soil moisture content, are important for understanding regional changes in the surface energy fluxes.

Internal States Influence the Representation and Modulation of Food Intake by Subthalamic Neurons - Haichuan Wu; Xiang Yan; Dongliang Tang; Weixin Gu; Yiwen Luan; Haijiang Cai; Chunyi Zhou; Cheng Xiao (Neuroscience Bulletin, 2020)

Plasma Protein Panels for Mild Cognitive Impairment Among Elderly Chinese Individuals with Different Educational Backgrounds - Hongyu Yang; Shouquan Gu; Yue Wu; Yan Jiang; Jinfa Zhao; Zaohuo Cheng (Journal of Molecular Neuroscience, 2020)

Land subsidence monitoring in sinking coastal areas using distributed fiber optic sensing: a case study - Su-Ping Liu; Bin Shi; Kai Gu; Cheng-Cheng Zhang; Ji-Long Yang; Song Zhang; Peng Yang (Natural Hazards, 2020)

Physiological and transcriptomic analyses of brassinosteroid function in moso bamboo (Phyllostachys edulis) seedlings - Zhe Zhang; Xuelian Yang; Ling Cheng; Zejun Guo; Huiyuan Wang; Weihuang Wu; Kihye Shin; Jinyao Zhu; Xiaoli Zheng; Jianghu Bian; Yangchen Li; Lianfeng Gu; et al. (Planta, 2020)

The characteristics and genome analysis of vB_ApiP_XC38, a novel phage infecting Acinetobacter pittii - Mengjun Cheng; Man Luo; Hengyu Xi; Yunze Zhao; Shuai Le; Li-Kuang Chen; Demeng Tan; Yuan Guan; Tianqi Wang; Wenyu Han; Nannan Wu; Tongyu Zhu; et al. (Virus Genes, 2020)

Metal bioavailability during the periodic drying and rewetting process of littoral anoxic sediment - Cheng Liu; Ming Kong; Lei Zhang; Kaining Chen; Xiaozhi Gu; Xiaoming Hao (Journal of Soils and Sediments, 2020)

Thermoluminescence Studies of β and γ-Irradiated Geological Materials for Environment Monitoring - Gu Cheng-lin; Vikas Dubey; Kamal Kumar Kushwah; Manish Kumar Mishra; Ekta Pandey; Ratnesh Tiwari; Angesh Chandra; Neha Dubey (Journal of Fluorescence, 2020)

Mixed secondary chromatin structure revealed by modeling radiation-induced DNA fragment length distribution - Wenzong Ma; Chenyang Gu; Lin Ma; Caoqi Fan; Chao Zhang; Yujie Sun; Cheng Li; Gen Yang (Science China Life Sciences, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

The effect of environmental regulation on capacity utilization in China’s manufacturing industry - Zhonghua Cheng; Jun Liu; Lianshui Li; Xinbei Gu (Environmental Science and Pollution Research, 2020)

Three new ɑ-pyrone derivatives induced by chemical epigenetic manipulation of Penicillium herquei , an endophytic fungus isolated from Cordyceps sinensis - Da-Le Guo; Ling Qiu; Dan Feng; Xin He; Xiao-Hua Li; Zhi-Xing Cao; Yu-Cheng Gu; Ling Mei; Fang Deng; Yun Deng (Natural Product Research, 2020)

Selenate Reduction and Selenium Enrichment of Tea by the Endophytic Herbaspirillum sp. Strain WT00C - Xiao Xu; Wei Cheng; Xin Liu; Heng You; Guitai Wu; Kunming Ding; Xiuliang Tu; Lanfang Yang; Youpin Wang; Yadong Li; Haoshuang Gu; Xingguo Wang (Current Microbiology, 2020)

Increased interregional functional connectivity of anterior insula is associated with improved smoking cessation outcome - Chao Wang; Zhujing Shen; Peiyu Huang; Wei Qian; Cheng Zhou; Kaicheng Li; Qingze Zeng; Xiao Luo; Quanquan Gu; Hualiang Yu; Yihong Yang; Minming Zhang (Brain Imaging and Behavior, 2020)

Insights into the thermostability and product specificity of a maltooligosaccharide-forming amylase from Bacillus stearothermophilus STB04 - Xiaofang Xie; Xiaofeng Ban; Zhengbiao Gu; Caiming Li; Yan Hong; Li Cheng; Zhaofeng Li (Biotechnology Letters, 2020)

Transformation and toxicity of environmental contaminants as influenced by Fe containing clay minerals: a review - Yi Wang; Xin Jin; Anping Peng; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2020)

Numerical investigation of the wind environment around tall buildings in a central business district - Pingzhi Fang; Deqian Zheng; Ming Gu; Haifeng Cheng; Bihong Zhu (Frontiers of Earth Science, 2019)

Decellularization, cross-linking and heparin immobilization of porcine carotid arteries for tissue engineering vascular grafts - Zhiwen Cai; Yongquan Gu; Jin Cheng; Ji Li; Zeqin Xu; Yuehao Xing; Cong Wang; Zhonggao Wang (Cell and Tissue Banking, 2019)

Rapid evolution of α-gliadin gene family revealed by analyzing Gli-2 locus regions of wild emmer wheat - Naxin Huo; Tingting Zhu; Shengli Zhang; Toni Mohr; Ming-Cheng Luo; Jong-Yeol Lee; Assaf Distelfeld; Susan Altenbach; Yong Q. Gu (Functional & Integrative Genomics, 2019)

Correction to: SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

From Analysis of Ischemic Mouse Brain Proteome to Identification of Human Serum Clusterin as a Potential Biomarker for Severity of Acute Ischemic Stroke - Hailong Song; Hui Zhou; Zhe Qu; Jie Hou; Weilong Chen; Weiwu Cai; Qiong Cheng; Dennis Y. Chuang; Shanyan Chen; Shuwei Li; Jilong Li; Jianlin Cheng; et al. (Translational Stroke Research, 2019)

Biological properties and genomics analysis of vB_KpnS_GH-K3, a Klebsiella phage with a putative depolymerase-like protein - Ruopeng Cai; Zijing Wang; Gang Wang; Hao Zhang; Mengjun Cheng; Zhimin Guo; Yalu Ji; Hengyu Xi; Xinwu Wang; Yibing Xue; Sadeeq ur Rahman; Changjiang Sun; et al. (Virus Genes, 2019)

SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

2,3,7,8-Tetrachlorodibenzo-p-dioxin-induced aryl hydrocarbon receptor activation enhanced the suppressive function of mesenchymal stem cells against splenocyte proliferation - Guorui Zhang; Xiaoming Li; Yi Cheng; Haiyang Yu; Wen Gu; Zhilei Cui; Xuejun Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Molecular characterization and expression analysis of cyp19a gene in Culter alburnus - Jianbo Zheng; Yongyi Jia; Fei Li; Shili Liu; Meili Chi; Shun Cheng; Zhimi Gu (Fisheries Science, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

A panel analysis of the sustainability of logistics industry in China: based on non-radial slacks-based method - Lingling Tan; Qunqi Wu; Qian Li; Wen Cheng; Yulei Gu (Environmental Science and Pollution Research, 2019)

Current Research Advancements in Basic and Applied Soil Remediation in China - Wang Yujun; Zhong Huan; Gu Cheng; Zhou Dongmei (Bulletin of Environmental Contamination and Toxicology, 2019)

Occurrence and Ecological Impacts of Microplastics in Soil Systems: A Review - Fengxiao Zhu; Changyin Zhu; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2019)

Genome-wide identification of Ziziphus jujuba TCP transcription factors and their expression in response to infection with jujube witches’ broom phytoplasma - Peng Chen; Jidong Li; Xia Ye; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Huiyu Wang; Liyuan Gu; Jiancan Feng (Acta Physiologiae Plantarum, 2019)

Identifying the genes around Rf5 and Rf6 loci for the fertility restoration of WA-type cytoplasmic male sterile japonica rice (Oryza sativa) lines - Honggen Zhang; Xiaojun Cheng; Lijia Zhang; Qiaoquan Liu; Minghong Gu; Shuzhu Tang (Euphytica, 2019)

Baroreflex Control of Heart Rate in Mice Overexpressing Human SOD1: Functional Changes in Central and Vagal Efferent Components - Jin Chen; He Gu; Robert D. Wurster; Zixi Cheng (Neuroscience Bulletin, 2019)

Molecular identification of dmrt1 and its promoter CpG methylation in correlation with gene expression during gonad development in Culter alburnus - Yongyi Jia; Jianbo Zheng; Meili Chi; Shili Liu; Wenping Jiang; Shun Cheng; Zhimi Gu; Liqiao Chen (Fish Physiology and Biochemistry, 2019)

Genome-wide association study of maize plant architecture using F1 populations - Yang Zhao; Hengsheng Wang; Chen Bo; Wei Dai; Xingen Zhang; Ronghao Cai; Longjiang Gu; Qing Ma; Haiyang Jiang; Jun Zhu; Beijiu Cheng (Plant Molecular Biology, 2019)

HDAC9 Polymorphisms Predict Susceptibility, Severity, and Short-Term Outcome of Large Artery Atherosclerotic Stroke in Chinese Population - Mengmeng Wang; Mengmeng Gu; Zibao Li; Bo Sun; Xi Cheng; Zhengze Dai; Shun Li; Lulu Xiao; Min Zhao; Zhaojun Wang; Ying Lin; Yahong Liu; et al. (Journal of Molecular Neuroscience, 2019)

ATMT transformation efficiencies with native promoters in Botryosphaeria kuwatsukai causing ring rot disease in pear - Xueying Gu; Jiamin Zhao; Hongkai Wang; Fu-Cheng Lin; Qingyuan Guo; Neeraj Shrivastava; Rajesh Jeewon (World Journal of Microbiology and Biotechnology, 2018)

Saikosaponin-d inhibits proliferation by up-regulating autophagy via the CaMKKβ–AMPK–mTOR pathway in ADPKD cells - Weiwei Shi; Dechao Xu; Junhui Gu; Cheng Xue; Bo Yang; Lili Fu; Shuwei Song; Dongmei Liu; Wei Zhou; Jiayi Lv; Ke Sun; Meihan Chen; et al. (Molecular and Cellular Biochemistry, 2018)

Reassessment of the evolution of wheat chromosomes 4A, 5A, and 7B - Jan Dvorak; Le Wang; Tingting Zhu; Chad M. Jorgensen; Ming-Cheng Luo; Karin R. Deal; Yong Q. Gu; Bikram S. Gill; Assaf Distelfeld; Katrien M. Devos; Peng Qi; Patrick E. McGuire (Theoretical and Applied Genetics, 2018)

Global transcriptome and weighted gene co-expression network analyses reveal hybrid-specific modules and candidate genes related to plant height development in maize - Hengsheng Wang; Longjiang Gu; Xingen Zhang; Mingli Liu; Haiyang Jiang; Ronghao Cai; Yang Zhao; Beijiu Cheng (Plant Molecular Biology, 2018)

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

Expression Analysis of TCP Genes in Peach Reveals an Involvement of PpTCP.A2 in Ethylene Biosynthesis During Fruit Ripening - Zhi-Hua Guo; Wei-Shen Shu; Hai-Yan Cheng; Guo-Ming Wang; Kai-Jie Qi; Shao-Ling Zhang; Chao Gu (Plant Molecular Biology Reporter, 2018)

Calpain inhibition attenuates bleomycin-induced pulmonary fibrosis via switching the development of epithelial-mesenchymal transition - Yuan Liu; Bing Liu; Gu-qin Zhang; Jing-feng Zou; Meng-lin Zou; Zhen-shun Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

CXCL5 regulation of proliferation and migration in human non-small cell lung cancer cells - Lin Wang; Lin Shi; Jie Gu; Cheng Zhan; Junjie Xi; Jianyong Ding; Di Ge (Journal of Physiology and Biochemistry, 2018)

Virtual Issue #2: Contribution of Chinese research to the field of environmental contamination and toxicology: The most cited papers published in BECT from 2012–2017 - Huan Zhong; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2018)

Oceanic plate subduction history in the western Pacific Ocean: Constraint from late Mesozoic evolution of the Tan-Lu Fault Zone - Guang Zhu; Cheng Liu; Chengchuan Gu; Shuai Zhang; Yunjian Li; Nan Su; Shiye Xiao (Science China Earth Sciences, 2018)

Recent advances in microbial production of mannitol: utilization of low-cost substrates, strain development and regulation strategies - Min Zhang; Lei Gu; Chao Cheng; Jiangfeng Ma; Fengxue Xin; Junli Liu; Hao Wu; Min Jiang (World Journal of Microbiology and Biotechnology, 2018)

Neuroprotective Effect and Mechanism of Action of Tetramethylpyrazine Nitrone for Ischemic Stroke Therapy - Gaoxiao Zhang; Tao Zhang; Liangmiao Wu; Xinhua Zhou; Jianbo Gu; Cuimei Li; Wei Liu; Cheng Long; Xifei Yang; Luchen Shan; Lipeng Xu; Yuqiang Wang; et al. (NeuroMolecular Medicine, 2018)

Rf4 has minor effects on the fertility restoration of wild abortive-type cytoplasmic male sterile japonica (Oryza sativa) lines - Honggen Zhang; Xiaojun Cheng; Lijia Zhang; Hua Si; Yongshen Ge; Minghong Gu; Shuzhu Tang (Euphytica, 2018)

New triterpenoid saponins from the steaming treated roots of Panax notoginseng - Cheng-Zhen Gu; Yi-Jun Qiao; Dong Wang; Hong-Tao Zhu; Chong-Ren Yang; Min Xu; Ying-Jun Zhang (Natural Product Research, 2018)

Spatial and temporal distribution of Neolithic sites in coastal China: Sea level changes, geomorphic evolution and human adaption - HongBo Zheng; YouSheng Zhou; Qing Yang; ZhuJun Hu; GuangJiu Ling; JuZhong Zhang; ChunGuang Gu; YingYing Wang; YeTing Cao; XianRong Huang; Yue Cheng; XiaoYu Zhang; et al. (Science China Earth Sciences, 2018)

An anti-Propionibacterium acnes antibody shows heterologous resistance to an Actinobacillus pleuropneumoniae infection independent of neutrophils in mice - Jian-fang Liu; Qiu-yue Ma; Ri-ning Zhu; Meng-jun Cheng; Chun-tong Bao; Jing-min Gu; Chang-jiang Sun; Paul Richard Langford; Wen-yu Han; Lian-cheng Lei (Immunologic Research, 2017)

Population genetic diversity of marble goby (Oxyeleotris marmoratus) inferred from mitochondrial DNA and microsatellite analysis - Cheng Zhao; Xiaoping Zhu; Yichun Gu; Qintao Wang; Zecheng Li; Shaowu Yin (Journal of Genetics, 2017)

Cerebral perfusion alterations in type 2 diabetes and its relation to insulin resistance and cognitive dysfunction - Ying Cui; Xia Liang; Hong Gu; Yuzheng Hu; Zhen Zhao; Xiang-Yu Yang; Cheng Qian; Yihong Yang; Gao-Jun Teng (Brain Imaging and Behavior, 2017)

Identification of HIF-1 signaling pathway in Pelteobagrus vachelli using RNA-Seq: effects of acute hypoxia and reoxygenation on oxygen sensors, respiratory metabolism, and hematology indices - Guosong Zhang; Cheng Zhao; Qintao Wang; Yichun Gu; Zecheng Li; Panfeng Tao; Jiawei Chen; Shaowu Yin (Journal of Comparative Physiology B, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

Estrogen receptor beta mediates hepatotoxicity induced by perfluorooctane sulfonate in mouse - Cheng Xu; Zhao-Yan Jiang; Qian Liu; Hui Liu; Aihua Gu (Environmental Science and Pollution Research, 2017)

Effects of portable solar water quality control machines on aquaculture ponds - Xingguo Liu; Hao Xu; Guofeng Cheng; Chong Liu; Shijing Liu; Shimin Lu; Changfeng Tian; Rong Tang; Zhaojun Gu (Environmental Science and Pollution Research, 2017)

Nonstationarity-based evaluation of flood risk in the Pearl River basin: changing patterns, causes and implications - Xihui Gu; Qiang Zhang; Vijay P. Singh; Mingzhong Xiao; Jinqiang Cheng (Hydrological Sciences Journal, 2017)

Theoretical investigation of congener-specific soil sorption of polychlorinated biphenyls by DFT computation and potent QSAR analyses - Mengrong Zhu; Chenggang Gu; Yinwen Cheng; Xuehai Ju; Yongrong Bian; Xinglun Yang; Yang Song; Mao Ye; Fang Wang; Xin Jiang (Journal of Soils and Sediments, 2017)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Penimethavone A, a flavone from a gorgonian-derived fungus Penicillium chrysogenum - Xue-Mei Hou; Chang-Yun Wang; Yu-Cheng Gu; Chang-Lun Shao (Natural Product Research, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Does Concurrent Use of Some Botanicals Interfere with Treatment of Tuberculosis? - William R. Folk; Aaron Smith; Hailong Song; Dennis Chuang; Jianlin Cheng; Zezong Gu; Grace Sun (NeuroMolecular Medicine, 2016)

Association of gene polymorphisms of FV, FII, MTHFR, SERPINE1, CTLA4, IL10, and TNFalpha with pre-eclampsia in Chinese women - Lu Zhou; Li Cheng; Yun He; Yin Gu; Yejun Wang; Chenhong Wang (Inflammation Research, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

PA-X-associated early alleviation of the acute lung injury contributes to the attenuation of a highly pathogenic H5N1 avian influenza virus in mice - Jiao Hu; Yiqun Mo; Zhao Gao; Xiaoquan Wang; Min Gu; Yanyan Liang; Xin Cheng; Shunlin Hu; Wenbo Liu; Huimou Liu; Sujuan Chen; Xiaowen Liu; et al. (Medical Microbiology and Immunology, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Roseomonas chloroacetimidivorans sp. nov., a chloroacetamide herbicide-degrading bacterium isolated from activated sludge - Cui-Wei Chu; Qing Chen; Cheng-Hong Wang; Hong-Mei Wang; Zhong-Guan Sun; Qin He; Jian He; Jin-Gang Gu (Antonie van Leeuwenhoek, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Toll-Like Receptor 4 Deficiency Causes Reduced Exploratory Behavior in Mice Under Approach-Avoidance Conflict - Chunlu Li; Yixiu Yan; Jingjing Cheng; Gang Xiao; Jueqing Gu; Luqi Zhang; Siyu Yuan; Junlu Wang; Yi Shen; Yu-Dong Zhou (Neuroscience Bulletin, 2016)

Extracting urban areas in China using DMSP/OLS nighttime light data integrated with biophysical composition information - Yang Cheng; Limin Zhao; Wei Wan; Lingling Li; Tao Yu; Xingfa Gu (Journal of Geographical Sciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Chitosan Degradation Products Promote Nerve Regeneration by Stimulating Schwann Cell Proliferation via miR-27a/FOXO1 Axis - Yongjun Wang; Yahong Zhao; Cheng Sun; Wen Hu; Jing Zhao; Guicai Li; Luzhong Zhang; Mei Liu; Yan Liu; Fei Ding; Yumin Yang; Xiaosong Gu (Molecular Neurobiology, 2016)

Analysis of Mineral Elements, Metabolism, and Inflammation Indexes in the Plasma of Dairy Cows Suffering from Different Degrees of Lameness - Dongbo Sun; Chunqiu Li; Cheng Gu; Jianfei Chen; Yongli Qu; Xinyu Wang; Jing Gao; Shan Wei; Jianfa Wang; Rui Wu; Donghua Guo (Biological Trace Element Research, 2015)

Levels and ecological risk assessment of metals in soils from a typical e-waste recycling region in southeast China - Weituo Zhao; Lei Ding; Xiaowen Gu; Jie Luo; Yunlang Liu; Li Guo; Yi Shi; Ting Huang; Shenggao Cheng (Ecotoxicology, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Dynamic evolution of resistance gene analogs in the orthologous genomic regions of powdery mildew resistance gene MlIW170 in Triticum dicoccoides and Aegilops tauschii - Yong Liang; De-Yun Zhang; Shuhong Ouyang; Jingzhong Xie; Qiuhong Wu; Zhenzhong Wang; Yu Cui; Ping Lu; Dong Zhang; Zi-Ji Liu; Jie Zhu; Yong-Xing Chen; et al. (Theoretical and Applied Genetics, 2015)

Endoplasmic reticulum stress participates in the progress of senescence of bone marrow-derived mesenchymal stem cells in patients with systemic lupus erythematosus - Zhifeng Gu; Yan Meng; Tao Tao; Genkai Guo; Wei Tan; Yunfei Xia; Chun Cheng; Hong Liu (Cell and Tissue Research, 2015)

Risk factors of severe hand, foot and mouth disease complicated with cardiopulmonary collapse - Chunlan Song; Cheng Yibing; Yanjun Guo; Zhipeng Jin; Yajie Cui; Xue Gu (Infectious Diseases, 2015)

Joint toxicity of tetracycline with copper(II) and cadmium(II) to Vibrio fischeri: effect of complexation reaction - Fei Tong; Yanping Zhao; Xueyuan Gu; Cheng Gu; Charles C.C. Lee (Ecotoxicology, 2015)

Multicenter Study on Adult Growth Hormone Level in Postoperative Pituitary Tumor Patients - Jing-min Cheng; Jian-wen Gu; Yong-qin Kuang; Yuan Ma; Xun Xia; Tao Yang; Min Lu; Wei-qi He; Zhi-yong Sun; Yan-chao Zhang (Cell Biochemistry and Biophysics, 2015)

Isolation and characterization of twenty polymorphic microsatellites for Hemibarbus labeo (Cyprinidae) - Cuiyun Lu; Ying Gu; Longwu Geng; Lei Cheng; Chao Li; Guangxiang Tong; Haifeng Jiang; Shahid Mahboob; Wei Xu; Xiaowen Sun (Conservation Genetics Resources, 2015)

Effects of metal cations and fulvic acid on the adsorption of ciprofloxacin onto goethite - Yinyue Tan; Yong Guo; Xueyuan Gu; Cheng Gu (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Interferon-γ produced by tumor-infiltrating NK cells and CD4+ T cells downregulates TNFSF15 expression in vascular endothelial cells - Yi Lu; Xin Gu; Li Chen; Zhi Yao; Juan Song; Xiulong Niu; Rong Xiang; Tao Cheng; Zhihai Qin; Weimin Deng; Lu-Yuan Li (Angiogenesis, 2014)

Development and characterization of eighteen microsatellites for endangered fish Huso dauricus - Lu Cuiyun; Yin Qianqian; Cheng Lei; Gu Ying; Li Chao; Sun Xiaowen (Conservation Genetics Resources, 2014)

Aquamicrobium terrae sp. nov., isolated from the polluted soil near a chemical factory - Zhi-Guo Wu; Fang Wang; Cheng-Gang Gu; Yin-Ping Zhang; Zong-Zheng Yang; Xiao-Wei Wu; Xin Jiang (Antonie van Leeuwenhoek, 2014)

Isolation, molecular cloning and characterization of a cold-responsive gene, AmDUF1517, from Ammopiptanthus mongolicus - Lijiang Gu; Hongmei Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Age distribution patterns of human gene families: divergent for Gene Ontology categories and concordant between different subcellular localizations - Gangbiao Liu; Yangyun Zou; Qiqun Cheng; Yanwu Zeng; Xun Gu; Zhixi Su (Molecular Genetics and Genomics, 2014)

Cyclic AMP-Dependent Protein Kinase Enhances SC35-Promoted Tau Exon 10 Inclusion - Caoyi Chen; Nana Jin; Wei Qian; Wen Liu; Xiangling Tan; Fei Ding; Xiaosong Gu; Khalid Iqbal; Cheng-Xin Gong; Ji Zuo; Fei Liu (Molecular Neurobiology, 2014)

Wnt/β-catenin signaling mediates the senescence of bone marrow-mesenchymal stem cells from systemic lupus erythematosus patients through the p53/p21 pathway - Zhifeng Gu; Wei Tan; Guijuan Feng; Yan Meng; Biyu Shen; Hong Liu; Chun Cheng (Molecular and Cellular Biochemistry, 2014)

Assessment of wheat variety stability using SSR markers - Li Xin Wang; Hong Bo Li; Tie Cheng Gu; Li Hua Liu; Bin Shuang Pang; Jun Qiu; Chang Ping Zhao (Euphytica, 2014)

Replacing Shox2 with human SHOX leads to congenital disc degeneration of the temporomandibular joint in mice - Xihai Li; Hongbing Liu; Shuping Gu; Chao Liu; Cheng Sun; Yuqian Zheng; YiPing Chen (Cell and Tissue Research, 2014)

Deep RNA-Seq uncovers the peach transcriptome landscape - Lu Wang; Shuang Zhao; Chao Gu; Ying Zhou; Hui Zhou; Juanjuan Ma; Jun Cheng; Yuepeng Han (Plant Molecular Biology, 2013)

The discovery of 3-(1-aminoethylidene)quinoline-2, 4(1H,3H)-dione derivatives as novel PSII electron transport inhibitors - Yu-Xiu Liu; Hua-Ping Zhao; Zi-Wen Wang; Yong-Hong Li; Hai-Bin Song; Hannah Riches; David Beattie; Yu-Cheng Gu; Qing-Min Wang (Molecular Diversity, 2013)

Combined structure-based pharmacophore, virtual screening, and 3D-QSAR studies of structural diverse dehydrosqualene synthase inhibitors - Fei Peng; Aihua Peng; Youfu Luo; Wei Huang; Bo Han; Xiaoyan Yang; Wei Ang; Tao Yang; Mingli Xiang; Cheng Peng; Gu He (Medicinal Chemistry Research, 2013)

The spatial–temporal variations in optical properties of atmosphere aerosols derived from AERONET dataset over China - H. Chen; X. Gu; T. Cheng; Z. Li; T. Yu (Meteorology and Atmospheric Physics, 2013)

Assessment of private economic benefits and positive environmental externalities of tea plantation in China - Hui Xue; Xiaoyi Ren; Shiyu Li; Xu Wu; Hao Cheng; Bin Xu; Baojing Gu; Guofu Yang; Changhui Peng; Ying Ge; Jie Chang (Environmental Monitoring and Assessment, 2013)

Dynamic Changes of Jab1 and p27kip1 Expression in Injured Rat Sciatic Nerve - Xinghai Cheng; Zhengming Zhou; Guangfei Xu; Jing Zhao; Hao Wu; Long Long; Hai Wen; Xingxing Gu; Youhua Wang (Journal of Molecular Neuroscience, 2013)

Transcription Initiation Factor IIB Involves in Schwann Cell Differentiation after Rat Sciatic Nerve Crush - Jiao Yang; Jianhua Cao; Youhua Wang; Jian Xu; Zhengming Zhou; Xingxing Gu; Xiaojuan Liu; Hai Wen; Hao Wu; Chun Cheng (Journal of Molecular Neuroscience, 2013)

A radiation hybrid map of chromosome 1D reveals synteny conservation at a wheat speciation locus - Monika K. Michalak de Jimenez; Filippo M. Bassi; Farhad Ghavami; Kristin Simons; Rissa Dizon; Raed I. Seetan; Loai M. Alnemer; Anne M. Denton; Münevver Doğramacı; Hana Šimková; Jaroslav Doležel; Kiran Seth; et al. (Functional & Integrative Genomics, 2013)

Wheat Zapper: a flexible online tool for colinearity studies in grass genomes - Loai M. Alnemer; Raed I. Seetan; Filippo M. Bassi; Charith Chitraranjan; Adam Helsene; Paul Loree; Steve Bou Goshn; Yong Q. Gu; Ming-Cheng Luo; M. Javed Iqbal; Gerard R. Lazo; Anne M. Denton; et al. (Functional & Integrative Genomics, 2013)

Analysis of molecular variation of porcine reproductive and respiratory syndrome virus in Central China from 2006 to 2012 - Yuejun Shi; Zhibin Hu; Zhenghui Xiong; Yanjun Zhou; Xin Jin; Changqin Gu; Xueying Hu; Guofu Cheng; Nianhua Song; Wanpo Zhang (Archives of Virology, 2013)

Coordinated regulation of anthocyanin biosynthesis through photorespiration and temperature in peach (Prunus persica f. atropurpurea) - Ying Zhou; Dong Guo; Jing Li; Jun Cheng; Hui Zhou; Chao Gu; Sue Gardiner; Yue-Peng Han (Tree Genetics & Genomes, 2013)

Increased expression of Gem after rat sciatic nerve injury - Youhua Wang; Xinghai Cheng; Zhengming Zhou; Hao Wu; Long Long; Xingxing Gu; Guangfei Xu (Journal of Molecular Histology, 2013)

Formaldehyde Impairs Learning and Memory Involving the Disturbance of Hydrogen Sulfide Generation in the Hippocampus of Rats - Xiao-Qing Tang; Yuan-Yuan Zhuang; Ping Zhang; Heng-Rong Fang; Cheng-Fang Zhou; Hong-Feng Gu; Hui Zhang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2013)

Exploring the diploid wheat ancestral A genome through sequence comparison at the high-molecular-weight glutenin locus region - Lingli Dong; Naxin Huo; Yi Wang; Karin Deal; Ming-Cheng Luo; Daowen Wang; Olin D. Anderson; Yong Qiang Gu (Molecular Genetics and Genomics, 2012)

Effect of groundwater geochemistry on pentachlorophenol remediation by smectite-templated nanosized Pd0/Fe0 - Hanzhong Jia; Cheng Gu; Hui Li; Xiaoyun Fan; Shouzhu Li; Chuanyi Wang (Environmental Science and Pollution Research, 2012)

Atmospheric scattering and turbulence modulation transfer function for CCD cameras on CBERS-02b and HJ-1A/1B - Xiaoying Li; Xingfa Gu; Tao Yu; Tianhai Cheng; Jiaguo Li; Hailiang Gao; Zuo Wang (International Journal of Remote Sensing, 2012)

The distribution of IGF2 and IMP3 in osteosarcoma and its relationship with angiogenesis - Peng Chen; Shao-jin Wang; Hong-bo Wang; Peng Ren; Xi-qian Wang; Wen-guang Liu; Wan-li Gu; Dong-qing Li; Ting-guo Zhang; Cheng-jun Zhou (Journal of Molecular Histology, 2012)

Characterizing the walnut genome through analyses of BAC end sequences - Jiajie Wu; Yong Q. Gu; Yuqin Hu; Frank M. You; Abhaya M. Dandekar; Charles A. Leslie; Mallikarjuna Aradhya; Jan Dvorak; Ming-Cheng Luo (Plant Molecular Biology, 2012)

A linkage map of cultivated cucumber (Cucumis sativus L.) with 248 microsatellite marker loci and seven genes for horticulturally important traits - Han Miao; Shengping Zhang; Xiaowu Wang; Zhonghua Zhang; Man Li; Shengqi Mu; Zhouchao Cheng; Ruowei Zhang; Sanwen Huang; Bingyan Xie; Zhiyuan Fang; Zhenxian Zhang; et al. (Euphytica, 2011)

Comparison of a high-density genetic linkage map to genome features in the model grass Brachypodium distachyon - Naxin Huo; David F. Garvin; Frank M. You; Stephanie McMahon; Ming-Cheng Luo; Yong Q. Gu; Gerard R. Lazo; John Philip Vogel (Theoretical and Applied Genetics, 2011)

Initial research on the polarized reflectance of typical urban surface types measured by the Directional Polarimetric Camera - DongHai Xie; XingFa Gu; TianHai Cheng; Tao Yu; ZhengQiang Li; XingFeng Chen; Hao Chen; Jing Guo (Science China Earth Sciences, 2011)

Plasminogen K5 activates mitochondrial apoptosis pathway in endothelial cells by regulating Bak and Bcl-xL subcellular distribution - Xiaoqiong Gu; Yachao Yao; Rui Cheng; Yang Zhang; Zhiyu Dai; Genping Wan; Zhonghan Yang; Weibin Cai; Guoquan Gao; Xia Yang (Apoptosis, 2011)

EHPC 2010: sharing knowledge on environmental health for risk mitigation - T. E. Ford; A. L. Bass; S. Cheng; G. N. Cherr; B. Cole; E. Fairbairn; J.-D. Gu; R. S. Halbrook; F. E. Löffler; E. L. Madsen; N. A. McGinn (Ecotoxicology, 2011)

Reproductive toxicity in male mice exposed to Nanjing City tap water - Dayong Zhao; Yajun Chen; Kemei Zhou; Shupei Cheng; Ting Ma; Cuiling Jiang; Wenming Yan; Liqin Zhu; Xijun Gu; Xiaohua Zhu; Bing Wu; Yan Zhang; et al. (Ecotoxicology, 2011)

Comparative analysis of binding affinities between styrene and mammalian CYP2E1 by bioinformatics approaches - Bing Wu; Jie Sun; Shu-Pei Cheng; Ji-Dong Gu; Ai-Min Li; Xu-Xiang Zhang (Ecotoxicology, 2011)

Fine genetic mapping localizes cucumber scab resistance gene Ccu into an R gene cluster - Houxiang Kang; Yiqun Weng; Yuhong Yang; Zhonghua Zhang; Shengping Zhang; Zhenchuan Mao; Guohua Cheng; Xingfang Gu; Sanwen Huang; Bingyan Xie (Theoretical and Applied Genetics, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

VKORC1-1639G>A, CYP2C9, EPHX1691A>G genotype, body weight, and age are important predictors for warfarin maintenance doses in patients with mechanical heart valve prostheses in southwest China - Qiang Gu; Yan Kong; Jörn Schneede; Ying-Bin Xiao; Lin Chen; Qian-Jin Zhong; Xue-Feng Wang; Jia Hao; Bai-Cheng Chen; Jing-Jin Chen (European Journal of Clinical Pharmacology, 2010)

Cu(II): a “signaling molecule” of the mangrove endophyte Fusarium oxysporum ZZF51? - Jia-hui Pan; Yong-cheng Lin; Ni Tan; Yu-cheng Gu (BioMetals, 2010)

Preliminary Evidence that Copper and Zinc Inhibits the Dissipation of Synthetic Pyrethroid in Red Soil - Xiao-zhi Gu; Lei Zhang; Gang-ya Zhang; Cheng-xin Fan; Li Chen (Water, Air, & Soil Pollution, 2010)

Personalized image-based templates for precise acetabular prosthesis placement in total hip arthroplasty: a pilot study - Bin Chen; Sheng-xiang Xiao; Peng-cheng Gu; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2010)

A brief account on the study of the insulin crystal structure - Da-Cheng Wang; XiaoCheng Gu (Science China Life Sciences, 2010)

Effects of Gestational Cadmium Exposure on Pregnancy Outcome and Development in the Offspring at Age 4.5 Years - Li-Li Tian; Yong-Cheng Zhao; Xiao-Chun Wang; Jin-Long Gu; Zhi-Juan Sun; Ya-Li Zhang; Ji-Xian Wang (Biological Trace Element Research, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

The hydroxyl radical generation and oxidative stress for the earthworm Eisenia fetida exposed to tetrabromobisphenol A - Yingang Xue; Xueyuan Gu; Xiaorong Wang; Cheng Sun; Xianghua Xu; Jian Sun; Baogang Zhang (Ecotoxicology, 2009)

Saturation and comparative mapping of the genomic region harboring Hessian fly resistance gene H26 in wheat - Guo Tai Yu; Xiwen Cai; Marion O. Harris; Yong Qiang Gu; Ming-Cheng Luo; Steven S. Xu (Theoretical and Applied Genetics, 2009)

Structural characterization of Brachypodium genome and its syntenic relationship with rice and wheat - Naxin Huo; John P. Vogel; Gerard R. Lazo; Frank M. You; Yaqin Ma; Stephanie McMahon; Jan Dvorak; Olin D. Anderson; Ming-Cheng Luo; Yong Q. Gu (Plant Molecular Biology, 2009)

Morphology, ecology, and contaminant removal efficiency of eight wetland plants with differing root systems - Xiu-Yun Cheng; Wen-Yin Chen; Bin-He Gu; Xu-Cheng Liu; Fang Chen; Zhang-He Chen; Xian-Ye Zhou; Yu-Xiang Li; Hua Huang; Yun-Jin Chen (Hydrobiologia, 2009)

Development and genetic mapping of microsatellite markers from genome survey sequences in Brassica napus - Xiaomao Cheng; Jinsong Xu; Shu Xia; Jianxun Gu; Yuan Yang; Jie Fu; Xiaoju Qian; Shunchang Zhang; Jiangsheng Wu; Kede Liu (Theoretical and Applied Genetics, 2009)

Evaled Expression of ICAM-1 and Its Ligands in the Rat Spinal Cord Following Lipopolysaccharide Intraspinal Injection - Junling Yang; Min Fei; Yangyang Gu; Linlin Sun; Zhiyun Ben; Dan Zhou; Jianping Chen; Youhua Wang; Ping Wang; Aiguo Shen; Chun Cheng (NeuroMolecular Medicine, 2008)

ROLLED LEAF 9, encoding a GARP protein, regulates the leaf abaxial cell fate in rice - Song Yan; Chang-Jie Yan; Xiu-Hong Zeng; Ya-Chun Yang; Yu-Wei Fang; Chun-Yan Tian; Ya-Wei Sun; Zhu-Kuan Cheng; Ming-Hong Gu (Plant Molecular Biology, 2008)

The nuclear genome of Brachypodium distachyon: analysis of BAC end sequences - Naxin Huo; Gerard R. Lazo; John P. Vogel; Frank M. You; Yaqin Ma; Daniel M. Hayden; Devin Coleman-Derr; Theresa A. Hill; Jan Dvorak; Olin D. Anderson; Ming-Cheng Luo; Yong Q. Gu (Functional & Integrative Genomics, 2008)

Polychlorinated Biphenyls (PCBs) in PM10 Surrounding a Chemical Industrial Zone in Shanghai, China - Jin-Ping Cheng; Qian Wu; Hai-Ying Xie; Jin-Min Gu; Wen-Chang Zhao; Jing Ma; Wen-Hua Wang (Bulletin of Environmental Contamination and Toxicology, 2007)

Suppression of colorectal tumor growth by regulated survivin targeting - Binghua Li; Junkai Fan; Xinran Liu; Rong Qi; Linan Bo; Jinfa Gu; Cheng Qian; Xinyuan Liu (Journal of Molecular Medicine, 2006)

Diversity of centromeric repeats in two closely related wild rice species, Oryza officinalis and Oryza rhizomatis - Weidong Bao; Wenli Zhang; Qiuying Yang; Yu Zhang; Bin Han; Minghong Gu; Yongbiao Xue; Zhukuan Cheng (Molecular Genetics and Genomics, 2006)

The Geographical Society of China - Lu Dadao; Bao Jigang; Cai Yunlong; Cheng Guodong; Fu Bojie; Gu Chaolin; Li Xiubin; Shi Peijun; Song Changqing; Xu Shiyuan; Zhang Guoyou (Journal of Geographical Sciences, 2004)

Lung cancer risk in germline p53 mutation carriers: association between an inherited cancer predisposition, cigarette smoking, and cancer risk - Li Shu-Chung Cheng; Guillermina Lozano; Christopher I. Amos; Xiangjun Gu; Louise C. Strong; Shih-Jen Hwang (Human Genetics, 2003)

Isolation and characterization of a human putative receptor protein kinase cDNA STYK1* - Xin Ye; Chaoneng Ji; Qingshan Huang; Chao Cheng; Rong Tang; Jian Xu; Li Zeng; Jianfeng Dai; Qihan Wu; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Molecular cloning and characterization of a novel human kinase gene,PDIK1L - Lingchen Guo; Chaoneng Ji; Shaohua Gu; Kang Ying; Haipeng Cheng; Xiaoghua Ni; Jianping Liu; Yi Xie; Yumin Mao (Journal of Genetics, 2003)

Note: Isolation and Characterization of a Novel Human Putative Anemia-Related Gene Homologous to Mouse Sideroflexin - Xin Ye; Jian Xu; Chao Cheng; Gang Yin; Li Zeng; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Biochemical Genetics, 2003)

Cloning, expression and characterization of a novel human VMP gene* - Chao Cheng; Jian Xu; Xin Ye; Jianfeng Dai; Qihan Wu; Li Zeng; Liu Wang; Wei Zhao; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2002)

A novel human hydroxysteroid dehydrogenase like 1 gene (HSDL1) is highly expressed in reproductive tissuesa - Yan Huang; Rong Tang; Jianfeng Dai; Shaohua Gu; Wei Zhao; Chao Cheng; Ming Xu; Zongxiang Zhou; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2001)

B chromosome in a rice aneuploid variation - Z. K. Cheng; H. X. Yu; H. H. Yan; M. H. Gu; L. H. Zhu (Theoretical and Applied Genetics, 2000)

Alteration of N-acetylglucosaminyltransferases in pancreatic carcinoma - Bi-cheng Nan; Dong-min Shao; Hui-li Chen; Yong Huang; Jian-xin Gu; Yi-bin Zhang; Zhao-guang Wu (Glycoconjugate Journal, 1998)